Protein polyurethane alloy material
By developing protein polyurethane alloy materials for textiles, addressing environmental and resource issues in traditional leather production, it provides a sustainable alternative that maintains similar properties and appearance to natural leather.
Patent Information
- Application Number
- CN202380062479.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-18
- Filing Date
- 2023-08-17
- Publication Date
- 2025-04-18
AI Technical Summary
Traditional leather production has environmental pollution, resource consumption and social problems, and the supply of high-quality leather is reduced, making it difficult to meet market demand.
Develop materials containing protein polyurethane alloys for textiles or fabric products as alternatives to natural leather. The material consists of textiles, protein polyurethane alloys and fat-adding agents, and the protein is dissolved in polyurethane to provide strength and wear resistance.
The material can provide a sustainable alternative while maintaining the appearance and mechanical properties similar to natural leather while reducing environmental pollution and resource consumption during production.
Smart Images

Figure CN119855955A_ABST
Abstract
Description
[0001] References to sequence listings submitted electronically
[0002] The contents of the sequence listing submitted electronically in the ASCII text file submitted with this application (name: 4431_091PC01_Seqlisting_ST26.xml; size: 4,669 bytes; creation date: August 10, 2023) are incorporated herein by reference in their entirety. Technical Field
[0003] The present disclosure relates to materials comprising protein polyurethane alloys, which comprise one or more proteins dissolved in polyurethane. In particular embodiments, the present disclosure relates to materials comprising protein polyurethane alloys and textile substrates. In some embodiments, these materials can be used to make textiles or fabric articles, such as textiles or fabric articles typically prepared from natural leather. Background Art
[0004] Leather is a common product used in many industries, including: the furniture industry, where leather is often used as a furniture upholstery material; the apparel industry, where leather is used to make pants and jackets; the footwear industry, where leather is used to make casual and dress shoes; the luggage industry; the handbags and accessories industry; and the automotive industry. The global trade value of leather is high, and the demand for leather products continues to grow. Although leather seems to be everywhere, there are various costs, restrictions, and social issues associated with producing natural leather. First, natural leather is made from animal skins, so livestock must be raised and slaughtered. Raising livestock requires large amounts of feed, pasture, water, and fossil fuels, and can cause air and waterway pollution, such as through greenhouse gases such as methane. Leather production also raises social issues related to the treatment of animals. In recent years, the supply of traditional high-quality leather has also seen a considerable decline. For at least these reasons, it is desirable to find alternative ways to meet the demand for leather.
[0005] In addition, other textile or fabric materials (such as cotton and spandex) are used in many industries, including the furniture industry and the clothing industry. The demand for such materials is high, and there is a constant need for improved textile and fabric materials. Summary of the invention
[0006] The present disclosure provides materials comprising protein polyurethane alloys. These materials can be used in a variety of applications, including as a replacement for natural leather and in other textile and fabric applications.
[0007] The first embodiment (1) of the present disclosure is directed to a material comprising: a textile; a protein-polyurethane alloy disposed on the textile, the protein-polyurethane alloy comprising a protein dissolved in a polyurethane; and about 1 wt % to about 16 wt % of one or more fatliquors.
[0008] In a second embodiment (2), the protein polyurethane alloy according to the first embodiment (1) comprises greater than 50% by weight of the protein.
[0009] In a third embodiment (3), the protein-polyurethane alloy according to the first embodiment (1) comprises about 60 wt % to about 90 wt % of the protein.
[0010] In a fourth embodiment (4), the one or more fatliquors according to any one of embodiments (1) to (3) comprise a functionalized oil.
[0011] In a fifth embodiment (5), the one or more fatliquors according to any one of embodiments (1) to (3) are selected from the group consisting of sulfited fatliquors, sulfated fatliquors or combinations thereof.
[0012] In a sixth embodiment (6), the material according to any one of embodiments (1) to (5) has an elastic modulus of 9*10^7 Pa or less.
[0013] In a seventh embodiment (7), the material according to any one of embodiments (1) to (5) has an elastic modulus of 6*10^7 Pa or less.
[0014] The eighth embodiment (8) of the present disclosure relates to a material comprising: a textile; a protein polyurethane alloy comprising a protein dissolved in a polyurethane; a first part having a first protein polyurethane alloy density; and a second part having a second protein polyurethane alloy density different from the first protein polyurethane alloy density.
[0015] In a ninth embodiment (9), in the material according to the eighth embodiment (8), the density of the first protein polyurethane alloy is smaller or larger than the density of the second protein polyurethane alloy by 5% or more.
[0016] In the tenth embodiment (10), the first portion of the material according to the eighth embodiment (8) or the ninth embodiment (9) includes a first protein polyurethane alloy layer, and the second portion of the material according to the eighth embodiment (8) or the ninth embodiment (9) includes a second protein polyurethane alloy layer.
[0017] In an eleventh embodiment (11), in the material according to the tenth embodiment (10), the textile includes a top surface and a bottom surface, the first protein polyurethane alloy layer is arranged on the top surface of the textile, and the second protein polyurethane alloy layer is arranged on the bottom surface of the textile.
[0018] In a twelfth embodiment (12), in the material according to the eighth embodiment (8) or the ninth embodiment (9), the first portion comprises the protein polyurethane alloy integrated into the textile at the first protein polyurethane alloy density, and the second portion comprises the protein polyurethane alloy integrated into the textile at the second protein polyurethane alloy density.
[0019] In a thirteenth embodiment (13), in the material according to the eighth embodiment (8) or the ninth embodiment (9), the textile includes a first textile layer connected to a second textile layer, the first portion includes the protein polyurethane alloy integrated into the first textile layer at the first protein polyurethane alloy density, and the second portion includes the protein polyurethane alloy integrated into the second textile layer at the second protein polyurethane alloy density.
[0020] In a fourteenth embodiment (14), the material according to any one of embodiments (8) to (13) further comprises a crosslinking agent selected from the group consisting of an epoxy-based crosslinking agent, an isocyanate-based crosslinking agent, and a carbodiimide-based crosslinking agent.
[0021] In a fifteenth embodiment (15), the crosslinking agent according to the fourteenth embodiment (14) is a carbodiimide-based crosslinking agent.
[0022] The sixteenth embodiment (16) of the present disclosure is directed to an aqueous formulation comprising: water; an aqueous polyurethane dispersion; a protein; about 4 wt % to about 10 wt % of one or more colored dyes; and a foam stabilizer.
[0023] In a seventeenth embodiment (17), the protein according to the sixteenth embodiment (16) is dissolved in the polyurethane of the polyurethane dispersion.
[0024] The eighteenth embodiment (18) of the present disclosure relates to a material comprising: a textile; a protein-polyurethane alloy integrated into the textile, the protein-polyurethane alloy comprising a protein dissolved in a polyurethane; and about 100 wt % to about 250 wt % of one or more colored dyes, the weight % of the one or more colored dyes being measured relative to the weight of the protein in the protein-polyurethane alloy. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The accompanying drawings incorporated herein form a part of this specification and illustrate embodiments of the present disclosure. These drawings, together with the specification, are further used to explain the principles of the embodiments of the present disclosure and enable those skilled in the relevant art to implement and use the embodiments of the present disclosure. These drawings are intended to be exemplary and non-restrictive. Although the present disclosure is generally described in the context of these embodiments, it should be understood that the scope of the present disclosure is not intended to be limited to these specific embodiments. In the accompanying drawings, similar reference numerals indicate identical or functionally similar elements.
[0026] Figure 1 It is a dynamic mechanical analysis (DMA) graph of storage modulus and temperature for various materials.
[0027] Figure 2 is a graph showing the relationship between maximum tensile stress and gelatin weight percentage for gelatin-polyurethane alloys according to some embodiments.
[0028] Figure 3 is a graph showing the relationship between Young's modulus and gelatin weight percentage for gelatin-polyurethane alloys according to some embodiments.
[0029] Figure 4 It is a DMA plot of storage modulus and temperature for various materials.
[0030] Figure 5 is a graph showing the relationship between maximum tensile stress and weight percentage of soy protein isolate (SPI) for SPI polyurethane alloys according to some embodiments.
[0031] Figure 6 is a graph showing the relationship between Young's modulus and SPI weight percent for SPI polyurethane alloys according to some embodiments.
[0032] Figure 7 It is a DMA plot of storage modulus and temperature for various materials.
[0033] Fig. 8A is a graph comparing the maximum tensile stress of various protein polyurethane alloys according to some embodiments.
[0034] Figure 8B is a graph comparing the Young's modulus of various protein polyurethane alloys according to some embodiments.
[0035] Fig. 9 DMA thermograms comparing L3360 and gelatin L3360 alloy according to some embodiments.
[0036] Fig.10DMA thermograms comparing Hauthane HD-2001 polyurethane and gelatin Hauthane HD-2001 polyurethane alloys according to some embodiments.
[0037] Fig.11 SANCURE according to some embodiments TM 20025F Polyurethane and gelatin SANCURE TM DMA thermogram curve of 20025F polyurethane alloy.
[0038] Fig.12 According to some embodiments DLS Polyurethane and Gelatin DMA thermogram of DLS polyurethane alloy.
[0039] Fig.13 BONDTHANE according to some embodiments TM UD-108 POLYURETHANE AND GELATIN BONDTHANE TM DMA thermal spectrum curve of UD-108 polyurethane alloy.
[0040] Fig.14 BONDTHANE according to some embodiments TM UD-303 POLYURETHANE AND GELATIN BONDTHANE TM DMA thermal spectrum curve of UD-303 polyurethane alloy.
[0041] Fig.15 BONDTHANE according to some embodiments TM UD-250 POLYURETHANE AND GELATIN BONDTHANE TM DMA thermogram of UD-250 polyurethane alloy.
[0042] Fig.16 is a representative DMA graph illustrating a method of measuring a first DMA modulus transition onset temperature and a second DMA modulus transition onset temperature.
[0043] Fig.17A Materials comprising a protein polyurethane alloy integrated into a textile are shown according to some embodiments.
[0044] Fig. 17B Shown are materials comprising a protein polyurethane alloy integrated into a multilayer textile, according to some embodiments.
[0045] Fig. 17C Materials comprising a protein polyurethane alloy integrated into and forming a layer on a textile are shown according to some embodiments.
[0046] Fig.18A Layered materials according to some embodiments are shown.
[0047] Fig.18B A layered material including a non-foamed layer and a foamed layer according to some embodiments is shown.
[0048] Fig.19 is a block diagram illustrating a method for preparing a layered material according to some embodiments.
[0049] FIG. 20A to FIG. 20F Methods of preparing layered materials according to some embodiments are shown.
[0050] Fig.21 A spacer fabric according to some embodiments is shown.
[0051] Fig. 22 According to some embodiments DL 5249 polyurethane and soy protein isolate DMA thermogram of DL 5249 alloy.
[0052] Fig.23 is a graph measuring the weight of water transported through a construction of a multi-layered protein polyurethane alloy according to some embodiments as a change in weight versus time. DETAILED DESCRIPTION
[0053] The indefinite articles "a", "an" and "the" include plural referents unless clearly contradicted or the context clearly dictates otherwise.
[0054] The terms "comprising" and "including" are open transitional phrases. A list of elements following the transitional phrase "comprising" or "including" is a non-exclusive list such that elements other than those specifically recited in the list may be present. The phrase "consisting essentially of limits the composition of a component to the specified materials and materials that do not materially affect the basic and novel characteristics of the component. The phrase "consisting of limits the composition of a component to the specified materials and excludes any materials not specified.
[0055] When quoting the numerical range including the upper limit and the lower limit herein, unless otherwise specified in a particular case, the range is intended to include its endpoints, and all integers and fractions within the range. When limiting the range, it is not intended that the disclosure or claims be limited to the specific values cited. In addition, when equivalents, concentrations or other values or parameters are given with a range, one or more ranges or are given with a list of upper and lower limits, it should be understood to specifically disclose all ranges or values formed by any paired upper range limit and any lower range limit, regardless of whether such pairs are disclosed individually. Finally, when the term "about" is used to describe the endpoint of a value or range, the disclosure should be understood to include the specific value or endpoints mentioned. Regardless of whether the endpoint of a numerical value or range is described as "about", the endpoint of a numerical value or range is intended to include two embodiments: one is modified by "about", and one is not modified by "about".
[0056] As used herein, the term "about" refers to a value within the range of ±10% of the stated value. For example, about 3 MPa may include any value from 2.7 MPa to 3.3 MPa. That is, if a percentage is listed and the value of the percentage cannot be higher than 100%, such as 100% by weight or 99% by weight, "about" does not modify the percentage to include values higher than 100%.
[0057] As used herein, a first layer described as being "attached to" a second layer means that the layers are attached to each other by direct contact and attachment between the two layers or via one or more intermediate adhesive layers. The intermediate adhesive layer can be any layer used to attach the first layer to the second layer.
[0058] As used herein, the phrase "disposed on" means that a first component (e.g., a layer, alloy, or textile) is in direct contact with a second component. A first component "disposed on" a second component may be deposited, formed, placed, or otherwise applied directly to the second component. In other words, if a first component is disposed on a second component, there are no components between the first component and the second component.
[0059] As used herein, the phrase "disposed on" means that other components (eg, layers or substrates) may or may not exist between the first component and the second component.
[0060] As used herein, "bio-based polyurethane" is a polyurethane in which the structural units of the polyol (such as a diol) and the diacid (such as succinic acid) are derived from biomaterials such as corn starch.
[0061] As used herein, the term "substantially free" means that a component is present in a detectable amount of no more than about 0.1% by weight.
[0062] As used herein, the term "free of" means that the component is not present in the blend or material (eg, protein polyurethane alloy), even in trace amounts.
[0063] As used herein, "collagen" refers to a family of at least 28 different naturally occurring collagen types, including but not limited to I, II, III, IV, V, VI, VII, VIII, IX, X, XI, XII, XIII, XIV, XV, XVI, XVII, XVIII, XIX and XX collagen. As used herein, the term collagen also refers to collagen prepared using recombinant technology. The term collagen includes collagen, collagen fragments, collagen-like proteins, triple helical collagen, α chains, monomers, gelatin, trimers and combinations thereof. The recombinant expression of collagen and collagen-like proteins is known in the art (see, for example, Bell, EP 1232182B1, Bovine collagen and method for producing recombinant gelatin; Olsen et al., U.S. Patent 6,428,978, and Van Heerde et al., U.S. Patent 8,188,230, these patent documents are incorporated herein by reference in their entirety). Unless otherwise indicated, any type of collagen, whether naturally occurring or prepared using recombinant technology, can be used in any of the embodiments described herein. That is, in some embodiments, the collagen described herein can be prepared using bovine type I collagen. Collagen is characterized by a repeating triplet of amino acids, -(Gly-XY)n-, such that approximately one-third of the amino acid residues in collagen are glycine. X is typically proline, and Y is typically hydroxyproline. Thus, the structure of collagen can consist of three interwoven peptide chains of varying lengths. Different animals can produce different amino acid compositions of collagen, which can result in different properties (and differences in the resulting leather).
[0064] In some embodiments, collagen may be chemically modified to promote solubility in water.
[0065] Any type of collagen, truncated collagen, unmodified or post-translationally modified or amino acid sequence modified collagen can be used as part of the protein polyurethane alloy.
[0066] In some embodiments, the collagen can be a plant-based collagen. For example, the collagen can be a plant-based collagen prepared by CollPlant.
[0067] In some embodiments, the collagen solution can be fibrillated into collagen fibrils. As used herein, collagen fibrils refer to nanofibers composed of tropocollagen or tropocollagen-like structures (which have a triple helical structure). In some embodiments, triple helical collagen can be fibrillated to form nanofibers of collagen.
[0068] In some embodiments, recombinant collagen can include collagen fragments of the amino acid sequence of the native collagen molecule that can form procollagen (trimeric collagen). Recombinant collagen can also include collagen or truncated collagen with at least 70%, 80%, 90%, 95%, 96%, 97%, 98% or 99% homogeneity or similarity with the native collagen amino acid sequence (or with its fibril-forming region or with the segment that substantially comprises [Gly-XY]n). In some embodiments, the collagen fragment can be the 50kDa part of native collagen. The native collagen sequence includes the amino acid sequence of CollA1, CollA2 and Col3A1, which is described in Accession Nos. NP_001029211.1, NP_776945.1 and NP_001070299.1, and these sequences are incorporated herein by reference. In some embodiments, the collagen fragment may be a portion of human collagen alpha-1 (III) (Col3A1; Uniprot #P02461, Entrez Gene ID #1281). In some embodiments, the collagen fragment may be an amino acid sequence listed as SEQ ID NO: 1. In some embodiments, the collagen fragment may be an amino acid sequence listed as SEQ ID NO: 2. In some embodiments, the collagen fragment comprises an amino acid sequence having at least 80% sequence identity to SEQ ID NO: 2. Exemplary proteins comprising at least 80% sequence identity to SEQ ID NO: 2 are disclosed in PCT / US2022 / 027016, the disclosure of which is incorporated herein by reference.
[0069] Methods for producing recombinant collagen and recombinant collagen fragments are known in the art. For example, U.S. Publication Nos. 2019 / 0002893, 2019 / 0040400, 2019 / 0093116, and 2019 / 0092838 provide methods for producing collagen and collagen fragments, which can be used to produce recombinant collagen and recombinant collagen fragments disclosed herein. The contents of these four disclosures are incorporated herein by reference in their entirety.
[0070] The protein polyurethane alloys described herein may include proteins that are miscible with only one of the multiple phases of the polyurethane or with multiple polyurethanes blended therewith. For example, in some embodiments, the protein polyurethane alloys may include proteins that are miscible with only the hard phase of the polyurethane or with the multiple polyurethanes having both hard and soft phases. The protein polyurethane alloys described herein may be free of or substantially free of proteins in the form of particles dispersed in the polyurethane. For example, in some embodiments, the protein polyurethane alloys may be free of or substantially free of protein particles having an average diameter greater than 1 micron (μm).
[0071] In some embodiments, the protein polyurethane alloy may be free of or substantially free of soybean protein particles with an average diameter greater than 1 micron (μm). In some embodiments, the protein polyurethane alloy may be free of or substantially free of collagen particles with an average diameter greater than 1 micron (μm). In some embodiments, the protein polyurethane alloy may be free of or substantially free of gelatin particles with an average diameter greater than 1 micron (μm). In some embodiments, the protein polyurethane alloy may be free of or substantially free of bovine serum albumin particles with an average diameter greater than 1 micron (μm). In some embodiments, the protein polyurethane alloy may be free of or substantially free of pea protein particles with an average diameter greater than 1 micron (μm). In some embodiments, the protein polyurethane alloy may be free of or substantially free of egg white albumin particles with an average diameter greater than 1 micron (μm). In some embodiments, the protein polyurethane alloy may be free of or substantially free of casein particles with an average diameter greater than 1 micron (μm). In some embodiments, the protein polyurethane alloy may be free of or substantially free of peanut protein particles with an average diameter greater than 1 micron (μm). In some embodiments, the protein polyurethane alloy may be free of or substantially free of edema globulin particles with an average diameter greater than 1 micron (μm). In some embodiments, the protein polyurethane alloy may be free of or substantially free of whey protein particles having an average diameter greater than 1 micron (μm). In some embodiments, the protein polyurethane alloy may be free of or substantially free of karanja protein particles having an average diameter greater than 1 micron (μm). In some embodiments, the protein polyurethane alloy may be free of or substantially free of cellulase particles having an average diameter greater than 1 micron (μm). In some embodiments, the protein polyurethane alloy may be free of or substantially free of recombinant collagen fragment particles having an average diameter greater than 1 micron (μm).
[0072] In certain embodiments, the present disclosure provides a unique combination of protein and polyurethane, wherein the protein is dissolved only in the hard phase of the polyurethane. The present disclosure also provides methods for preparing the protein polyurethane alloys described herein. The present disclosure also provides materials comprising one or more protein polyurethane alloys and methods for preparing the materials. In some embodiments, the present disclosure provides layered materials comprising one or more layers in a protein polyurethane alloy layer and methods for preparing the layered materials. Protein polyurethane alloys and protein polyurethane alloy layers may contain one or more types of proteins and one or more polyurethanes.
[0073] Proteins suitable for use in the alloys disclosed herein may be unmodified or chemically modified. In some embodiments, the protein may be modified to promote miscibility of the protein with the hard phase of the polyurethane. In some embodiments, the protein may be chemically modified to promote solubility in water. In such embodiments, chemical modifications that promote solubility in water may promote miscibility of the protein with the hard phase of the polyurethane. In some embodiments, the chemically modified protein may be a partially hydrolyzed protein. In some embodiments, the chemically modified protein may be a protein modified by covalently linking a hydrophilic polymer chain (such as a polyethylene glycol (PEG) chain) to the protein.
[0074] Suitable polyurethanes for use in the protein polyurethane alloys described herein include those containing at least two phases including a "soft phase" and a "hard phase". The soft phase is formed by polyol segments within the polyurethane that are separated from the urethane-containing phase due to polarity differences. The urethane-containing phase is referred to as the hard phase. This phase separation is known in the art and is the basis of many of the properties of polyurethanes.
[0075] The soft phase is typically elastomeric at room temperature and typically has a softening point or glass transition temperature (Tg) below room temperature. Tg can be measured by dynamic mechanical analysis (DMA) and quantified by the peak value of tan (δ) or the onset of the drop in storage modulus. Alternatively, Tg can be measured by differential scanning calorimetry (DSC). In some cases, there may be crystallinity in the soft phase, which can be considered a melting point, typically between 0°C and about 60°C. For example, Fig.13 The peak in the tan(δ) curve of the UD-108 polyurethane in ATTACH ® at about 35° C. indicates the crystallinity in the soft phase of the polyurethane.
[0076] The hard phase typically has a Tg or melting point above room temperature, more typically above about 80° C. Softening of the hard phase can be measured by measuring the onset of the drop in storage modulus (sometimes referred to as stiffness) as measured by DMA.
[0077] The "soft phase" of polyurethane or protein polyurethane alloy containing polyurethane comprises the polyol component of polyurethane. Its function is to become soft and flexible at a temperature higher than its Tg, so as to give polyurethane toughness, elongation and flexibility. Typical soft segments may include polyether polyols, polyester polyols, polycarbonate polyols and mixtures thereof. Its usual molecular weight is from about 250 Daltons to a range greater than about 5 kilodaltons. The "hard phase" for polyurethane or protein polyurethane alloy containing polyurethane comprises a urethane segment of a polymer given by an isocyanate for connecting polyols and short-chain diols such as butanediol, propylene glycol, etc. Typical isocyanates suitable for polyurethane of the present invention include but are not limited to hexamethylene diisocyanate, isophorone diisocyanate, methylene diisocyanate, phenyl diisocyanate, etc. These molecules are more polar and harder than the polyols used to prepare soft segments. Therefore, compared with soft segments, hard segments are harder and have a higher softening point. The function of the hard phase is to provide properties such as strength, temperature resistance and wear resistance to polyurethane.
[0078] In some embodiments described herein, the protein may be miscible only with the hard phase, leaving the soft phase transition substantially unchanged. Without wishing to be bound by a particular theory, it is believed that when the protein is dissolved in the hard phase, it significantly increases the temperature at which the hard phase begins to soften, thereby increasing the temperature resistance of the alloys described herein. The protein-polyurethane alloys described herein may also have increased stiffness and increased strength relative to the base polyurethane (i.e., the polyurethane itself in the absence of the protein).
[0079] Protein polyurethane alloys and layers described herein can be formed by blending one or more proteins with one or more aqueous polyurethane dispersions in a liquid state and drying the blend. In some embodiments, protein polyurethane alloys and layers described herein can be formed by blending one or more proteins dissolved or dispersed in an aqueous solution with one or more aqueous polyurethane dispersions in a liquid state and drying the blend. In some embodiments, the polyurethane dispersion can be ionic and anionic or cationic. In some embodiments, the polyurethane dispersion can be nonionic. In some embodiments, the blended protein and polyurethane can be formed into sheets, and in certain embodiments, suitable attachment methods (such as direct coating, lamination methods or thermal molding methods) can be used to attach to the substrate. In certain embodiments, the lamination method may include using an adhesive layer to attach the sheet to the substrate. In some embodiments, the blended protein and polyurethane can be coated or otherwise deposited on the substrate to attach the blended protein and polyurethane to the substrate. In some embodiments, the blended protein and polyurethane are attached to the substrate and can cause a portion of the blended protein and polyurethane to be integrated into a portion of the substrate.
[0080] In a protein polyurethane alloy comprising one or more miscible proteins and polyurethanes, the one or more proteins may be dissolved in the hard phase of the one or more polyurethanes. The protein polyurethane alloy may include at least one protein that is miscible with the hard phase of one or more polyurethanes in the alloy. In some embodiments, the protein polyurethane alloy may include multiple proteins and / or multiple polyurethane hard phases that are miscible with each other. In all of these embodiments, and without wishing to be bound by a particular theory, it is believed that the protein or multiple proteins are dissolved in the hard phase of the polyurethane or multiple polyurethanes.
[0081] When blended, one or more proteins dissolved in the hard phase of one or more polyurethanes can form a homogenized mixture. In some embodiments, the protein polyurethane alloy can include multiple proteins dissolved in one or more polyurethanes, so that the protein and polyurethane form a homogenized mixture when blended and dried. Typically, the protein polyurethane alloy comprising a homogenized mixture of protein and polyurethane does not include a large amount of protein that is not dissolved in the polyurethane. That is, and in some embodiments, the protein polyurethane alloy can include a portion of the protein dispersed in the polyurethane.
[0082] In the embodiments described herein, the miscibility of the protein with the hard phase of the polyurethane can increase the DMA modulus transition softening onset temperature of the hard phase in the protein polyurethane alloy without significantly changing one or more other thermomechanical properties of the alloy relative to the thermomechanical properties of the polyurethane itself. For example, the miscibility of the protein with the hard phase of the polyurethane can increase the DMA modulus transition onset temperature of the hard phase in the protein polyurethane alloy without significantly changing the DMA transition temperature of the soft phase in the alloy relative to the DMA transition temperature of the polyurethane soft phase itself.
[0083] The DMA transition temperature of the soft phase can be referred to as the glass transition temperature (Tg) of the polyurethane or protein polyurethane alloy. The DMA transition temperature of the soft phase or Tg can be quantified as (i) the DMA storage modulus transition starting temperature of the soft phase (referred to herein as the "first DMA modulus transition starting temperature") or (ii) the DMA tan (δ) peak temperature corresponding to the soft phase. The DMA transition temperature of the hard phase can be measured by the initial decrease in the storage modulus of the polyurethane or polyurethane protein alloy, and can be quantified as the DMA modulus transition starting temperature of the hard phase (referred to herein as the "second DMA modulus transition starting temperature"). In some embodiments, the second DMA modulus transition starting temperature of the protein polyurethane alloy may be higher than about 80°C or higher than about 130°C.
[0084] Although many types of proteins are contemplated for use in the protein polyurethane alloys described herein, including, for example, collagen and soy protein, it should be understood that for all embodiments disclosed herein, the protein may be a protein other than collagen and / or a protein other than soy protein. Therefore, in some embodiments, the protein dissolved in the protein polyurethane alloy may be a protein other than collagen. In other embodiments, the protein dissolved in the protein polyurethane alloy may be a protein other than soy protein. In some embodiments, the protein dissolved in the protein polyurethane alloy may be a protein other than collagen and a protein other than soy protein. In some embodiments, the protein polyurethane alloy may be free of or substantially free of collagen. In some embodiments, the protein polyurethane alloy may be free of or substantially free of soy protein. In some embodiments, the protein polyurethane alloy may be free of or substantially free of soy protein and collagen.
[0085] As previously discussed, the soft phase and hard phase of the polyurethane can be measured using dynamic mechanical analysis (DMA). Therefore, the one or more polyurethanes contained in the protein polyurethane alloy described herein may have at least two DMA transition temperatures, one corresponding to the soft phase and one corresponding to the hard phase. The DMA transition temperature of the soft phase can be quantified as the "first DMA modulus transition start temperature" or DMA tan (δ) peak temperature corresponding to the soft phase. The DMA transition temperature of the hard phase can be quantified by the "second DMA modulus transition start temperature". The first DMA modulus transition start temperature or DMA tan (δ) peak temperature is a lower DMA transition temperature, and the second DMA modulus transition start temperature is a higher DMA transition temperature.
[0086] Similarly, the protein polyurethane alloys described herein may have at least two phases. The at least two phases may include a soft phase and a hard phase. The different phases of the alloy may be measured and quantified in the same manner as described above for polyurethane.
[0087] A polyurethane or protein polyurethane alloy having a first and a second DMA transition temperature means that it has a first DMA transition temperature that occurs at a lower temperature than a second DMA transition temperature. However, the first and second transition temperatures do not need to be sequential transition temperatures. Other DMA transition temperatures may occur between the first and second transitions.
[0088] In some embodiments, the first DMA modulus transition onset temperature of the polyurethane may be less than 30° C. In some embodiments, the first DMA modulus transition onset temperature of the polyurethane may be in the range of about -65° C. to about 30° C., including subranges. For example, in some embodiments, the first DMA modulus transition onset temperature of the polyurethane may be about -65° C., about -60° C., about -55° C., about -50° C., about -45° C., about -40° C., about -35° C., about -30° C., about -25° C., about -20° C., about -15° C., about -10° C., about -5° C., about -1° C., 0° C., about 1° C., about 5° C., about 10° C., about 15° C., about 20° C., about 25° C., or about 30° C., or in a range having any two of these values as endpoints, including the endpoints. In some embodiments, the first DMA modulus transition onset temperature of the polyurethane may be from about -65°C to about 30°C, from about -65°C to about 25°C, from about -65°C to about 20°C, from about -65°C to about 15°C, from about -65°C to about 10°C, from about -65°C to 5°C, from about -65°C to about 1°C, from about -65°C to 0°C, from about -65°C to about -1°C, from about -65°C to about -5°C, from about -65°C to about -10°C, from about -65°C to about -15°C, from about -65°C to about -20°C, from about -65°C to about -25°C, from about -65°C to about -30°C, from about -65°C to about -35°C, from about -65°C to about -35°C, from about -65°C to about -40°C, from about -65°C to about -45°C.
[0089] Figures 9 to 15 DMA thermogram curves of various exemplary polyurethanes are shown. The first DMA modulus transition onset temperature (T 起始1 ) is the temperature at which the slope of the storage modulus (E') curve begins to decrease significantly for the first time for each exemplary polyurethane. Fig.16 A method for measuring this value is illustrated in . A programmable DMA device, such as the DMA-850 from TA Instruments, can automatically calculate this temperature. Table 4 lists the Figures 9 to 15 The first DMA modulus transition onset temperature automatically calculated from the DMA graph in (see Example Nos. 1 to 7).
[0090] In some embodiments, the DMA tan (δ) peak temperature corresponding to the soft phase of the polyurethane may be below 30° C. In some embodiments, the DMA tan (δ) peak temperature corresponding to the soft phase of the polyurethane may be in the range of about -60° C. to about 30° C., including subranges. For example, in some embodiments, the DMA tan (δ) peak temperature corresponding to the soft phase of the polyurethane may be about -60° C., about -55° C., about -50° C., about -45° C., about -40° C., about -35° C., about -30° C., about -25° C., about -20° C., about -15° C., about -10° C., about -5° C., about -1° C., 0° C., about 1° C., about 5° C., about 10° C., about 15° C., about 20° C., about 25° C., or about 30° C., or in a range having any two of these values as endpoints, including the endpoints. In some embodiments, the DMA tan (δ) peak temperature corresponding to the soft phase of the polyurethane may be from about -60°C to about 30°C, from about -60°C to about 25°C, from about -60°C to about 20°C, from about -60°C to about 15°C, from about -60°C to about 10°C, from about -60°C to about 5°C, from about -60°C to about 1°C, from about -60°C to 0°C, from about -60°C to about -1°C, from about -60°C to about -5°C, from about -60°C to about -10°C, from about -60°C to about -15°C, from about -60°C to about -20°C, from about -60°C to about -25°C, from about -60°C to about -30°C, from about -60°C to about -35°C, or from about -60°C to about -40°C.
[0091] Figures 9 to 15 The DMA thermograms in FIG. 4 show the DMA tan(δ) peak temperatures corresponding to the soft phase of various exemplary polyurethanes. Similar to the DMA modulus transition onset temperature, a programmable DMA instrument, such as the DMA-850 from TA Instruments, can automatically calculate this temperature. Table 4 lists the peak temperatures of the DMA modulus transition onset temperatures from FIG. Figures 9 to 15 DMA tan(δ) peak temperature automatically calculated from the DMA graph in (see Example Nos. 1 to 7).
[0092] In some embodiments, the second DMA modulus transition onset temperature of the polyurethane may be higher than 30° C. In some embodiments, the second DMA modulus transition onset temperature of the polyurethane may be in the range of about 45° C. to about 165° C. For example, in some embodiments, the second DMA modulus transition onset temperature of the polyurethane may be about 45° C., about 50° C., about 55° C., about 60° C., about 65° C., about 70° C., about 75° C., about 80° C., about 85° C., about 90° C., about 95° C., about 100° C., about 105° C., about 110° C., about 115° C., about 120° C., about 125° C., about 130° C., about 135° C., about 140° C., about 145° C., about 150° C., about 155° C., about 160° C., or about 165° C., or in any range having any two of these values as endpoints, including the endpoints. In some embodiments, the second DMA modulus transition onset temperature of the polyurethane may be from about 45°C to about 165°C, from about 50°C to about 160°C, from about 55°C to about 155°C, from about 60°C to about 150°C, from about 65°C to about 145°C, from about 70°C to about 140°C, from about 75°C to about 135°C, from about 80°C to about 130°C, from about 85°C to about 125°C, from about 90°C to about 120°C, from about 95°C to about 115°C, or from about 100°C to about 110°C.
[0093] Figures 9 to 15 The DMA thermogram curves in FIG. 2 show the second DMA modulus transition onset temperature of various exemplary polyurethanes. The second DMA modulus transition onset temperature (T 起始2 ) is the temperature at which the slope of the storage modulus (E') curve begins to decrease significantly at the second time for each exemplary polyurethane. Fig.16 A method for measuring this value is illustrated in . A programmable DMA device, such as the DMA-850 from TA Instruments, can automatically calculate this temperature. Table 3 lists the Figures 9 to 15 The second DMA modulus transition onset temperature automatically calculated from the DMA graph in (see Example Nos. 1 to 7).
[0094] In some embodiments, the polyurethane may exhibit crystallinity in the soft phase. This is common in polyether soft segments containing polytetramethylene glycol and some polyester polyols. In such embodiments, the polyurethane may exhibit at least three transitions: the Tg of the soft phase, the melting point of the soft phase, and the modulus transition of the hard phase. This melting in the soft phase, when present, typically occurs between 0°C and about 60°C. In embodiments where crystallinity is exhibited in the soft phase, the protein polyurethane alloy typically still exhibits melting in the soft phase because the protein is miscible with the hard phase, leaving the mechanical properties of the soft phase essentially unchanged.
[0095] In typical embodiments described herein, the protein polyurethane alloy may have a second DMA modulus transition start temperature that is higher than the second DMA modulus transition temperature of the polyurethane in the absence of protein (i.e., the polyurethane itself). It is believed that this increase in the second DMA modulus transition start temperature in the alloy is due to the miscibility of the hard phase of the protein and the polyurethane. This selective miscibility of the protein is indicated by an increase in the second DMA modulus transition start temperature, while the DMA transition temperature of the soft phase does not have a similar increase (quantified by the first DMA modulus transition start temperature or DMA tan (δ) peak temperature corresponding to the soft phase). This selective miscibility can be used to control the properties of the protein polyurethane alloy, such as mechanical and thermal properties.
[0096] In some embodiments, the protein polyurethane alloys and / or materials described herein may have a look and feel and mechanical properties similar to natural leather. For example, the protein polyurethane alloy or a material including the protein polyurethane alloy may have tactile properties, aesthetic properties, mechanical / performance properties, manufacturable properties, and / or thermal properties similar to natural leather. Mechanical / performance properties similar to natural leather include, but are not limited to, tensile strength, tear strength, elongation at break, wear resistance, internal cohesion, water resistance, breathability (quantified by moisture vapor transmission rate measurement in some embodiments), and the ability to dye with reactive dyes and maintain color during friction (color fastness). Tactile properties similar to natural leather include, but are not limited to, softness, stiffness, coefficient of friction, and compression modulus. Aesthetic properties similar to natural leather include, but are not limited to, dyeability, embossability, aging, color, color depth, and color pattern. Manufacturing properties similar to natural leather include, but are not limited to, the ability to be stitched, cut, ground, and split. Thermal properties similar to natural leather include, but are not limited to, heat resistance and resistance to hardening or softening in a significantly wide temperature range (e.g., 25°C to 100°C).
[0097] The desired properties of the protein polyurethane alloys described herein include, but are not limited to, optical properties, tactile properties, aesthetic properties, thermal properties, mechanical properties, and / or breathability properties. Exemplary thermal properties include heat resistance and resistance to melting, and can be measured, for example, by measuring the second modulus transition onset temperature (T 起始2 ) quantified. Exemplary mechanical properties include abrasion resistance, maximum tensile stress (also referred to as "tensile strength"), and Young's modulus. Unless otherwise specified, the maximum tensile stress values and Young's modulus values disclosed herein are measured according to the method provided by ASTM D638. Exemplary air permeability properties include g / m 2 The moisture vapor transmission rate (MVTR) is measured in grams per square meter per 24 hours. Unless otherwise specified, the moisture vapor transmission rate disclosed herein is measured according to the method provided in ASTM E96—Method B.
[0098] In some embodiments, the protein polyurethane alloy may be transparent. In some embodiments, a transparent protein polyurethane alloy may indicate that the protein is miscible with the hard phase of the polyurethane in the alloy. As used herein, a "transparent" material refers to a material with an opacity of about 50% or less. Opacity is measured as follows: a sample of the material is placed on a white background to measure the Y tristimulus value ("compared to white Y") in reflectivity using a D65 10 degree illuminant with a spectrometer. The same sample is then placed on a black background, and the measurement is repeated to obtain "compared to black Y". The opacity percentage is calculated as "compared to black Y" divided by "compared to white Y" multiplied by 100.
[0099] 100% opacity is defined as the lowest transparency, and 0% opacity is defined as the highest transparency.
[0100] In some embodiments, the protein polyurethane alloy can be transparent and the opacity can be in the range of 0% to about 50%, including subranges. For example, the opacity of the transparent protein polyurethane alloy can be in the range of 0% to about 40%, 0% to about 30%, 0% to about 20%, 0% to about 10%, or 0% to about 5%. The transparency of the protein polyurethane alloy is evaluated before dyeing or otherwise coloring the protein polyurethane alloy.
[0101] Transparent protein polyurethane alloys can be produced by selecting and blending appropriate combinations of one or more proteins and one or more polyurethanes. Although not all combinations of proteins and polyurethanes will produce a transparent protein polyurethane alloy layer, it is within the skill of the ordinary technician to determine whether a given blend produces a transparent protein polyurethane alloy layer in accordance with the present disclosure. In embodiments involving materials including the transparent protein polyurethane alloys described herein, the transparent protein polyurethane alloys can provide unique properties to the material. For example, compared to opaque protein polyurethane alloys, transparent protein polyurethane alloys can provide unique color depth when dyed. Similarly, transparent protein polyurethane alloys can provide the material with its mechanical properties without significantly affecting the aesthetic properties of the material.
[0102] In some embodiments, the protein polyurethane alloy may include one or more colorants. In some embodiments, the colorant may be a dye, such as a fiber reactive dye, a direct dye, an acid dye, or a natural dye. Exemplary dyes include, but are not limited to, azo acid dyes, metal complex structure acid dyes, anthraquinone structure acid dyes, azo / diazo direct dyes, sulfur dyes, and vat dyes. In some embodiments, the colorant may be a pigment, such as a lake pigment.
[0103] Suitable polyurethanes for blending with one or more proteins according to the embodiments described herein include, but are not limited to, aliphatic polyurethanes, aromatic polyurethanes, bio-based polyurethanes, or acrylic modified polyurethanes. Suitable polyurethanes are commercially available from manufacturers including Lubrizol, Hauthaway, Stahl, etc. In some embodiments, the polyurethane used for protein polyurethane alloys may be bio-polyurethanes. In some embodiments, the polyurethane is a water-dispersible polyurethane. In some embodiments, the polyurethane may be a polyester polyurethane. In some embodiments, the polyurethane may be a polyether polyurethane. In some embodiments, the polyurethane may be a polycarbonate-based polyurethane. In some embodiments, the polyurethane may be an aliphatic polyester polyurethane. In some embodiments, the polyurethane may be an aliphatic polyether polyurethane. In some embodiments, the polyurethane may be an aliphatic polycarbonate polyurethane. In some embodiments, the polyurethane may be an aromatic polyester polyurethane. In some embodiments, the polyurethane may be an aromatic polyether polyurethane. In some embodiments, the polyurethane may be an aromatic polycarbonate polyurethane.
[0104] In some embodiments, polyurethane may have a soft segment selected from the group consisting of: polyether polyols, polyester polyols, polycarbonate polyols and mixtures thereof. In some embodiments, polyurethane may have a hard segment comprising a diisocyanate and an optional short-chain diol. Suitable diisocyanates may be selected from the group consisting of: aliphatic diisocyanates, such as hexamethylene diisocyanate, isophorone diisocyanate; aromatic diisocyanates, such as 4,4' diphenylmethylene diisocyanate, toluene diisocyanate, phenyl diisocyanate and mixtures thereof. Suitable short-chain diols include ethylene glycol, propylene glycol, butanediol, 2,2 methyl 1,3 propanediol, pentanediol, hexanediol and mixtures thereof. In some embodiments, crosslinking agents such as polyfunctional alcohols, for example trimethylolpropane triol or diamines, such as ethylenediamine or 4,4' diaminodiphenyl diamine.
[0105] Exemplary commercial polyurethanes include, but are not limited to, L3360 and Hauthane HD-2001 from CL Hauthaway & Sons Corporation, SANCURE TM Polyurethane, BONDTHANE from Bond Polymers International TM Polyurethanes such as UD-108, UD-250 and UD-303, and UD-60 available from BASF ECO 3702 and P100 ECO. L3360 is an aliphatic polyester polyurethane polymer aqueous dispersion having a solid content of 35%, a viscosity of 50 cps (centipoise) to 500 cps, and a density of about 8.5 lb / gal (pounds per gallon). HD-2001 is an aliphatic polyester polyurethane polymer aqueous dispersion having a solid content of 40%, a viscosity of 50 cps to 500 cps, and a density of about 8.9 lb / gal. BONDTHANE TM UD-108 is an aqueous dispersion of an aliphatic polyether polyurethane polymer having a solids content of 33%, a viscosity of 300 cps, and a density of 8.7 lb / gal. TM UD-250 is an aqueous dispersion of an aliphatic polyester polyurethane polymer having a solids content of 35%, a viscosity of 200 cps, and a density of 8.8 lb / gal. BONDTHANE TM UD-303 is an aqueous dispersion of an aliphatic polyether polyurethane polymer having a solids content of 35%, a viscosity of less than 500 cps, and a density of 8.7 lb / gal. P100 ECO is an aqueous dispersion of a polyester polyurethane elastomer having approximately 40% solids and a viscosity of about 40 mPas.
[0106] Additional exemplary polyurethanes include, but are not limited to: (i) an aqueous aliphatic polyether-based polyurethane dispersion having a solid content of 35%, a specific gravity of 1.02 g / mL, and a Brookfield viscosity of 160 mPa.s, (ii) a nonionic aliphatic polycarbonate-polyether polyurethane dispersion having a solid content of 30%, a specific gravity of 1.1 g / mL, and a viscosity of <1000 mPa.s, and (iii) an aqueous aliphatic polyether-based polyurethane dispersion having a solid content of 35%, a specific gravity of 1.04 g / mL, and a Brookfield viscosity of 30 mPa.s at 25°C.
[0107] Exemplary bio-based polyurethanes include, but are not limited to, L3360 available from CL Hauthaway & Sons Corporation, Eco DLS, Eco DL 519, Eco DLP-R and DL-5249. Eco DLS is an anionic aliphatic polyester polyurethane polymer aqueous dispersion having a solids content of approximately 50%, a viscosity of less than 1,200 MPa·s, and a density of about 1.1 g / cc. Eco DL 519 is an anionic, aliphatic polyester polyurethane polymer aqueous dispersion. Eco DLP-R is an anionic, aliphatic polyester polyurethane polymer aqueous dispersion. DL 5249 is an anionic, aliphatic polyester polyurethane polymer aqueous dispersion.
[0108] In some embodiments, the polyurethane may include reactive groups that can crosslink with proteins. Exemplary reactive groups include, but are not limited to, sulfonates, aldehydes, carboxylic acids or esters, blocked isocyanates, and the like, and combinations thereof. In such embodiments, the polyurethane can be crosslinked with proteins in a protein-polyurethane alloy by reacting reactive groups on the protein with reactive groups present in the polyurethane.
[0109] Suitable proteins for blending with one or more polyurethanes according to the embodiments described herein include, but are not limited to, collagen, gelatin, bovine serum albumin (BSA), soy protein, pea protein, egg white albumin, casein, peanut protein, hemp globulin, whey protein, karanja protein, and cellulase. Suitable collagens include, but are not limited to, recombinant collagen (r-collagen), recombinant collagen fragments, and extracted collagen. Suitable soy proteins include, but are not limited to, soy protein isolate (SPI), soybean meal protein, and soy protein derivatives. In some embodiments, soy protein isolate may be partially hydrolyzed soy protein isolate. Suitable pea proteins include, but are not limited to, pea protein isolate and pea protein derivatives. In some embodiments, pea protein isolate may be partially hydrolyzed pea protein isolate.
[0110] Table 1 below lists some exemplary proteins and properties of proteins. Gelatin is gelatin from pig skin, type A (Sigma Aldrich G2500). Collagen is extracted bovine collagen purchased from Wuxi BIOT Biology-technology Company. Bovine serum albumin Sigma Aldrich 5470 bovine serum albumin. R-collagen is recombinant collagen from Modern Meadow. Soy protein isolate is soy protein isolate purchased from MP Medicals (IC90545625). Pea protein is pea protein powder purchased from Bobs Red Mills (MTX5232). Egg white albumin is albumin from chicken egg white (Sigma Aldrich A5253). Casein is casein from milk (Sigma Aldrich C7078). Peanut protein is peanut protein powder purchased from Tru-Nut. Whey protein is whey from milk (Sigma Aldrich W1500). Other suitable soy protein isolates include, but are not limited to, soy protein isolates available from AMD (Clarisoy 100, 110, 150, 170, 180) or DuPont ( XT 55, XT 221D and Other suitable pea protein powders include, but are not limited to, pea protein powders available from Puris (870 and 870H).
[0111] Karanja protein is a protein found in Karanja seeds harvested from the Pongamia pinnata tree (also known as the Pongamia glabra tree). See Rahman, M M. and Netravali, "Green Resin from Forestry Waste Residue'Karanja (Pongamia pinnata) Seed Cake' for Biobased Composite Structures", ACS Sustainable Chem. Eng., 2: 2318-2328 (2014); see also Mandal et al., "Nutritional Evaluation of Proteins from three Non-traditional Seeds with or without Amino Acids Supplementation in Albino Rats," Proc. Indiannatn. Sci. Acad., B50, No. 1, 48-56 (1984). The protein can be extracted from Karanja seeds using a solvent extraction method. Same as above. In some embodiments, the Karanja protein can be a Karanja isolated protein. In such embodiments, Karanja protein isolate can be obtained by alkaline extraction and acid precipitation of defatted Karanja seed cake. See Rahman, MM. and Netravali, "Green Resin from Forestry Waste Residue'Karanja (Pongamiapinnata) Seed Cake'for Biobased Composite Structures", ACS Sustainable Chem. Eng., 2:2318-2328 (2014).
[0112] Suitable cellulase proteins are listed in Table 1 below. "Cellulase-RG" protein was purchased from CREATIVE The "Cellulase-IG" protein is a laboratory grade cellulase purchased from Carolina BiologicalSupply Company.
[0113] The 50 KDa recombinant collagen fragment (50 KDa r-collagen fragment) in Table 1 is a collagen fragment having the amino acid sequence listed as SEQ ID NO:2.
[0114] The "Dissolution Methods" listed in Table 1 are exemplary aqueous solvents in which proteins can be dissolved in solutions that are miscible with the hard phase of the polyurethane as described herein. Proteins that are at least partially soluble in aqueous solutions are suitable for forming protein-polyurethane alloys with polyurethane dispersions.
[0115] Table 1: Example proteins
[0116]
[0117]
[0118] In some embodiments, the protein may have one or more of the following properties: (i) a molecular weight within the ranges described herein, (ii) an isoelectric point within the ranges described below, (iii) an amino acid composition measured as grams of lysine per 100 grams of protein within the ranges described below, and (iv) protein thermal stability up to 200°C.
[0119] Protein molecular weight
[0120] In some embodiments, the molecular weight of the protein can range from about 1 KDa (kilodaltons) to about 700 KDa, including subranges. For example, the molecular weight of the protein can be in the range of about 1 KDa to about 700 KDa, about 10 KDa to about 700 KDa, about 20 KDa to about 700 KDa, about 50 KDa to about 700 KDa, about 100 KDa to about 700 KDa, about 200 KDa to about 700 KDa, about 300 KDa to about 700 KDa, about 400 KDa to about 700 KDa, about 500 KDa to about 700 KDa, about 600 KDa to about 700 KDa, about 1 KDa to about 600 KDa, about 1 KDa to about 500 KDa, about 1 KDa to about 400 KDa, about 1 KDa to about 300 KDa, about 1 KDa to about 200 KDa, about 1 KDa to about 100 KDa, about 1 KDa to about 50 KDa, about 1 KDa to about 20 KDa, or about 1 KDa to about 10 KDa, or in any range having any two of these values as endpoints, inclusive.
[0121] Protein isoelectric point
[0122] In some embodiments, the isoelectric point of the protein may be in the range of about 4 to about 10, including subranges. For example, the isoelectric point of the protein may be in the range of about 4 to about 10, about 4.5 to about 9.5, about 5 to about 9, about 5.5 to about 8.5, about 6 to about 8, about 6.5 to about 7.5, or about 6.5 to about 7, or in a range having any two of these values as endpoints, inclusive. In some embodiments, the isoelectric point of the protein may be in the range of about 4 to about 5.
[0123] Protein amino acid composition
[0124] In some embodiments, the protein may have an amino acid composition (referred to as "lysine weight percent") ranging from about 0.5% by weight to about 100% by weight (including sub-ranges) measured in grams of lysine per 100 grams of protein. For example, the lysine weight percent of the protein may be in the range of about 0.5% by weight to about 100% by weight, about 1% by weight to about 100% by weight, about 5% by weight to about 100% by weight, about 10% by weight to about 100% by weight, about 20% by weight to about 100% by weight, about 30% by weight to about 100% by weight, about 40% by weight to about 100% by weight, about 50% by weight to about 100% by weight, about 60% by weight to about 100% by weight, about 70% by weight to about 100% by weight, about 80% by weight to about 100% by weight, or about 90% by weight to about 100% by weight, or in the range of having any two of these values as endpoints, including the endpoints. In some embodiments, the protein may be polylysine.
[0125] In some embodiments, the lysine weight percentage of protein can be in the range of about 0.5 weight % to about 20 weight %, including sub-ranges. For example, the lysine weight percentage of protein can be in the range of about 0.5 weight % to about 20 weight %, about 1 weight % to about 19 weight %, about 2 weight % to about 18 weight %, about 3 weight % to about 17 weight %, about 4 weight % to about 16 weight %, about 5 weight % to about 15 weight %, about 6 weight % to about 14 weight %, about 7 weight % to about 13 weight %, about 8 weight % to about 12 weight %, about 9 weight % to about 11 weight % or about 9 weight % to about 10 weight %, or in the range of any two of these values as endpoints, including endpoints. In some embodiments, the lysine weight percentage of protein can be in the range of about 1 weight % to about 20 weight %. In some embodiments, the lysine weight percentage of protein can be in the range of about 5 weight % to about 20 weight %. In some embodiments, the lysine weight percentage of protein can be in the range of about 1 weight % to about 12 weight %. In some embodiments, the protein's lysine weight percent may be in the range of about 5 weight percent to about 12 weight percent. In some embodiments, the protein's lysine weight percent may be in the range of about 1 weight percent to about 15 weight percent. In some embodiments, the protein's lysine weight percent may be in the range of about 5 weight percent to about 15 weight percent.
[0126] In some embodiments, protein may be heat-stable. In some embodiments, protein may be non-heat-stable. As described herein, protein thermal stability is determined by differential scanning calorimetry (DSC), wherein pre-dried protein powder (wherein moisture is less than 3%) is scanned from 0°C to 200°C. In the DSC curve of protein, the endothermic peak greater than 10mW / mg is determined as "denaturation peak", and the temperature corresponding to the endothermic "denaturation peak" is defined as the "denaturation temperature" of protein. "Heat-stable" protein means that the protein has a denaturation temperature of 200°C or higher. For the purposes of this disclosure, proteins with a denaturation temperature lower than 200°C are considered to be "non-heat-stable". For example, it is found that the whey from milk listed in Table 1 has a denaturation temperature at 158°C according to DSC, and therefore whey is considered to be non-heat-stable.
[0127] Protein solubilization
[0128] In some embodiments, before being blended with one or more polyurethanes, one or more proteins can be dissolved in an aqueous solution to form an aqueous protein mixture. In some embodiments, dissolving the protein in an aqueous solution before blending the protein with one or more polyurethanes can promote the miscibility of the hard phase of the protein with the one or more polyurethanes. For example, dissolving the protein in an aqueous solution before blending the protein with one or more polyurethanes can promote the miscibility of the hard phase of the protein with the polyurethane. Not all proteins are naturally miscible with any phase of polyurethane. For example, and as illustrated in Examples 33 and 34, casein is not necessarily miscible with polyurethane. As shown in these two embodiments, if casein, water and L3360 are mixed, casein is not miscible with L3360. The film obtained has an opaque appearance, and there are many optically visible particles in the film. However, if casein is dissolved in a sodium hydroxide solution before mixing with L3360, casein is miscible with the hard phase of L3360. The film obtained by blending these components has a transparent and uniform appearance, and there are no optically visible particles in the film.
[0129] Suitable aqueous solutions include, but are not limited to, water, alkaline aqueous solutions, acid aqueous solutions, aqueous solutions including organic solvents, urea solutions, and mixtures thereof. In some embodiments, the alkaline aqueous solution may be an alkaline solution, such as sodium hydroxide, ammonia, or ammonium hydroxide solution. In some embodiments, examples of acid aqueous solutions may be acetic acid or hydrochloric acid (HCl) solutions. Suitable organic solvents include, but are not limited to, ethanol, isopropanol, acetone, ethyl acetate, isopropyl acetate, glycerol, and the like. In some embodiments, the protein concentration in the aqueous protein mixture may be in the range of about 10 g / L to about 300 g / L, including subranges. For example, the protein concentration in the aqueous protein mixture can be about 10 g / L, about 20 g / L, about 30 g / L, about 40 g / L, about 50 g / L, about 60 g / L, about 70 g / L, about 80 g / L, about 90 g / L, about 100 g / L, about 150 g / L, about 200 g / L, about 250 g / L, or about 300 g / L, or in a range having any two of these values as endpoints, including the endpoints. In some embodiments, the protein concentration in the aqueous protein mixture can be in the range of about 10 g / L to about 300 g / L, about 20 g / L to about 250 g / L, about 30 g / L to about 200 g / L, about 40 g / L to about 150 g / L, about 50 g / L to about 100 g / L, about 60 g / L to about 90 g / L, or about 70 g / L to about 80 g / L.
[0130] In some embodiments, the protein can be pretreated and / or purified to improve solubility in water. Suitable pretreatments include, but are not limited to, acid treatment, alkaline treatment, enzymatic hydrolysis, and salt treatment. Exemplary acid treatments are acid hydrolysis with suitable acids such as acetic acid or HCl. Exemplary alkaline treatments are alkaline hydrolysis with suitable alkalis (such as ammonium hydroxide, NaOH, KOH, or mixtures thereof). Exemplary enzymes for hydrolysis include, but are not limited to, papain, bromelain, trypsin, alkaline protease, and the like. Suitable purification treatments include, but are not limited to, removal of phytic acid with calcium salts, diafiltration, ultrafiltration, centrifugation, and the like.
[0131] In some embodiments, adding lysine or other hydrophilic amino acids to the protein prior to blending with the one or more polyurethanes can promote miscibility of the protein with the hard phase of the one or more polyurethanes.
[0132] Protein hydrolysis
[0133] In some embodiments, the protein may be partially hydrolyzed. The partial hydrolysis of the protein may promote the dissolution of the protein in water and / or promote the miscibility of the protein with the hard phase of the polyurethane. The partial hydrolysis of the protein may be completed using an enzyme or a strong to moderate base. The viscosity may be reduced and / or the protein molecular weight may be reduced after the hydrolysis. Characterization methods for determining the reduction in protein molecular weight and thus the level of protein hydrolysis include, but are not limited to, light scattering, gel electrophoresis, size exclusion chromatography, solution viscosity measurements, detection of the terminal amino groups with trinitrobenzene sulfonic acid or ninhydrin, or particle size measurements with laser diffraction. Example 21 describes partially hydrolyzed soy protein prepared using sodium hydroxide according to some embodiments.
[0134] PEGylation of proteins
[0135] In some embodiments, the protein can be chemically modified by covalently attaching PEG (PEG) to the protein. PEG modification of the protein can promote the dissolution of the protein in water and / or promote the miscibility of the protein with the hard phase of the polyurethane. PEG modification of the protein can be accomplished using a method in which a hydrophilic polyethylene glycol (PEG) chain is covalently attached to the protein.
[0136] In some embodiments, the amount of protein in the protein polyurethane alloy can be in the range of about 10% to about 50% by weight protein, including subranges. For example, in some embodiments, the amount of protein in the protein polyurethane alloy is in the range of about 10% to about 50% by weight, about 15% to about 50% by weight, about 20% to about 50% by weight, about 25% to about 50% by weight, about 30% to about 50% by weight, about 35% to about 50% by weight, about 40% to about 50% by weight, about 45% to about 50% by weight, about 10% to about 45% by weight, about 10% to about 40% by weight, about 10% to about 35% by weight, about 10% to about 30% by weight, about 10% to about 25% by weight, about 10% to about 20% by weight, or about 10% to about 15% by weight, or in a range having any two of these values as endpoints, including the endpoints. In some embodiments, the amount of protein in the protein polyurethane alloy may range from about 20 wt % to about 35 wt %.
[0137] In some embodiments, the amount of protein in the protein polyurethane alloy may be greater than 50% by weight. In some embodiments, the amount of protein in the protein polyurethane alloy may be in the range of about 50% by weight to about 90% by weight protein, including sub-ranges. For example, in some embodiments, the amount of polyurethane in the protein polyurethane alloy may be in the range of about 50% by weight to about 90% by weight, about 55% by weight to about 90% by weight, about 60% by weight to about 90% by weight, about 65% by weight to about 90% by weight, about 70% by weight to about 90% by weight, about 75% by weight to about 90% by weight, about 80% by weight to about 90% by weight, about 85% by weight to about 90% by weight, about 50% by weight to about 85% by weight, about 50% by weight to about 80% by weight, about 50% by weight to about 75% by weight, about 50% by weight to about 70% by weight, about 60% by weight to about 85% by weight, about 60% by weight to about 80% by weight, or about 70% by weight to about 90% by weight, or in the range of any two of these values as endpoints, including endpoints.
[0138] In some embodiments, the amount of polyurethane in the protein polyurethane alloy can be in the range of about 50% to about 90% by weight, including subranges. For example, in some embodiments, the amount of polyurethane in the protein polyurethane alloy can be in the range of about 50% to about 90% by weight, about 55% to about 90% by weight, about 60% to about 90% by weight, about 65% to about 90% by weight, about 70% to about 90% by weight, about 75% to about 90% by weight, about 80% to about 90% by weight, about 85% to about 90% by weight, about 50% to about 85% by weight, about 50% to about 80% by weight, about 50% to about 75% by weight, about 50% to about 70% by weight, about 50% to about 65% by weight, about 50% to about 60% by weight, or about 50% to about 55% by weight, or in a range having any two of these values as endpoints, including the endpoints. In some embodiments, the amount of polyurethane in the protein polyurethane alloy may range from about 65 wt % to about 80 wt %.
[0139] In some embodiments, the amount of polyurethane in the protein polyurethane alloy may be less than 50 weight %. In some embodiments, the amount of polyurethane in the protein polyurethane alloy may be in the range of about 10 weight % to about 50 weight %, including sub-ranges. For example, in some embodiments, the amount of polyurethane in the protein polyurethane alloy may be in the range of about 10 weight % to about 50 weight %, about 15 weight % to about 50 weight %, about 20 weight % to about 50 weight %, about 25 weight % to about 50 weight %, about 10 weight % to about 45 weight %, about 10 weight % to about 40 weight %, about 10 weight % to about 35 weight %, about 10 weight % to about 30 weight %, about 10 weight % to about 25 weight %, about 10 weight % to about 20 weight %, about 15 weight % to about 40 weight %, about 20 weight % to about 40 weight % or about 10 weight % to about 30 weight %, or in the range of having any two of these values as endpoints, including endpoints.
[0140] In some embodiments, the weight percentage values and ranges listed above may be based on the total weight of the protein polyurethane alloy or protein polyurethane alloy layer. In some embodiments, the weight percentage values and ranges listed above may be based on the total weight of only protein and polyurethane in the protein polyurethane alloy or protein polyurethane alloy layer. Unless otherwise stated, the weight percentage values or ranges of polyurethane and protein are based on the total weight of only protein and polyurethane in the protein polyurethane alloy or protein polyurethane alloy layer.
[0141] In some embodiments, the sum of the amount of protein plus the amount of polyurethane in the protein polyurethane alloy may be about 80 wt % or more. For example, in some embodiments, the sum of the amount of protein plus the amount of polyurethane in the protein polyurethane alloy may be in the range of about 80 wt % to 100 wt %, about 82 wt % to 100 wt %, about 84 wt % to 100 wt %, about 86 wt % to 100 wt %, about 88 wt % to 100 wt %, about 90 wt % to 100 wt %, about 92 wt % to 100 wt %, about 94 wt % to 100 wt %, about 96 wt % to 100 wt %, or about 98 wt % to 100 wt %.
[0142] In some embodiments, protein polyurethane alloys may include water that is a part of the total weight percentage of the material. In some embodiments, the amount of water in the protein polyurethane alloy may be in the range of about 1 wt % to about 10 wt %, including sub-ranges. For example, in some embodiments, the amount of water in the protein polyurethane alloy may be in the range of about 1 wt % to about 10 wt %, about 2 wt % to about 10 wt %, about 3 wt % to about 10 wt %, about 4 wt % to about 10 wt %, about 5 wt % to about 10 wt %, about 6 wt % to about 10 wt %, about 7 wt % to about 10 wt %, about 8 wt % to about 10 wt %, about 1 wt % to about 9 wt %, about 1 wt % to about 8 wt %, about 1 wt % to about 7 wt %, about 1 wt % to about 6 wt %, about 1 wt % to about 5 wt %, about 1 wt % to about 4 wt % or about 1 wt % to about 3 wt %, or in the range of having any two of these values as endpoints, including endpoints.
[0143] The protein polyurethane alloys described herein may have one or more of the following: (i) a second dynamic mechanical analysis (DMA) modulus transition onset temperature greater than the second DMA modulus transition onset temperature of the non-alloy polyurethane; (ii) a first dynamic mechanical analysis (DMA) modulus transition onset temperature substantially the same as the first DMA modulus transition onset temperature of the non-alloy polyurethane, (iii) a DMA tan (δ) peak at a temperature substantially the same as the temperature of the DMA tan (δ) peak corresponding to the softness of the non-alloy polyurethane; (iv) a Young's modulus greater than the Young's modulus of the non-alloy polyurethane, (v) a tensile strength greater than the tensile strength of the non-alloy polyurethane, or (vi) a moisture vapor transmission rate (MVTR) greater than the MVTR of the non-alloy polyurethane.
[0144] Figures 1 to 15The effect of dissolving different amounts of different proteins in different polyurethanes to form polyurethane alloys according to some embodiments is shown. Tables 3 to 6 list the thermal and mechanical properties of various protein polyurethane alloys according to some embodiments, as well as the thermal and mechanical properties of various polyurethanes. The test samples were prepared by blending the listed proteins with the aqueous dispersions of the listed polyurethanes, casting the mixture into a flat film, drying overnight (16 hours to 24 hours) in an oven at 45°C, and conditioning for 24 hours in a standard reference atmosphere (23°C, 50% humidity) before testing. The weight percentage values in the accompanying drawings and Tables 3 to 6 are the relative weight percentages of solids added to the blends used to produce the samples. For example, 0.825 grams of gelatin and 5.5g of L3360 (35% by weight of solids) were mixed to produce a sample of Example No. 9 having 30% by weight of gelatin and 70% by weight of L3360. Based on the total weight of the dried sample, the weight percentages in the accompanying drawings and Tables 3 to 6 can be very close to the weight percentages of proteins and polyurethanes in the dried samples of Example Nos. 1 to 44. The dried sample includes water as a small portion (eg, about 5 wt % to about 10 wt %) of the total weight percentage of the sample.
[0145] Table 7 lists the moisture vapor transmission rates of various protein polyurethane alloys according to some embodiments. Test samples were prepared as described in Example Nos. 45 to 56. The weight percentage values in Table 7 are the relative weight percentages of solids added to the blends used to produce the samples. Based on the total weight of the dried samples, these weight percentages can be very close to the weight percentages of protein and polyurethane in the dried samples of Example Nos. 45 to 56. The dried samples include a small portion (e.g., about 5 weight % to about 10 weight %) of water that constitutes the total weight percentage of the sample.
[0146] The DMA temperatures in Tables 3 and 4 were measured using a DMA-850 from TA Instruments. For testing, a 1 cm × 2.5 cm strip was cut from the sample film using a metal die. The cut film sample was loaded into a film and fiber tension fixture for testing. During the test, a preload of 0.01 Newton (N) was applied to the cut film sample. The instrument was cooled to -80 ° C, held for 1 minute, and then the temperature was raised to 200 ° C at 4 ° C / min, or until the sample was too weak to maintain tension. During the temperature ramp, the sample oscillated 0.1% strain at a frequency of 1 Hz. For each test, the resulting storage modulus, loss modulus, and tan (δ) values were plotted against temperature. Unless otherwise stated, all DMA test data reported herein were measured using this test method. The tensile strength values and Young's modulus values in Tables 5 and 6 were measured according to the method provided by ASTM D638. The tensile strength values and Young's modulus values are the average values of at least three test sample specimens.
[0147] Figure 1 The DMA graph shown in shows the storage modulus (E') measured by 100% L3360 (Example No. 1) and gelatin (Example Nos. 9 and 25 to 28) dissolved in L3360 at various weight percentages (i.e., 5 wt%, 10 wt%, 15 wt%, 20 wt%, and 30 wt%). The figure shows that gelatin and L3360 blends can produce alloys with a second DMA modulus transition start temperature greater than 100% of the second DMA modulus transition start temperature of L3360. Without wishing to be bound by a particular theory, it is believed that as the hard phase comprising gelatin and the hard segments of the polyurethane become continuous at higher gelatin contents, the increase in the second DMA modulus transition start temperature in this test becomes more pronounced. This trend indicates that gelatin is miscible with the hard phase of L3360.
[0148] This miscibility of gelatin and hard phase L3360 is Figure 2 and Figure 3 This is further illustrated in the mechanical properties diagram of , which compares two different mechanical properties of Example No. 1 and Example Nos. 9 and 25 to 28. Figure 2 As shown, the maximum tensile stress ("tensile strength") of the tested protein polyurethane alloys is greater than the maximum tensile stress of L3360 at 100%. This increase in maximum tensile stress is particularly significant at 10 wt% or higher gelatin weight percentages. Figure 3 As shown, the Young's modulus of the tested protein polyurethane alloys is greater than 100% of the Young's modulus of L3360. This increase in Young's modulus is particularly significant at a gelatin weight percentage of 15 wt% or greater.
[0149] Figure 4 The DMA graph shown in shows the measured storage modulus (E') of 100% L3360 (Example No. 1) and SPI (Example Nos. 21, 30 and 31) dissolved in L3360 at various weight percentages (i.e., 10 wt%, 20 wt% and 30 wt%). The thermogram shows that blending SPI with L3360 can produce a protein polyurethane alloy having a second DMA modulus transition onset temperature greater than 100% of the second DMA modulus transition onset temperature of L3360. As more SPI is added, the increase in the second DMA modulus transition onset temperature increases. This trend indicates that SPI is miscible with the hard phase of L3360.
[0150] This miscibility of SPI and hard phase L3360 is Figure 5 and Figure 6 This is further illustrated in the mechanical properties diagram of , which compares two different mechanical properties of Example No. 1 and Example Nos. 21, 30 and 31. Figure 5As shown, the maximum tensile stress ("tensile strength") of the tested protein polyurethane alloys is greater than the maximum tensile stress of 100% L3360. This increase in maximum tensile stress is particularly significant at 10% by weight or greater SPI weight percentages. Figure 6 As shown, the Young's modulus of the tested protein polyurethane alloys is greater than that of 100% L3360. This increase in Young's modulus is particularly significant at SPI weight percentages of 15 weight % or greater.
[0151] Figure 7 The DMA graph shown in shows the measured storage modulus (E') of 100% L3360 (Example No. 1) and various proteins (Example Nos. 9 and 17 to 23) dissolved in L3360 at 30% by weight. The figure shows that gelatin, SPI and other proteins can be blended with L3360 to produce a protein polyurethane alloy having a second DMA modulus transition starting temperature greater than 100% of the second DMA modulus transition starting temperature of L3360. All proteins except whey produce a protein polyurethane alloy having a second DMA modulus transition starting temperature greater than 100% of the second DMA modulus transition starting temperature of L3360. It is believed that whey is miscible with the hard phase of L3360 because it can improve the mechanical properties of the protein polyurethane alloy relative to 100% of L3360. However, it is believed that whey does not increase the second DMA modulus transition starting temperature because whey has a low denaturation temperature as determined by DSC.
[0152] also, Figure 7 The graphs of FIG. 4 show that dissolving various proteins in L3360 does not result in a DMA transition temperature of the soft phase of the protein polyurethane alloy that is significantly different from the DMA transition temperature of the soft phase of 100% L3360. As shown in Table 4, the δ1 modulus transition onset of all Example Nos. 9 and 17 to 23 is less than 10° C. Relatedly, the δTan (δ) peak temperature of all Example Nos. 9 and 17 to 23 is less than 10° C. These results indicate that the protein is not miscible with the soft phase of L3360.
[0153] This selective miscibility of protein and hard phase L3360 is Fig. 8A and Figure 8B The mechanical property test results are further illustrated in the graphs plotted in FIG. 1 and reported in Tables 5 and 6. Fig. 8A and Figure 8B The graph of compares the tensile strength and Young's modulus of Example No. 1 and Example Nos. 9 and 17 to 23. An increase in tensile strength and / or an increase in Young's modulus may indicate that the protein is miscible with the hard phase of L3360. Tables 5 and 6 report the tensile strength and Young's modulus of these materials.
[0154] To further illustrate the selective miscibility of proteins with the hard phase of polyurethanes having both soft and hard phases, gelatin was blended with various exemplary polyurethanes. Figures 9 to 15 DMA thermograms for these exemplary blends are shown, as well as the thermogram of the polyurethane in the absence of gelatin. Fig. 9 The DMA data for protein polyurethane alloys made from 30 wt% gelatin and 70 wt% L3360 (Example No. 9) and 100% L3360 (Example No. 1) were compared. Fig.10 The DMA data for protein polyurethane alloys made from 30 wt % gelatin and 70 wt % HD-2001 (Example No. 15) and 100 wt % HD-2001 (Example No. 7) were compared. Fig.11 The DMA data for protein polyurethane alloys made from 30 wt% gelatin and 70 wt% Sancure (Example No. 14) and 100% Sancure (Example No. 6) were compared. Fig.12 The DMA data of protein polyurethane alloys made from 30 wt% gelatin and 70 wt% Impranil DLS (Example No. 12) and 100% Impranil DLS (Example No. 5) were compared. Fig.13 The DMA data for protein polyurethane alloys made from 30 wt% gelatin and 70 wt% UD-108 (Example No. 10) and 100% UD-108 (Example No. 2) were compared. Fig.14 The DMA data for protein polyurethane alloys made from 30 wt% gelatin and 70 wt% UD-303 (Example No. 13) and 100% UD-303 (Example No. 4) were compared. Fig.15 The DMA data for protein polyurethane alloys made from 30 wt% gelatin and 70 wt% UD-250 (Example No. 11) and 100% UD-250 (Example No. 3) were compared.
[0155] Fig. 22 The results showed that 30 wt% soy protein isolate (SPI) and 70 wt% DL 5249 and 100% DMA data of protein-polyurethane alloys made from DL 5249 polyurethane sample. Fig. 22 30 wt % soy protein isolate (SPI) and 70 wt % having an average thickness of 0.44 mm The average Young's modulus of the three samples of DL 5249 alloy is 65.80 MPa. Fig. 22 100% with an average thickness of 0.7 mm The average Young's modulus of three samples of DL 5249 polyurethane was 10.13 MPa. Fig. 22 The DMA data shown in Figure 2 and the results of this mechanical testing of protein polyurethane alloys illustrate the relationship between SPI and Selective miscibility of the hard phase of DL 5249.
[0156] Tables 3 and 4 report DMA data for various exemplary polyurethanes and those same polyurethanes blended with 30 wt % gelatin. Tables 5 and 6 report tensile strength and Young's modulus data for various exemplary polyurethanes and those same polyurethanes blended with 30 wt % gelatin. The results indicate that the tested proteins have selective miscibility with the hard phase of the tested polyurethanes.
[0157] In some embodiments, the protein polyurethane alloy may include a polyurethane having a second DMA modulus transition start temperature in the absence of protein. The second DMA modulus transition start temperature of the same protein polyurethane alloy may be in the range of about 5°C to about 100°C compared to the second DMA modulus transition start temperature of the polyurethane in the absence of protein. This relative increase in the second DMA modulus transition start temperature may be referred to as a "delta 2 modulus transition start". In some embodiments, the delta 2 modulus transition start may be about 5°C or higher. In some embodiments, the delta second modulus transition onset may be between about 5°C and about 100°C, about 5°C and about 95°C, about 5°C and about 90°C, about 5°C and about 85°C, about 5°C and about 80°C, about 5°C and about 75°C, about 5°C and about 70°C, about 5°C and about 65°C, about 5°C and about 60°C, about 5°C and about 55°C, about 5°C and about 50°C, about 5°C and about 45°C, about 5°C and about 40°C, about 5°C and about 35°C, about 5°C and about 30°C, about 5°C and about 25°C, about 5°C and about 20°C, about 5°C and about 15°C, about 5°C and about 10°C, about 10°C and about 100°C, about 15°C and about 10 ℃, about 0 ℃, about 20 ℃ to about 100 ℃, about 25 ℃ to about 100 ℃, about 30 ℃ to about 100 ℃, about 35 ℃ to about 100 ℃, about 40 ℃ to about 100 ℃, about 45 ℃ to about 100 ℃, about 50 ℃ to about 100 ℃, about 55 ℃ to about 100 ℃, about 60 ℃ to about 100 ℃, about 65 ℃ to about 100 ℃, about 70 ℃ to about 100 ℃, about 75 ℃ to about 100 ℃, about 80 ℃ to about 100 ℃, about 85 ℃ to about 100 ℃, about 90 ℃ to about 100 ℃ or about 95 ℃ to about 100 ℃, or in a range with any two of these values as endpoints, inclusive.
[0158] In some embodiments, the delta 2 modulus transition onset may be in the range of about 5°C to about 80°C. In some embodiments, the delta 2 modulus transition onset may be in the range of about 20°C to about 80°C.
[0159] In some embodiments, the delta 2 modulus transition onset may be in the range of about 40°C to about 80°C.
[0160] In some embodiments, the delta 2 modulus transition onset may be greater than about 100° C. For example, the delta 2 modulus transition onset may be in the range of about 100° C. to about 150° C.
[0161] In some embodiments, the soy protein polyurethane alloy may include a polyurethane having a second DMA modulus transition onset temperature in the absence of soy protein. The second DMA modulus transition onset temperature of the same soy protein polyurethane alloy may be about 15°C to about 100°C higher than the second DMA modulus transition onset temperature of the polyurethane in the absence of soy protein. In some embodiments, the delta 2 modulus transition onset of the soy protein polyurethane alloy may be about 15°C or higher. In some embodiments, the delta second modulus transition start of the soybean protein polyurethane alloy can be about 15°C to about 100°C, about 15°C to about 95°C, about 15°C to about 90°C, about 15°C to about 85°C, about 15°C to about 80°C, about 15°C to about 75°C, about 15°C to about 70°C, about 15°C to about 65°C, about 15°C to about 60°C, about 15°C to about 55°C, about 15°C to about 50°C, about 15°C to about 45°C, about 15°C to about 40°C, about 15°C to about 35°C, about 15°C to about 30°C, about 15°C to about 25°C, about 15°C to about 20°C, about 20°C ℃ to about 100 ℃, about 25 ℃ to about 100 ℃, about 30 ℃ to about 100 ℃, about 35 ℃ to about 100 ℃, about 40 ℃ to about 100 ℃, about 45 ℃ to about 100 ℃, about 50 ℃ to about 100 ℃, about 55 ℃ to about 100 ℃, about 60 ℃ to about 100 ℃, about 65 ℃ to about 100 ℃, about 70 ℃ to about 100 ℃, about 75 ℃ to about 100 ℃, about 80 ℃ to about 100 ℃, about 85 ℃ to about 100 ℃, about 90 ℃ to about 100 ℃ or about 95 ℃ to about 100 ℃, or in a range with any two of these values as endpoints, inclusive.
[0162] In some embodiments, the second DMA modulus transition onset temperature of the protein polyurethane alloy may be in the range of about 100° C. to about 200° C., including subranges. For example, in some embodiments, the second DMA modulus transition onset temperature of the protein polyurethane alloy may be in the range of about 100° C. to about 200° C., about 100° C. to about 195° C., about 100° C. to about 190° C., about 100° C. to about 185° C., about 100° C. to about 180° C., about 100° C. to about 175° C., about 100° C. to about 170° C., about 100° C. to about 165° C., about 100° C. to about 160° C., about 100° C. to about 155° C., about 100° C. to about 150° C., about 100° C. to about 145° C., about 100° C. to about 140° C., about 100° C. to about 135° C., about 100° C. to about 130° C., about 100° C. to about 125° C., about 100° C. to about 1 In some embodiments, the second DMA modulus transition onset temperature of the protein polyurethane alloy may be in the range of about 120°C to about 200°C, about 105°C to about 200°C, about 110°C to about 200°C, about 115°C to about 200°C, about 120°C to about 200°C, about 125°C to about 200°C, about 130°C to about 200°C, about 135°C to about 200°C, about 140°C to about 200°C, about 145°C to about 200°C, about 150°C to about 200°C, about 155°C to about 200°C, about 160°C to about 200°C, about 165°C to about 200°C, about 170°C to about 200°C, about 175°C to about 200°C, or about 180°C to about 200°C, or in a range having any two of these values as endpoints, inclusive. In some embodiments, the second DMA modulus transition onset temperature of the protein polyurethane alloy may be in the range of about 120°C to about 200°C. In some embodiments, the second DMA modulus transition onset temperature of the protein polyurethane alloy may be in the range of about 130° C. to about 200° C. In some embodiments, the second DMA modulus transition onset temperature of the protein polyurethane alloy may be in the range of about 165° C. to about 200° C.
[0163] In some embodiments, the second DMA modulus transition starting temperature of the soy protein polyurethane alloy may be in the range of about 130°C to about 200°C, including subranges. For example, in some embodiments, the second DMA modulus transition starting temperature of the soy protein polyurethane alloy may be in the range of about 130°C to about 200°C, about 130°C to about 195°C, about 130°C to about 190°C, about 130°C to about 185°C, about 130°C to about 180°C, about 130°C to about 175°C, about 130°C to about 170°C, about 130°C to about 165°C, about 130°C to about 160°C, about 130°C to about 155°C, about 130°C to about 150°C, about 130°C to about 145°C, about 130°C to about 150°C, about 130°C to about 145°C, about 130°C to about 150°C, about 130°C to about 15 ... ℃ to about 200 ℃, about 180 ℃ to about 200 ℃, about 185 ℃ to about 200 ℃, or about 190 ℃ to about 200 ℃, or in a range having any two of these values as endpoints, inclusive.
[0164] In some embodiments, the first DMA modulus transition temperature of the protein polyurethane alloy may be less than 30° C. In some embodiments, the first DMA modulus transition onset temperature of the protein polyurethane alloy may be in the range of about −65° C. to about 30° C., including subranges. For example, in some embodiments, the first DMA modulus transition onset temperature of the protein polyurethane alloy may be in a range of about -65°C to about 30°C, about -65°C to about 25°C, about -65°C to about 20°C, about -65°C to about 15°C, about -65°C to about 10°C, about -65°C to 5°C, about -65°C to about 1°C, about -65°C to 0°C, about -65°C to about 1°C, about -65°C to about -5°C, about -65°C to about -10°C, about -65°C to about -15°C, about -65°C to about -20°C, about -65°C to about -25°C, about -65°C to about -30°C, about -65°C to about -35°C, about -65°C to about -35°C, about -65°C to about -40°C, or about -65°C to about -45°C, or in a range having any two of these values as endpoints, inclusive.
[0165] In some embodiments, the protein polyurethane alloy may include a polyurethane having a first DMA modulus transition start temperature in the absence of protein. The first DMA modulus transition start temperature of the same protein polyurethane alloy may be + / -X°C of the first DMA modulus transition start temperature of the polyurethane in the absence of protein. This relative increase or decrease in the first DMA modulus transition start temperature may be referred to as "delta 1 modulus transition start". In some embodiments, X may be 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10.
[0166] In some embodiments, the DMA tan(δ) peak temperature of the protein polyurethane alloy may be less than 30° C. In some embodiments, the DMA tan(δ) peak temperature of the protein polyurethane alloy may be in the range of about −60° C. to about 30° C., including subranges. For example, in some embodiments, the DMA tan(δ) peak temperature of the protein polyurethane alloy may be in the range of about -60°C to about 30°C, about -60°C to about 25°C, about -60°C to about 20°C, about -60°C to about 15°C, about -60°C to about 10°C, about -60°C to 5°C, about -60°C to about 1°C, about -60°C to 0°C, about -60°C to about 1°C, about -60°C to about -5°C, about -60°C to about -10°C, about -60°C to about -15°C, about -60°C to about -20°C, about -60°C to about -25°C, about -60°C to about -30°C, about -60°C to about -35°C, or about -60°C to about -40°C, or in a range having any two of these values as endpoints.
[0167] In some embodiments, the protein polyurethane alloy may include a polyurethane having a DMA tan (δ) peak temperature corresponding to a soft phase of the polyurethane in the absence of protein. The DMA tan (δ) peak temperature of the same protein polyurethane alloy may be + / -Y ° C. of the DMA tan (δ) peak temperature corresponding to the soft phase of the polyurethane in the absence of protein. This relative increase or decrease in DMA Tan (δ) peak temperature may be referred to as "δ Tan (δ) peak temperature". In some embodiments, Y may be 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10.
[0168] In some embodiments, the protein polyurethane alloy may include a polyurethane having a tensile strength in the absence of protein. The tensile strength of the same protein polyurethane alloy may range from about 5% to about 55% greater than the tensile strength of the polyurethane in the absence of protein. This relative percentage increase in tensile strength may be referred to as "% delta tensile strength". In some embodiments, the % delta tensile strength may be 5% or greater. In some embodiments, the %δ tensile strength may be in the range of about 5% to about 55%, about 10% to about 55%, about 15% to about 55%, about 20% to about 55%, about 25% to about 55%, about 30% to about 55%, about 35% to about 55%, about 40% to about 55%, about 45% to about 55%, about 50% to about 55%, about 5% to about 50%, about 5% to about 45%, about 5% to about 40%, about 5% to about 35%, about 5% to about 30%, about 5% to about 25%, about 5% to about 20%, about 5% to about 15%, or about 5% to about 10%, or in the range with any two of these values as endpoints, including the endpoints. In some embodiments, the %δ tensile strength may be in the range of about 15% to about 55%. In some embodiments, the %δ tensile strength may be greater than about 55%. For example, the %δ tensile strength may be in the range of about 55% to about 1000%.
[0169] In some embodiments, the soybean protein polyurethane alloy may be included in the polyurethane with tensile strength in the absence of soybean protein. The tensile strength of the same soybean protein polyurethane alloy is comparable to the tensile strength of polyurethane in the absence of soybean protein in the range of about 10% to about 45%. In some embodiments, the %δ tensile strength of the soybean protein polyurethane alloy may be 10% or greater. In some embodiments, the %δ tensile strength of the soybean protein polyurethane alloy may be in the range of about 10% to about 45%, about 15% to about 45%, about 20% to about 45%, about 25% to about 45%, about 30% to about 45%, about 35% to about 45%, about 40% to about 45%, about 10% to about 40%, about 10% to about 35%, about 10% to about 30%, about 10% to about 25%, about 10% to about 20% or about 10% to about 15%, or in the range of any two of these values as endpoints, including endpoints.
[0170] In some embodiments, the protein polyurethane alloy may include a polyurethane having tensile strength in the absence of protein. The tensile strength of the same protein polyurethane alloy is about 2MPa (megapascals) to about 8MPa compared to the tensile strength of polyurethane in the absence of protein. This relative increase in tensile strength can be referred to as "delta tensile strength". In some embodiments, delta tensile strength can be 2MPa or greater. In some embodiments, delta tensile strength can be from about 2MPa to about 8MPa, from about 3MPa to about 8MPa, from about 4MPa to about 8MPa, from about 5MPa to about 8MPa, from about 6MPa to about MPa, from about 7MPa to about 8MPa, from about 2MPa to about 7MPa, from about 2MPa to about 6MPa, from about 2MPa to about 5MPa, from about 2MPa to about 4MPa or from about 2MPa to about 3MPa, or in the range of any two of these values as endpoints, including endpoints. In some embodiments, delta tensile strength can be in the range of from about 5MPa to about 8MPa. In some embodiments, delta tensile strength can be greater than about 8MPa. For example, the delta tensile strength may be in the range of about 8 MPa to about 15 MPa.
[0171] In some embodiments, the soy protein polyurethane alloy may be included in a polyurethane having a tensile strength in the absence of soy protein. The tensile strength of the same soy protein polyurethane alloy is about 1.5MPa to about 5.5MPa compared to the tensile strength of the polyurethane in the absence of soy protein. In some embodiments, the delta tensile strength of the soy protein polyurethane alloy may be 1.5MPa or greater. In some embodiments, the delta tensile strength of the soy protein polyurethane alloy may be in the range of about 1.5MPa to about 5.5MPa, about 2MPa to about 5.5MPa, about 3MPa to about 5.5MPa, about 4MPa to about 5.5MPa, about 1.5MPa to about 5MPa, about 1.5MPa to about 4MPa or about 1.5MPa to about 3MPa, or in the range of any two of these values as endpoints, including endpoints.
[0172] In some embodiments, the tensile strength of the protein polyurethane alloy may be in the range of about 7 MPa to about 21 MPa, including subranges. For example, in some embodiments, the tensile strength of the protein polyurethane alloy may be in the range of about 7 MPa to about 21 MPa, about 10 MPa to about 21 MPa, about 15 MPa to about 21 MPa, about 7 MPa to about 15 MPa, or about 7 MPa to about 10 MPa, or in a range having any of these values as endpoints, including endpoints. In some embodiments, the tensile strength of the protein polyurethane alloy may be greater than about 21 MPa. For example, the tensile strength of the protein polyurethane alloy may be in the range of about 21 MPa to about 25 MPa.
[0173] In some embodiments, the tensile strength of the soy protein polyurethane alloy may be in the range of about 14 MPa to about 19 MPa or about 16 MPa to about 19 MPa.
[0174] In some embodiments, the tensile strength of polyurethane in the absence of protein may be about 2MPa or greater. In some embodiments, the tensile strength of polyurethane in the absence of protein may be in the range of about 2MPa to about 35MPa, including sub-ranges. For example, in some embodiments, the tensile strength of polyurethane in the absence of protein may be in the range of about 2MPa to about 35MPa, about 5MPa to about 30MPa, about 10MPa to about 25MPa, or about 15MPa to about 20MPa, or in the range of any two of these values as endpoints, including endpoints. In some embodiments, the tensile strength of polyurethane in the absence of protein may be in the range of about 10MPa to about 15MPa. In some embodiments, the tensile strength of polyurethane in the absence of protein may be in the range of about 1MPa to about 35MPa.
[0175] In some embodiments, the protein polyurethane alloy may include a polyurethane having a Young's modulus in the absence of protein. The Young's modulus of the same protein polyurethane alloy may range from about 10% to about 600% greater than the Young's modulus of the polyurethane in the absence of protein. This relative percentage increase in Young's modulus may be referred to as "% δ Young's modulus". In some embodiments, the % δ Young's modulus may be about 10% or greater. In some embodiments, % δ Young's modulus may be in the range of about 10% to about 600%, about 20% to about 600%, about 30% to about 600%, about 40% to about 600%, about 50% to about 600%, about 60% to about 600%, about 70% to about 600%, about 80% to about 600%, about 90% to about 600%, about 100% to about 600%, about 200% to about 600%, about 300% to about 600%, about 400% to about 600%, or about 500% to about 600%, or in the range of having any two of these values as endpoints, including the endpoints. In some embodiments, % δ Young's modulus may be in the range of about 40% to about 600%. In some embodiments, % δ Young's modulus may be greater than about 600%. For example, % δ Young's modulus may be in the range of about 600% to about 2400%.
[0176] In some embodiments, the soy protein polyurethane alloy may include a polyurethane having a Young's modulus in the absence of soy protein. The Young's modulus of the same soy protein polyurethane alloy can be comparable to the Young's modulus of the polyurethane in the absence of soy protein in the range of about 60% to about 570%. In some embodiments, the %δ Young's modulus of the soy protein polyurethane alloy may be about 60% or greater. In some embodiments, the %δ Young's modulus of the soy protein polyurethane alloy may be in the range of about 60% to about 570%, about 100% to about 570%, about 200% to about 570%, about 300% to about 570%, about 400% to about 570% or about 500% to about 570%, or in the range of any two of these values as endpoints, including endpoints.
[0177] In some embodiments, the protein polyurethane alloy may include a polyurethane having a Young's modulus in the absence of protein. The Young's modulus of the same protein polyurethane alloy may range from about 10 MPa to about 350 MPa compared to the Young's modulus of the polyurethane in the absence of protein. This relative increase in Young's modulus may be referred to as "delta Young's modulus". In some embodiments, delta Young's modulus may be greater than 10 MPa. In some embodiments, the delta Young's modulus may be in the range of about 10 MPa to about 350 MPa, about 25 MPa to about 350 MPa, about 50 MPa to about 350 MPa, about 100 MPa to about 350 MPa, about 150 MPa to about 350 MPa, about 200 MPa to about 350 MPa, about 250 MPa to about 350 MPa, about 300 MPa to about 350 MPa, about 10 MPa to about 300 MPa, about 10 MPa to about 250 MPa, about 10 MPa to about 200 MPa, about 10 MPa to about 150 MPa, about 10 MPa to about 100 MPa, about 10 MPa to about 50 MPa, or about 10 MPa to about 25 MPa, or in a range having any two of these values as endpoints, including the endpoints. In some embodiments, the delta Young's modulus may be in the range of about 25 MPa to about 350 MPa. In some embodiments, the delta Young's modulus may be in the range of about 100 MPa to about 350 MPa.
[0178] In some embodiments, the soy protein polyurethane alloy may include a polyurethane having a Young's modulus in the absence of soy protein. The Young's modulus of the same soy protein polyurethane alloy may be in the range of about 35 MPa to about 340 MPa compared to the Young's modulus of the polyurethane in the absence of soy protein. In some embodiments, the delta Young's modulus of the soy protein polyurethane alloy may be greater than 35 MPa. In some embodiments, the delta Young's modulus of the soy protein polyurethane alloy may be in a range of about 35 MPa to about 340 MPa, about 50 MPa to about 340 MPa, about 100 MPa to about 340 MPa, about 150 MPa to about 340 MPa, about 200 MPa to about 340 MPa, about 250 MPa to about 340 MPa, about 300 MPa to about 340 MPa, about 35 MPa to about 300 MPa, about 35 MPa to about 250 MPa, about 35 MPa to about 200 MPa, about 35 MPa to about 150 MPa, about 35 MPa to about 100 MPa, or about 35 MPa to about 50 MPa, or in a range having any two of these values as endpoints, inclusive.
[0179] In some embodiments, the protein polyurethane alloy may have a Young's modulus in the range of about 50 MPa to about 450 MPa, including sub-ranges. For example, in some embodiments, the Young's modulus of the protein polyurethane alloy can be in a range of about 50 MPa to about 450 MPa, about 75 MPa to about 450 MPa, about 100 MPa to about 450 MPa, about 150 MPa to about 450 MPa, about 200 MPa to about 450 MPa, about 250 MPa to about 450 MPa, about 300 MPa to about 450 MPa, about 350 MPa to about 450 MPa, about 400 MPa to about 450 MPa, about 50 MPa to about 400 MPa, about 50 MPa to about 350 MPa, about 50 MPa to about 300 MPa, about 50 MPa to about 250 MPa, about 50 MPa to about 200 MPa, about 50 MPa to about 150 MPa, about 50 MPa to about 100 MPa, or about 50 MPa to about 75 MPa, or in a range having any two of these values as endpoints, inclusive. In some embodiments, the Young's modulus of the protein polyurethane alloy may be in the range of about 75 MPa to about 450 MPa. In some embodiments, the Young's modulus of the protein polyurethane alloy may be greater than about 450 MPa. For example, the Young's modulus of the protein polyurethane alloy may be in the range of about 450 MPa to about 580 MPa.
[0180] In some embodiments, the Young's modulus of the soy protein polyurethane alloy may be in the range of about 90 MPa to about 400 MPa, including subranges. For example, in some embodiments, the Young's modulus of the soy protein polyurethane alloy may be in the range of about 90 MPa to about 400 MPa, about 100 MPa to about 400 MPa, about 150 MPa to about 400 MPa, about 200 MPa to about 400 MPa, about 250 MPa to about 400 MPa, about 300 MPa to about 400 MPa, about 350 MPa to about 400 MPa, about 90 MPa to about 350 MPa, about 90 MPa to about 300 MPa, about 90 MPa to about 250 MPa, about 90 MPa to about 200 MPa, about 90 MPa to about 150 MPa, or about 90 MPa to about 100 MPa, or in a range having any two of these values as endpoints, including the endpoints.
[0181] In some embodiments, the polyurethane in the absence of protein may have a Young's modulus of about 10MPa or more. In some embodiments, the polyurethane in the absence of protein may have a Young's modulus in the range of about 10MPa to about 600MPa (including sub-ranges). For example, in some embodiments, the Young's modulus of the polyurethane in the absence of protein may be in the range of about 10MPa to about 600MPa, about 10MPa to about 500MPa, about 10MPa to about 400MPa, about 10MPa to about 300MPa, about 10MPa to about 200MPa, about 10MPa to about 100MPa, or about 10MPa to about 50MPa, or in the range of any two of these values as endpoints, including the endpoints. In some embodiments, the polyurethane in the absence of protein may have a Young's modulus in the range of about 50MPa to about 100MPa.
[0182] In some embodiments, the protein polyurethane alloy may include a polyurethane having a moisture vapor transmission rate in the absence of protein. The moisture vapor transmission rate of the same protein polyurethane alloy may be about 20% or greater than the moisture vapor transmission rate in the absence of protein. In some embodiments, the moisture vapor transmission rate of the protein polyurethane alloy may range from about 20% to about 600% greater than the moisture vapor transmission rate of the polyurethane in the absence of protein. This relative percentage increase in moisture vapor transmission rate may be referred to as "%δMVTR". In some embodiments, %δMVTR may be about 20% or greater. In some embodiments, the %δMVTR may be in the range of about 20% to about 600%, about 30% to about 600%, about 40% to about 600%, about 50% to about 600%, about 75% to about 600%, about 100% to about 600%, about 125% to about 600%, about 150% to about 600%, about 200% to about 600%, about 20% to about 500%, about 20% to about 400%, about 20% to about 300%, about 20% to about 200%, about 20% to about 150%, about 20% to about 125%, or about 20% to about 100%, or in a range having any two of these values as endpoints, inclusive.
[0183] In some embodiments, the soy protein polyurethane alloy may include a % δ MVTR of about 20% or greater. In some embodiments, the soy protein polyurethane alloy may have a % δ MVTR of about 20% to about 600%, about 30% to about 600%, about 40% to about 600%, about 50% to about 600%, about 75% to about 600%, about 100% to about 600%, about 125% to about 600%, about 150% to about 600%, about 200% to about 600%, about 20% to about 500%, about 20% to about 400%, about 20% to about 300%, about 20% to about 200%, about 20% to about 150%, about 20% to about 125%, or about 20% to about 100%, or in a range having any two of these values as endpoints, inclusive.
[0184] In some embodiments, the protein polyurethane alloy may include a polyurethane having a moisture vapor transmission rate in the absence of protein. The moisture vapor transmission rate of the same protein polyurethane alloy may be about 30 g / m2 higher than the moisture vapor transmission rate of the polyurethane in the absence of protein. 2 / 24 hours to about 500g / m 2 / 24 hours. This relative increase in moisture vapor transmission rate can be referred to as "δMVTR". In some embodiments, δMVTR can be greater than or equal to 30 g / m 2 / 24 hours. In some embodiments, the delta MVTR may be about 30 g / m 2 / 24 hours to about 500g / m 2 / 24 hours, about 40g / m 2 / 24 hours to about 500g / m 2 / 24 hours, about 50g / m 2 / 24 hours to about 500g / m 2 / 24 hours, about 75g / m 2 / 24 hours to about 500g / m 2 / 24 hours, about 100g / m 2 / 24 hours to about 500g / m 2 / 24 hours, about 150g / m 2 / 24 hours to about 500g / m 2 / 24 hours, about 200g / m 2 / 24 hours to about 500g / m 2 / 24 hours, about 300g / m 2 / 24 hours to about 500g / m 2 / 24 hours, about 30g / m 2 / 24 hours to about 400g / m 2 / 24 hours, about 30g / m 2 / 24 hours to about 300g / m 2 / 24 hours, about 30g / m 2 / 24 hours to about 200g / m 2 / 24 hours, about 30g / m 2 / 24 hours to about 150g / m 2 / 24 hours, about 30g / m 2 / 24 hours to about 100g / m 2 / 24 hours, about 30MPa to about 75g / m 2 / 24 hours or about 30g / m 2 / 24 hours to about 50g / m 2 / 24 hours, or in a range with any two of these values as endpoints, inclusive.
[0185] In some embodiments, the soy protein polyurethane alloy may include a delta MVTR greater than or equal to 30 g / m 2 / 24 hours. In some embodiments, the δMVTR of the soybean protein polyurethane alloy can be about 30 g / m 2 / 24 hours to about 500g / m 2 / 24 hours, about 40g / m 2 / 24 hours to about 500g / m 2 / 24 hours, about 50g / m 2 / 24 hours to about 500g / m 2 / 24 hours, about 75g / m 2 / 24 hours to about 500g / m 2 / 24 hours, about 100g / m 2 / 24 hours to about 500g / m 2 / 24 hours, about 150g / m 2 / 24 hours to about 500g / m 2 / 24 hours, about 200g / m 2 / 24 hours to about 500g / m 2 / 24 hours, about 300g / m 2 / 24 hours to about 500g / m 2 / 24 hours, about 30g / m 2 / 24 hours to about 400g / m 2 / 24 hours, about 30g / m 2 / 24 hours to about 300g / m 2 / 24 hours, about 30g / m 2 / 24 hours to about 200g / m 2 / 24 hours, about 30g / m 2 / 24 hours to about 150g / m 2 / 24 hours, about 30g / m 2 / 24 hours to about 100g / m 2 / 24 hours, about 30MPa to about 75g / m 2 / 24 hours or about 30g / m 2 / 24 hours to about 50g / m 2 / 24 hours, or in a range with any two of these values as endpoints, inclusive.
[0186] In some embodiments, the protein polyurethane alloy may include a moisture vapor transmission rate of about 30 g / m 2 / 24 hours to about 1000g / m 2 / 24 hours, including sub-ranges. For example, in some embodiments, the protein polyurethane alloy may include a moisture vapor transmission rate of about 30g / m 2 / 24 hours to about 1000g / m 2 / 24 hours, about 60g / m 2 / 24 hours to about 1000g / m 2 / 24 hours, about 100g / m 2 / 24 hours to about 1000g / m 2 / 24 hours, about 200g / m 2 / 24 hours to about 1000g / m2 / 24 hours, about 250g / m 2 / 24 hours to about 1000g / m 2 / 24 hours, about 300g / m 2 / 24 hours to about 1000g / m 2 / 24 hours, about 400g / m 2 / 24 hours to about 1000g / m 2 / 24 hours, about 500g / m 2 / 24 hours to about 1000g / m 2 / 24 hours, about 30g / m 2 / 24 hours to about 900g / m 2 / 24 hours, about 30g / m 2 / 24 hours to about 800g / m 2 / 24 hours, about 30g / m 2 / 24 hours to about 700g / m 2 / 24 hours, about 30g / m 2 / 24 hours to about 600g / m 2 / 24 hours, about 30g / m 2 / 24 hours to about 500g / m 2 / 24 hours, about 30g / m 2 / 24 hours to about 400g / m 2 / 24 hours, about 30g / m 2 / 24 hours to about 300g / m 2 / 24 hours, about 30g / m 2 / 24 hours to about 250g / m 2 / 24 hours, about 30g / m 2 / 24 hours to about 200g / m 2 / 24 hours or about 30g / m 2 / 24 hours to about 100g / m 2 / 24 hours, or within a range having any two of these values as endpoints, including the endpoints. In some embodiments, the protein polyurethane alloy may include a moisture vapor transmission rate greater than or equal to about 250 g / m 2 / 24 hours. For example, in some embodiments, the protein polyurethane alloy may include a moisture vapor transmission rate of about 250g / m 2 / 24 hours to about 1000g / m 2 / 24 hours, about 250g / m 2 / 24 hours to about 700g / m 2 / 24 hours or about 250g / m 2 / 24 hours to about 500g / m2 / 24 hours.
[0187] In some embodiments, the soy protein polyurethane alloy may include a moisture vapor transmission rate of about 30 g / m 2 / 24 hours to about 1000g / m 2 / 24 hours, including sub-ranges. For example, in some embodiments, the soy protein polyurethane alloy may include a moisture vapor transmission rate of about 30g / m 2 / 24 hours to about 1000g / m 2 / 24 hours, about 60g / m 2 / 24 hours to about 1000g / m 2 / 24 hours, about 100g / m 2 / 24 hours to about 1000g / m 2 / 24 hours, about 200g / m 2 / 24 hours to about 1000g / m 2 / 24 hours, about 250g / m 2 / 24 hours to about 1000g / m 2 / 24 hours, about 300g / m 2 / 24 hours to about 1000g / m 2 / 24 hours, about 400g / m 2 / 24 hours to about 1000g / m 2 / 24 hours, about 500g / m 2 / 24 hours to about 1000g / m 2 / 24 hours, about 30g / m 2 / 24 hours to about 900g / m 2 / 24 hours, about 30g / m 2 / 24 hours to about 800g / m 2 / 24 hours, about 30g / m 2 / 24 hours to about 700g / m 2 / 24 hours, about 30g / m 2 / 24 hours to about 600g / m 2 / 24 hours, about 30g / m 2 / 24 hours to about 500g / m 2 / 24 hours, about 30g / m 2 / 24 hours to about 400g / m 2 / 24 hours, about 30g / m 2 / 24 hours to about 300g / m 2 / 24 hours, about 30g / m 2 / 24 hours to about 250g / m 2 / 24 hours, about 30g / m 2 / 24 hours to about 200g / m 2 / 24 hours or about 30g / m 2 / 24 hours to about 100g / m 2 / 24 hours, or in a range having any two of these values as endpoints, including the endpoints. In some embodiments, the soybean protein polyurethane alloy may include a moisture vapor transmission rate greater than or equal to about 250 g / m 2 / 24 hours. For example, in some embodiments, the soy protein polyurethane alloy may include a moisture vapor transmission rate of about 250g / m 2 / 24 hours to about 1000g / m 2 / 24 hours, about 250g / m 2 / 24 hours to about 700g / m 2 / 24 hours or about 250g / m 2 / 24 hours to about 500g / m 2 / 24 hours.
[0188] Fig.17A A material 1700 is shown according to some embodiments. The material 1700 includes a base layer 1710 and a protein polyurethane alloy 1720 comprising one or more proteins dissolved in one or more polyurethanes.
[0189] The protein polyurethane alloy 1720 may be coated or otherwise deposited on the substrate layer 1710. In some embodiments, all or a portion of the protein polyurethane alloy 1720 may be integrated into the substrate layer 1710. In some embodiments, the protein polyurethane alloy 1720 may be disposed on the substrate layer 1710. In some embodiments, the protein polyurethane alloy 1720 may be disposed on the top surface 1714 of the substrate layer 1710. In some embodiments, the protein polyurethane alloy 1720 may be disposed on the bottom surface 1712 of the substrate layer 1710. In some embodiments, the protein polyurethane alloy 1720 may be disposed on the top surface 1714 of the substrate layer 1710. In some embodiments, the protein polyurethane alloy 1720 may be disposed on the bottom surface 1712 of the substrate layer 1710.
[0190] Base layer 1710 includes a bottom surface 1712, a top surface 1714, and a thickness 1716 measured between bottom surface 1712 and top surface 1714. In some embodiments, thickness 1716 can be in a range of about 50 microns to about 1000 microns, including subranges. For example, thickness 1716 can be about 50 microns, about 100 microns, about 150 microns, about 200 microns, about 250 microns, about 300 microns, about 350 microns, about 400 microns, about 500 microns, about 600 microns, about 700 microns, about 800 microns, about 900 microns, or about 1000 microns, or in a range having any two of these values as endpoints, including the endpoints. In some embodiments, thickness 1716 may be in a range from about 100 microns to about 900 microns, about 150 microns to about 800 microns, about 200 microns to about 700 microns, about 250 microns to about 600 microns, about 300 microns to about 500 microns, or about 350 microns to about 400 microns.
[0191] The base layer 1710 may have a g / m2 (g / m 2 ) is measured in units of about 50g / m 2 About 600g / m 2 For example, the dry weight of the base layer 110 may be about 50 g / m 2 , about 75g / m 2 , about 100g / m 2 , about 125g / m 2 , about 150g / m 2 , about 175g / m 2 , about 200g / m 2 , about 300g / m 2 , about 400g / m 2 , about 500g / m 2 or about 600g / m 2 , or within a range having any two of these values as endpoints. In some embodiments, the dry weight of the base layer 1710 may be about 75 g / m 2 About 500g / m 2 , about 100g / m 2 About 400g / m 2 , about 125g / m 2 About 300g / m 2 , about 150g / m 2 About 200g / m 2 or about 175g / m 2 About 200g / m 2 within the range.
[0192] The base layer 1710 may include one or more textiles. The base layer 1710 may include one or more textile layers. The one or more textile layers may be, for example, a woven material layer, a nonwoven material layer, a braided fabric layer, a mesh fabric layer, or a leather layer. The one or more textile layers may be composed of recycled or virgin fibers, filaments, or yarns. In some embodiments, the base layer 1710 may be or may include a polyester braided fabric layer, a polyester-cotton blend, a polyester-cotton spandex blended braided fabric layer, or a suede leather layer. In some embodiments, the base layer 1710 may be made of one or more natural fibers, such as fibers made of cotton, linen, silk, wool, kenaf, flax, cashmere, angora goat wool, bamboo, bast, hemp, soybean, algae fiber, milk or milk protein, spider silk, chitosan, mycelium, cellulose (including bacterial cellulose) or wood. Mycelium is the nutrient part of a fungus or fungus-like bacterial colony, which is composed of a large number of branched linear hyphae. Fungi are primarily composed of cell walls that extend continuously at the apex of the hyphae. Unlike plant cell walls, which are primarily composed of cellulose, or animal cell structural components that rely on collagen, fungal cell walls rely primarily on chitin and beta-glucan for their structural oligosaccharides. Chitin is a strong, hard substance that is also found in the exoskeletons of arthropods.
[0193] In some embodiments, the base layer 1710 can be made of one or more synthetic fibers, such as polyester, nylon, aramid, polyolefin fibers (such as polyethylene, polypropylene), rayon, lyocell, viscose, antimicrobial yarn (AMY), Sorbtek, nylon, elastomers such as Spandex or Fibers made from polyester-polyurethane copolymers, aromatic polyamides, carbon (including carbon fibers and fullerenes), glass, silicon, minerals, metals or metal alloys (including those containing iron, steel, lead, gold, silver, platinum, copper, zinc and titanium), or mixtures thereof.
[0194] In some embodiments, nonwoven substrate layer 1710 can be a staple fiber nonwoven material, a meltblown nonwoven material, a spun nonwoven material, a flash spun nonwoven material or a combination thereof. In some embodiments, nonwoven substrate layer 1710 can be made by a carding process, can be air-laid, or can be wet-laid. In some embodiments, carding, air-laid or wet-laid substrates can be bonded by, for example, needle punching, spunlace, lamination or thermal bonding. In some embodiments, nonwoven substrate layer 1710 may include one or more natural fibers, for example, fibers made of cotton, linen, silk, wool, kenaf, flax, cashmere, angora goat wool, bamboo, bast, hemp, soybean, algae fiber, milk or milk protein, spider silk, chitosan, mycelium, cellulose (including bacterial cellulose) or wood.
[0195] In some embodiments, nonwoven substrate layer 1710 may include polymer fibers having functional particles in polymers. Exemplary functional particles include ceramic particles mixed in polymer resins during the extrusion process of preparing polymer fibers. Such ceramic particles can provide desired heat dissipation and flame retardant properties for polymer fibers. In some embodiments, nonwoven substrate layer 1710 may include fibers made of pulp (e.g., grape pulp or apple pulp) or pineapple fibers. In some embodiments, nonwoven substrate layer 1710 may include fibers made of recycled materials such as recycled plastics. In some embodiments, nonwoven substrate layer 1710 may include algae fibers. In some embodiments, nonwoven substrate layer 1710 may include cork fibers.
[0196] In some embodiments, the base layer 1710 may be or may include a spacer fabric, such as Fig.21 1. The spacer fabric 2100 is shown. The spacer fabric 2100 includes a first fabric layer 2110 and a second fabric layer 2120 connected by one or more spacer yarns 2130. The spacer yarns 2130 are disposed between the first fabric layer 2110 and the second fabric layer 2120 and define a distance between an inner surface 2114 of the first fabric layer 2110 and an inner surface 2124 of the second fabric layer 2120. The outer surface 2112 of the first fabric layer 2110 and the outer surface 2122 of the second fabric layer 2120 can define the top surface 1714 and the bottom surface 1712 of the base layer 1710, respectively.
[0197] The first fabric layer 2110 and the second fabric layer 2120 may include one or more fabric material layers. In some embodiments, the first fabric layer 2110 and the second fabric layer 2120 may include one or more textile layers made of staple fibers, filaments or their mixtures. As used herein, "short fibers" are fibers with a short length between about 0.2 mm and about 5 cm. Staple fibers may be naturally occurring or may be cut filaments. As used herein, "filaments" are long fibers with a length of 5 cm or longer. In some embodiments, the first fabric layer 2110 and the second fabric layer 2120 may include one or more woven material layers or knitted material layers. In some embodiments, the outer surface 2112 of the first fabric layer 2110 may be limited by a woven fabric layer or a knitted fabric layer. In some embodiments, the outer surface 2122 of the second fabric layer 2120 may be limited by a woven fabric layer or a knitted fabric layer.
[0198] In some embodiments, the first fabric layer 2110 and the second fabric layer 2120 may be made of one or more natural fibers, such as fibers made of cotton, linen, silk, wool, kenaf, flax, cashmere, angora goat wool, bamboo, bast, hemp, soy, algae fiber, milk or milk protein, spider silk, chitosan, mycelium, cellulose (including bacterial cellulose), or wood. In some embodiments, the first fabric layer 2110 and the second fabric layer 2120 may be made of one or more synthetic fibers, such as polyester, nylon, aramid, polyolefin fibers (such as polyethylene, polypropylene), rayon, lyocell, viscose, antimicrobial yarn (AMY), Sorbtek, nylon, elastomers such as Spandex or Fibers made of polyester-polyurethane copolymers, aromatic polyamides, carbon (including carbon fibers and fullerenes), glass, silicon, minerals, metals or metal alloys (including those containing iron, steel, lead, gold, silver, platinum, copper, zinc and titanium), or mixtures thereof. Spacer yarns 2130 may include monofilament yarns composed of any natural or synthetic material listed above for first fabric layer 2110 and second fabric layer 2120.
[0199] In some embodiments, the base layer 1710 can be colored with a colorant. In some embodiments, the colorant can be a colored dye, such as an acid dye, a fiber reactive dye, a direct dye, a sulfur dye, a basic dye, a reactive dye, or a vat dye. In some embodiments, the colorant can be a pigment, such as a lake pigment. In some embodiments, a first colorant can be incorporated into the protein polyurethane alloy, and a second colorant can be incorporated into the base layer 1710, depending on the desired aesthetics of the material.
[0200] Fiber-reactive dyes include one or more chromophores that are included in side groups that can form covalent bonds with nucleophilic sites in fiber cellulose substrates in the presence of alkaline pH and high temperature. These dyes can achieve high washing color fastness and bright tones over a wide range. Exemplary fiber-reactive dyes include, but are not limited to, sulfate-ethyl sulfone (Remazol), triazine, vinyl sulfone, and acrylamide dyes. These dyes can dye protein fibers such as silk, wool, and nylon by reacting with fiber nucleophiles via Michael addition. Direct dyes are anionic dyes that can dye cellulose or protein fibers. In the presence of electrolytes such as sodium chloride or sodium sulfate, near boiling point, these dyes can have an affinity for cellulose. Exemplary direct dyes include, but are not limited to, azo, stilbene, phthalocyanine, and dioxazine.
[0201] In some embodiments, material 1700 may include a first portion 1730 having a first protein polyurethane alloy density and a second portion 1740 having a second protein polyurethane alloy density different from the first protein polyurethane alloy density. As used herein, "protein polyurethane alloy density" refers to the mass of protein polyurethane alloy in grams per unit volume in a given component (e.g., a material, textile, or layer).
[0202] In some embodiments, the density of the first protein polyurethane alloy may be 5% or more less than or greater than the density of the second protein polyurethane alloy. In some embodiments, the density of the first protein polyurethane alloy may be 10% or more less than or greater than the density of the second protein polyurethane alloy. In some embodiments, the density of the first protein polyurethane alloy may be 20% or more less than or greater than the density of the second protein polyurethane alloy.
[0203] In some embodiments, the first protein polyurethane alloy density may be in the range of about 0.001 g / cc (grams per cubic centimeter) to about 1 g / cc. For example, in some embodiments, the first protein polyurethane alloy density can be in the range of about 0.001 g / cc to about 0.9 g / cc, about 0.001 g / cc to about 0.8 g / cc, about 0.001 g / cc to about 0.7 g / cc, about 0.001 g / cc to about 0.6 g / cc, about 0.001 g / cc to about 0.5 g / cc, about 0.001 g / cc to about 0.4 g / cc, about 0.001 g / cc to about 0.3 g / cc, about 0.001 g / cc to about 0.2 g / cc, about 0.001 g / cc to about 0.1 g / cc, about 0.01 g / cc to about 1 g / cc, about 0.05 g / cc to about 1 g / cc, about 0.1 g / cc to about 1 g / cc, or about 0.5 g / cc to about 1 g / cc. In some embodiments, the first protein polyurethane alloy density may be in the range of about 0.05 g / cc to about 0.9 g / cc. For example, in some embodiments, the first protein polyurethane alloy density can be in the range of about 0.05 g / cc to about 0.8 g / cc, about 0.05 g / cc to about 0.7 g / cc, about 0.05 g / cc to about 0.6 g / cc, about 0.05 g / cc to about 0.5 g / cc, about 0.05 g / cc to about 0.4 g / cc, about 0.05 g / cc to about 0.3 g / cc, about 0.05 g / cc to about 0.2 g / cc, about 0.1 g / cc to about 0.9 g / cc, about 0.2 g / cc to about 0.9 g / cc, about 0.3 g / cc to about 0.9 g / cc, about 0.4 g / cc to about 0.9 g / cc, about 0.5 g / cc to about 0.9 g / cc, about 0.6 g / cc to about 0.9 g / cc, or about 0.7 g / cc to about 0.9 g / cc.
[0204] In some embodiments, the second protein polyurethane alloy density may be in the range of about 0.001 g / cc to about 1 g / cc. For example, in some embodiments, the second protein polyurethane alloy density can be in the range of about 0.001 g / cc to about 0.9 g / cc, about 0.001 g / cc to about 0.8 g / cc, about 0.001 g / cc to about 0.7 g / cc, about 0.001 g / cc to about 0.6 g / cc, about 0.001 g / cc to about 0.5 g / cc, about 0.001 g / cc to about 0.4 g / cc, about 0.001 g / cc to about 0.3 g / cc, about 0.001 g / cc to about 0.2 g / cc, about 0.001 g / cc to about 0.1 g / cc, about 0.01 g / cc to about 1 g / cc, about 0.05 g / cc to about 1 g / cc, about 0.1 g / cc to about 1 g / cc, or about 0.5 g / cc to about 1 g / cc. In some embodiments, the second protein polyurethane alloy density may be in the range of about 0.05 g / cc to about 0.9 g / cc. For example, in some embodiments, the second protein polyurethane alloy density can be in the range of about 0.05 g / cc to about 0.8 g / cc, about 0.05 g / cc to about 0.7 g / cc, about 0.05 g / cc to about 0.6 g / cc, about 0.05 g / cc to about 0.5 g / cc, about 0.05 g / cc to about 0.4 g / cc, about 0.05 g / cc to about 0.3 g / cc, about 0.05 g / cc to about 0.2 g / cc, about 0.1 g / cc to about 0.9 g / cc, about 0.2 g / cc to about 0.9 g / cc, about 0.3 g / cc to about 0.9 g / cc, about 0.4 g / cc to about 0.9 g / cc, about 0.5 g / cc to about 0.9 g / cc, about 0.6 g / cc to about 0.9 g / cc, or about 0.7 g / cc to about 0.9 g / cc.
[0205] In some embodiments, the first portion 1730 may include the protein polyurethane alloy 1720 integrated into the base layer 1710 at a first protein polyurethane alloy density, and the second portion 1740 may include the protein polyurethane alloy 1720 integrated into the base layer 1710 at a second protein polyurethane alloy density.
[0206] In some embodiments, such as for example Fig. 17BAs shown, the base layer 1710 may include a first layer 1750 (e.g., a first textile layer) coupled to a second layer 1760 (e.g., a second textile layer). In such embodiments, the first portion 1730 of the material 1700 may include a protein polyurethane alloy 1720 integrated into the first layer 1750 at a first protein polyurethane alloy density, and the second portion 1740 of the material 1700 may include a protein polyurethane alloy 1720 integrated into the second layer 1760 at a second protein polyurethane alloy density.
[0207] In some embodiments, such as for example Fig. 17C As shown, the material 1700 may include a first protein polyurethane alloy layer 1770 disposed on the top surface 1714 of the base layer 1710, a second protein polyurethane layer 1780 disposed on the bottom surface 1712 of the base layer 1710, or both. In some embodiments, the first portion 1730 of the material 1700 may include the first protein polyurethane alloy layer 1770, and the second portion 1740 of the material 1700 may include the second protein polyurethane alloy layer 1780. In some embodiments, the first portion 1730 of the material 1700 may be the first protein polyurethane alloy layer 1770, and the second portion 1740 of the material 1700 may be the second protein polyurethane alloy layer 1780.
[0208] The first protein polyurethane alloy layer 1770 includes a bottom surface 1772, a top surface 1774, and a thickness 1776 measured between the bottom surface 1772 and the top surface 1774. In some embodiments, the thickness 1776 can be in a range of about 25 micrometers to about 400 micrometers (micrometers, μm). For example, in some embodiments, the thickness 1776 can be in a range of about 50 micrometers to about 350 micrometers, about 75 micrometers to about 300 micrometers, about 100 micrometers to about 250 micrometers, about 125 micrometers to about 200 micrometers, or about 150 micrometers to about 175 micrometers.
[0209] Similarly, second protein polyurethane alloy layer 1780 includes a bottom surface 1782, a top surface 1784, and a thickness 1786 measured between bottom surface 1782 and top surface 1784. In some embodiments, thickness 1786 can be in a range of about 25 micrometers to about 400 micrometers (micrometers, μm). For example, in some embodiments, thickness 1786 can be in a range of about 50 micrometers to about 350 micrometers, about 75 micrometers to about 300 micrometers, about 100 micrometers to about 250 micrometers, about 125 micrometers to about 200 micrometers, or about 150 micrometers to about 175 micrometers.
[0210] In some embodiments, the protein polyurethane alloy layer 1720 may include a foaming agent. In some embodiments, the protein polyurethane alloy layer 1720 may include a foam stabilizer. Suitable foam stabilizers include, but are not limited to 0520 (a surfactant available from Unichem Specialty Chemicals, LLC) or HeiQ Chemtex 2216-T (a stable blend of nonionic and anionic surfactants), HeiQ Chemtex 2241-A (a modified HEUR (hydrophobically modified ethylene oxide urethane) thickener), HeiQ Chemtex 2243 (a nonionic silicone dispersion) or HeiQ Chemtex 2317 (a stable blend of nonionic and anionic surfactants) foam stabilizers available from HeiQ Chemtex.
[0211] In some embodiments, material 1700 may include one or more colorants. In some embodiments, the colorant may be a colored dye, such as a fiber reactive dye, a direct dye, an acid dye, or a natural dye. Exemplary dyes include, but are not limited to, azo acid dyes, metal complex structured acid dyes, anthraquinone structured acid dyes, azo / diazo direct dyes, sulfur dyes, and vat dyes. In some embodiments, the colorant may be a pigment, such as a lake pigment.
[0212] In some embodiments, material 1700 may include one or more colored dyes. In some embodiments, material 1700 may include about 100 weight % to about 250 weight % of one or more colored dyes, and the weight % of the one or more colored dyes is measured relative to the weight of the protein in the protein polyurethane alloy 1720. For example, for a material comprising an alloy containing 10 grams of protein and 10 grams of colored dyes, the colored dye exists with 100 weight %. For another example, for a material comprising an alloy containing 10 grams of protein, 5 grams of the first colored dye and 5 grams of the second colored dye, the colored dye exists with 100 weight %. In some embodiments, the one or more colored dyes may include two colored dyes. In some embodiments, the one or more colored dyes may include three colored dyes. In some embodiments, the one or more colored dyes may include four colored dyes.
[0213] In some embodiments, material 1700 may include from about 100% to about 250% by weight of one or more colored dyes, from about 100% to about 245% by weight of one or more colored dyes, from about 100% to about 240% by weight of one or more colored dyes, from about 100% to about 235% by weight of one or more colored dyes, from about 100% to about 230% by weight of one or more colored dyes, from about 100% to about 225% by weight of one or more colored dyes, from about 100% to about 220% by weight of one or more colored dyes, from about 100% to about 215% by weight of one or more colored dyes, and from about 100% to about 210% by weight of one or more colored dyes. or more colored dyes, from about 100 wt % to about 205 wt % of one or more colored dyes, from about 100 wt % to about 200 wt % of one or more colored dyes, from about 100 wt % to about 195 wt % of one or more colored dyes, from about 100 wt % to about 190 wt % of one or more colored dyes, from about 100 wt % to about 185 wt % of one or more colored dyes, from about 100 wt % to about 180 wt % of one or more colored dyes, from about 100 wt % to about 175 wt % of one or more colored dyes, from about 100 wt % to about 170 wt % of one or more colored dyes, from about 100 wt % to about 165 ... 0 wt % to about 160 wt % of one or more colored dyes, about 100 wt % to about 155 wt % of one or more colored dyes, about 100 wt % to about 150 wt % of one or more colored dyes, about 100 wt % to about 145 wt % of one or more colored dyes, about 100 wt % to about 140 wt % of one or more colored dyes, about 100 wt % to about 135 wt % of one or more colored dyes, about 100 wt % to about 130 wt % of one or more colored dyes, about 100 wt % to about 125 wt % of one or more colored dyes, about 100 wt % to about 120 wt % of one or more colored dyes, 100 wt % to about 115 wt % of one or more colored dyes % to about 250 wt % of one or more colored dyes, about 100 wt % to about 110 wt % of one or more colored dyes, about 100 wt % to about 105 wt % of one or more colored dyes, about 105 wt % to about 250 wt % of one or more colored dyes, about 110 wt % to about 250 wt % of one or more colored dyes, about 115 wt % to about 250 wt % of one or more colored dyes, about 120 wt % to about 250 wt % of one or more colored dyes, about 125 wt % to about 250 wt % of one or more colored dyes, about 130 wt % to about 250 wt % of one or more colored dyes, about 135 wt % to about 250 wt % of one or more colored dyes,from about 140 wt % to about 250 wt % of one or more colored dyes, from about 145 wt % to about 250 wt % of one or more colored dyes, from about 150 wt % to about 250 wt % of one or more colored dyes, from about 155 wt % to about 250 wt % of one or more colored dyes, from about 160 wt % to about 250 wt % of one or more colored dyes, from about 165 wt % to about 250 wt % of one or more colored dyes, from about 170 wt % to about 250 wt % of one or more colored dyes, from about 175 wt % to about 250 wt % of one or more colored dyes, from about 180 wt % to about 250 wt % of one or more colored dyes, from about 185 wt % to about 250 wt % of one or more colored dyes, from about 190 wt % to about 250 wt % of one or more colored dyes, from about 195 wt % to about 250 wt % of one or more colored dyes, % of the one or more colored dyes, about 200 wt % to about 250 wt % of the one or more colored dyes, about 205 wt % to about 250 wt % of the one or more colored dyes, about 210 wt % to about 250 wt % of the one or more colored dyes, about 215 wt % to about 250 wt % of the one or more colored dyes, about 220 wt % to about 250 wt % of the one or more colored dyes, about 225 wt % to about 250 wt % of the one or more colored dyes, about 230 wt % to about 250 wt % of the one or more colored dyes, about 235 wt % to about 250 wt % of the one or more colored dyes, about 240 wt % to about 250 wt % of the one or more colored dyes, or about 245 wt % to about 250 wt % of the one or more colored dyes, or within a range having any two of these values as endpoints, inclusive.
[0214] The protein in the alloy of the material containing about 100 wt % to about 250 wt % of one or more colored dyes can be collagen, gelatin, bovine serum albumin (BSA), soy protein, pea protein, ovalbumin, casein, peanut protein, edema globulin, whey protein, karanja protein, cellulase, or a combination thereof. Suitable collagens include, but are not limited to, recombinant collagen (r-collagen), recombinant collagen fragments, and extracted collagen. In some embodiments, the collagen can be a collagen fragment comprising an amino acid sequence having at least 80% sequence identity with SEQ ID NO: 2.
[0215] In some embodiments, protein polyurethane alloy 1720 may include one or more colorants. In some embodiments, the colorant may be a colored dye, such as a fiber reactive dye, a direct dye, an acid dye, or a natural dye. Exemplary dyes include, but are not limited to, azo acid dyes, metal complex structure acid dyes, anthraquinone structure acid dyes, azo / diazo direct dyes, sulfur dyes, and vat dyes. In some embodiments, the colorant may be a pigment, such as a lake pigment. In some embodiments, the one or more colored dyes may include two colored dyes. In some embodiments, the one or more colored dyes may include three colored dyes. In some embodiments, the one or more colored dyes may include four colored dyes.
[0216] In some embodiments, the protein polyurethane alloy 1720 can include one or more colored dyes, the weight percent of the one or more colored dyes being measured relative to the weight of the protein in the protein polyurethane alloy 1720. In some embodiments, the protein polyurethane alloy 1720 can include about 100 weight percent to about 250 weight percent of the one or more colored dyes, about 100 weight percent to about 245 weight percent of the one or more colored dyes, about 100 weight percent to about 240 weight percent of the one or more colored dyes, about 100 weight percent to about 235 weight percent of the one or more colored dyes, about 100 weight percent to about 230 weight percent of the one or more colored dyes, about 100 weight percent to about 225 weight percent of the one or more colored dyes, about 100 weight percent to about 220 weight percent of the one or more colored dyes, about 100 weight percent to about 215 weight percent of the one or more colored dyes. % to about 180 wt % of one or more colored dyes, about 100 wt % to about 175 wt % of one or more colored dyes, about 100 wt % to about 170 wt % of one or more colored dyes, about 100 wt % to about 185 wt % of one or more colored dyes, about 100 wt % to about 190 wt % of one or more colored dyes, about 100 wt % to about 195 wt % of one or more colored dyes, about 100 wt % to about 190 wt % of one or more colored dyes, about 100 wt % to about 185 wt % of one or more colored dyes, about 100 wt % to about 180 wt % of one or more colored dyes, about 100 wt % to about 175 wt % of one or more colored dyes, about 100 wt % to about 170 wt % of one or more colored dyes, % of one or more colored dyes, about 100 wt % to about 165 wt % of one or more colored dyes, about 100 wt % to about 160 wt % of one or more colored dyes, about 100 wt % to about 155 wt % of one or more colored dyes, about 100 wt % to about 150 wt % of one or more colored dyes, about 100 wt % to about 145 wt % of one or more colored dyes, about 100 wt % to about 140 wt % of one or more colored dyes, about 100 wt % to about 135 wt % of one or more colored dyes, about 100 wt % to about 130 wt % of one or more colored dyes, about 100 wt % to about 155 wt % of one or more colored dyes, % to about 125% by weight of one or more colored dyes, from about 100% to about 120% by weight of one or more colored dyes, from about 100% to about 115% by weight of one or more colored dyes, from about 100% to about 110% by weight of one or more colored dyes, from about 100% to about 105% by weight of one or more colored dyes, from about 105% to about 250% by weight of one or more colored dyes, from about 110% to about 250% by weight of one or more colored dyes, from about 115% to about 250% by weight of one or more colored dyes, from about 120% to about 250% by weight of one or more colored dyes,From about 125 wt % to about 250 wt % of one or more colored dyes, from about 130 wt % to about 250 wt % of one or more colored dyes, from about 135 wt % to about 250 wt % of one or more colored dyes, from about 140 wt % to about 250 wt % of one or more colored dyes, from about 145 wt % to about 250 wt % of one or more colored dyes, from about 150 wt % to about 250 wt % of one or more colored dyes, from about 155 wt % to about 250 wt % of one or more colored dyes, from about 160 wt % to about 250 wt % of one or more colored dyes, from about 165 wt % to about 250 wt % of one or more colored dyes, from about 170 wt % to about 250 wt % of one or more colored dyes, from about 175 wt % to about 250 wt % of one or more colored dyes, from about 180 wt % to about 250 wt % of one or more colored dyes, from about 185 wt % to about 250 wt % of one or more colored dyes, from about 190 wt % to about 250 wt % of one or more colored dyes, about 195 wt % to about 250 wt % of one or more colored dyes, about 200 wt % to about 250 wt % of one or more colored dyes, about 205 wt % to about 250 wt % of one or more colored dyes, about 210 wt % to about 250 wt % of one or more colored dyes, about 215 wt % to about 250 wt % of one or more colored dyes, about 220 wt % to about 250 wt % of one or more colored dyes, about 225 wt % to about 250 wt % of one or more colored dyes, about 230 wt % to about 250 wt % of one or more colored dyes, about 235 wt % to about 250 wt % of one or more colored dyes, about 240 wt % to about 250 wt % of one or more colored dyes, or about 245 wt % to about 250 wt % of one or more colored dyes, or within a range having any two of these values as endpoints, inclusive.
[0217] The protein in the protein polyurethane alloy containing about 100 wt % to about 250 wt % of one or more colored dyes can be collagen, gelatin, bovine serum albumin (BSA), soy protein, pea protein, egg white albumin, casein, peanut protein, edema globulin, whey protein, karanja protein, cellulase or a combination thereof. Suitable collagens include, but are not limited to, recombinant collagen (r-collagen), recombinant collagen fragments and extracted collagen. In some embodiments, the collagen can be a collagen fragment comprising an amino acid sequence having at least 80% sequence identity with SEQ ID NO: 2.
[0218] In some embodiments, one or more colored dyes can be incorporated into the material 1700 and the protein polyurethane alloy 1720 by dyeing the material 1700 with one or more colored dyes. In some embodiments, one or more colored dyes can be incorporated into the material 1700 by blending the one or more colored dyes in a formulation before applying the formulation to the base layer 1710. In some embodiments, one or more colored dyes can be incorporated into the material 1700 and the protein polyurethane alloy 1720 by dyeing the material 1700 with one or more colored dyes and blending the one or more colored dyes in a formulation before applying the formulation to the base layer 1710.
[0219] In some embodiments, material 1700 can include a base coating (eg, base coating 1860). In some embodiments, material 1700 can include a top coating (eg, top coating 1870).
[0220] Fig.18A A layered material 1800 according to some embodiments is shown. The layered material 1800 includes a polyurethane protein alloy layer 1820 attached to a base layer 1710. The polyurethane protein alloy layer 1820 may be directly attached to the surface of the base layer 1710 or attached to the surface of the base layer 1710 via an intermediate layer (e.g., an adhesive layer). Direct attachment may be achieved using, for example, a thermal bonding process or stitching. The polyurethane protein alloy layer 1820 may be referred to as a "first polyurethane protein alloy layer".
[0221] The polyurethane protein alloy layer 1820 may include one or more types of proteins and one or more polyurethanes. In some embodiments, the polyurethane protein alloy layer 1820 may include one or more proteins dissolved in one or more polyurethanes. In some embodiments, the polyurethane protein alloy layer 1820 may be transparent. The transparency of the polyurethane protein alloy layer is evaluated before dyeing or otherwise coloring the polyurethane protein alloy layer.
[0222] The transparent protein polyurethane alloy layer can provide unique properties to the layered material. For example, the transparent protein polyurethane alloy layer can provide a unique color depth when dyed compared to an opaque layer. Similarly, the transparent protein polyurethane alloy layer can provide the layered material with its mechanical properties without significantly affecting the aesthetic properties of the material.
[0223] The protein polyurethane alloy layer 1820 includes a bottom surface 1822, a top surface 1824, and a thickness 1826 measured between the bottom surface 1822 and the top surface 1824. In some embodiments, the thickness 1826 may be in the range of about 25 microns to about 400 microns (micrometers, μm), including sub-ranges. For example, the thickness 1826 may be about 25 microns, about 50 microns, about 100 microns, about 125 microns, about 150 microns, about 175 microns, about 200 microns, about 250 microns, about 300 microns, about 350 microns, or about 400 microns, or in a range having any two of these values as endpoints, including endpoints. In some embodiments, the thickness 1826 may be in the range of about 50 microns to about 350 microns, about 75 microns to about 300 microns, about 100 microns to about 250 microns, about 125 microns to about 200 microns, or about 150 microns to about 175 microns.
[0224] The protein polyurethane alloy layer 1820 may have a gsm (g / m 2 ) is measured in units of about 25g / m 2 About 125g / m 2 For example, the dry weight of the protein polyurethane alloy layer 1820 may be about 25 g / m 2 , about 50g / m 2 , about 75g / m 2 , about 100g / m 2 or about 125g / m 2 , or within a range of any two of these values as endpoints, including the endpoints. In some embodiments, the dry weight of the protein polyurethane alloy layer 1820 can be about 25 g / m 2 About 125g / m 2 , about 25g / m 2 About 100g / m 2 or about 50g / m 2 About 100g / m 2 within the range.
[0225] Unless otherwise specified, the dry weight of the layer is measured during the preparation of the material using the following method. First, before the layer under consideration is applied to the material, a first sample of the material (about 10 cm in diameter) is cut, and the weight and size are measured to calculate the first dry weight. If a sacrificial layer is present, the sacrificial layer is removed before measuring the weight and size. Second, after applying and drying the layer under consideration, a second sample of the same size is cut from the material, and the weight and size are measured to calculate the second dry weight. If a sacrificial layer is present, the sacrificial layer is removed before measuring the weight and size. Third, the first dry weight is subtracted from the second dry weight to obtain the dry weight of the layer under consideration. All weight and size measurements are performed at the same humidity level, which is typically the humidity level of the manufacturing environment in which the material is prepared. In order to calculate the dry weight, three separate dry weight tests are performed, and the average dry weight is reported as the dry weight of the layer.
[0226] In some embodiments, the protein polyurethane alloy layer 1820 may be a non-foamed layer. A "non-foamed" layer refers to a layer having a density of 5% or less, such as 0% void space to 5% void space, measured as a void space percentage of the layer. In some embodiments, the protein polyurethane alloy layer 1820 may be a foamed layer. In such embodiments, the density of the protein polyurethane alloy layer 1820, measured as a void space percentage of the layer 1820, may be in the range of about 5% void space to about 70% void space, including sub-ranges. For example, the protein polyurethane alloy layer 1820 may have about 5% void space, about 10% void space, about 20% void space, about 30% void space, about 35% void space, about 40% void space, about 45% void space, about 50% void space, about 55% void space, about 60% void space, about 65% void space, or about 70% void space, or within a range having any two of these values as endpoints, including the endpoints. In some embodiments, the void space percentage of the protein polyurethane alloy layer 1820 may be in the range of about 10% to about 65%, about 20% to about 60%, about 30% to about 55%, about 35% to about 50%, or about 40% to about 45%.
[0227] The void space percentage (which may also be referred to as "porosity percentage") can be measured by image analysis of a cross section of the layer or by measuring the bulk density of a sample of the layer using a pycnometer. Unless otherwise specified, the void space percentage reported herein is measured by image analysis of a cross section of the layer. The image is analyzed using ImageJ software (or equivalent software) at 37 times magnification. ImageJ software uses a trainable Weka segmentation classifier to calculate the void space percentage in the layer. In order to calculate the void space percentage, three to five separate cross-sectional images are evaluated, and the average void space percentage is reported as the void space percentage of the layer. In some embodiments, protein polyurethane alloy layer 1820 may include one or more blowing agents and / or foam stabilizers. Suitable blowing agents and foam stabilizers include those discussed herein for layers 1830 and 1840.
[0228] In some embodiments, the layered material 1800 may include a protein polyurethane alloy layer 1820 attached to the top surface 1714 of the base layer 1710. In some embodiments, the bottom surface 1822 of the protein polyurethane alloy layer 1820 may be in direct contact with the top surface 1714 of the base layer 1710. In some embodiments, the bottom surface 1822 of the protein polyurethane alloy layer 1820 may be attached to the top surface 1714 of the base layer 1710 via an adhesive layer (e.g., adhesive layer 1850). In some embodiments, the layered material 1800 may include a protein polyurethane alloy layer 1820 attached to the bottom surface 1712 of the base layer 1710. In some embodiments, the top surface 1824 of the protein polyurethane alloy layer 1820 may be in direct contact with the bottom surface 1712 of the base layer 1710. In some embodiments, the top surface 1824 of the protein polyurethane alloy layer 1820 may be attached to the bottom surface 1712 of the base layer 1710 via an adhesive layer (e.g., adhesive layer 1850). In some embodiments, the layered material 1800 may include a protein polyurethane alloy layer 1820 attached to the top surface 1714 of the base layer 1710 and a protein polyurethane alloy layer 1820 attached to the bottom surface 1712 of the base layer 1710. In such embodiments, the layered material 1800 includes the protein polyurethane alloy layers 1820 disposed on opposite surfaces of the base layer 1710.
[0229] In some embodiments, such as for example Fig.18BAs shown, the layered material 1800 may include a second protein polyurethane alloy layer 1830 disposed between the protein polyurethane alloy layer 1820 and the base layer 1710. In such embodiments, the second protein polyurethane alloy layer 1830 is attached to the protein polyurethane alloy layer 1820. In some embodiments, the bottom surface 1822 of the protein polyurethane alloy layer 1820 may be in direct contact with the top surface 1834 of the second protein polyurethane alloy layer 1830.
[0230] Second protein polyurethane alloy layer 1830 includes a bottom surface 1832, a top surface 1834, and a thickness 1836 measured between bottom surface 1832 and top surface 1834. In some embodiments, thickness 1836 can be in the range of about 25 microns to about 600 microns, including subranges. For example, thickness 1836 can be about 25 microns, about 50 microns, about 100 microns, about 125 microns, about 150 microns, about 175 microns, about 200 microns, about 225 microns, about 250 microns, about 275 microns, about 300 microns, about 400 microns, about 500 microns, or about 600 microns, or in a range having any two of these values as endpoints, including the endpoints. In some embodiments, thickness 1836 can be in a range of about 50 microns to about 500 microns, about 75 microns to about 400 microns, about 100 microns to about 300 microns, about 125 microns to about 275 microns, about 150 microns to about 250 microns, about 175 microns to about 225 microns, or about 200 microns to about 225 microns. In some embodiments, thickness 1836 can be greater than thickness 1826. In some embodiments, thickness 1836 can be less than thickness 1826. In some embodiments, thickness 1836 can be greater or less than thickness 1826 by 5 microns or more.
[0231] The second protein polyurethane alloy layer 1830 may have a g / m2 (g / m 2 ) is measured in units of about 30g / m 2 About 600g / m 2 For example, the dry weight of the second protein polyurethane alloy layer 1830 may be about 30 g / m 2 , about 40g / m 2 , about 60g / m 2 , about 80g / m 2 , about 100g / m 2 , about 120g / m 2 , about 140g / m 2 , about 150g / m 2 , about 200g / m 2 , about 300g / m 2 , about 400g / m 2, about 500g / m 2 or about 600g / m 2 , or within a range having any two of these values as endpoints, including the endpoints. In some embodiments, the dry weight of the second protein polyurethane alloy layer 1830 may be about 40 g / m 2 About 500g / m 2 , about 60g / m 2 About 400g / m 2 , about 80g / m 2 About 300g / m 2 , about 100g / m 2 About 200g / m 2 , about 120g / m 2 About 150g / m 2 or about 140g / m 2 About 150g / m 2 In some embodiments, the protein polyurethane alloy layer 1820 may have a first weight, and the second protein polyurethane alloy layer 1830 may have a second weight, and the first weight may be less than the second weight. In some embodiments, the first weight may be less than the second weight by 5 g / m 2 or more.
[0232] In some embodiments, the second protein polyurethane alloy layer 1830 may include a foaming agent. In some embodiments, the second protein polyurethane alloy layer 1830 may include a foam stabilizer. The foaming agent or foam stabilizer may facilitate the formation of voids in the second protein polyurethane alloy layer 1830 during blending of the second protein polyurethane alloy layer 1830. Suitable foam stabilizers include, but are not limited to 0520 (a surfactant available from Unichem Specialty Chemicals, LLC) or HeiQ Chemtex 2216-T (a stable blend of nonionic and anionic surfactants), HeiQ Chemtex 2241-A (modified HEUR (hydrophobically modified ethylene oxide urethane) thickener), HeiQ Chemtex 2243 (a nonionic silicone dispersion), or HeiQ Chemtex 2317 (a stable blend of nonionic and anionic surfactants) foam stabilizer available from HeiQ Chemtex. When used, the foam stabilizer is used to stabilize mechanically generated foam (air gaps). Mechanically generated foam can be generated, for example, by a rotor and / or compressed air. When used, the blowing agent can generate foam (air gaps) within the layer by chemical reaction and / or via heat generation in the layer.
[0233] In some embodiments, the second protein polyurethane alloy layer 1830 may be referred to as a “foamed protein polyurethane alloy layer” because (i) layer 1830 includes one or more foaming agents or foam stabilizers and / or (ii) layer 1830 includes a density less than that of protein polyurethane alloy layer 1820 .
[0234] The density of the second protein polyurethane alloy layer 1830 can be in the range of about 5% void space to about 70% void space, including subranges, measured as a void space percentage of the layer 1830. For example, the second protein polyurethane alloy layer 1830 can have about 5% void space, about 10% void space, about 20% void space, about 30% void space, about 35% void space, about 40% void space, about 45% void space, about 50% void space, about 55% void space, about 60% void space, about 65% void space, or about 70% void space, or within a range having any two of these values as endpoints, inclusive. In some embodiments, the void space percentage of the second protein polyurethane alloy layer 1830 may be in a range of about 10% to about 65%, about 20% to about 60%, about 30% to about 55%, about 35% to about 50%, or about 40% to about 45%. In some embodiments, the protein polyurethane alloy layer 1820 may have a first density and the second protein polyurethane alloy layer 1830 may have a second density, and the first density may be greater than the second density. In some embodiments, the first density may have 5% or more void space greater than the second density.
[0235] Layering a plurality of protein polyurethane alloy layers with different weights and / or densities can be used to customize the material properties of a layered material. For example, a layer with a lighter weight and / or density can be used to increase the softness and / or flexibility of a layered material. On the other hand, a layer with a high weight and / or density can increase the strength of a layered material. In addition, using one or more layers with a relatively lighter weight and / or density can increase the ease with which cutting, stitching and / or forming process steps (e.g., scraping) can be performed on a layered material. Layering a plurality of protein polyurethane alloy layers provides a great degree of freedom in the design of the material.
[0236] In some embodiments, the second protein polyurethane alloy layer 1830 may further include, for example, a foaming agent, a foam stabilizer, or one or more colorants, in addition to any other components that may be present. The type and amount of colorant used in the second protein polyurethane alloy layer 1830 may be any type and amount described herein for the protein polyurethane alloy layer 1820. In some embodiments, the second protein polyurethane alloy layer 1830 may be free of or substantially free of colorants.
[0237] In some embodiments, such as for example Fig.18B As shown, the layered material 1800 may include a third protein polyurethane alloy layer 1840 disposed between the second protein polyurethane alloy layer 1830 and the base layer 1710. In such embodiments, the third protein polyurethane alloy layer 1840 is attached to the second protein polyurethane alloy layer 1830. In some embodiments, the bottom surface 1832 of the second protein polyurethane alloy layer 1830 may be in direct contact with the top surface 1844 of the third protein polyurethane alloy layer 1840.
[0238] The third protein polyurethane alloy layer 1840 includes a bottom surface 1842, a top surface 1844, and a thickness 1846 measured between the bottom surface 1842 and the top surface 1844. In some embodiments, the thickness 1846 can be in the range of about 25 microns to about 600 microns, including subranges. For example, the thickness 1846 can be about 25 microns, about 50 microns, about 100 microns, about 125 microns, about 150 microns, about 175 microns, about 200 microns, about 225 microns, about 250 microns, about 275 microns, about 300 microns, about 400 microns, about 500 microns, or about 600 microns, or in a range having any two of these values as endpoints, including the endpoints. In some embodiments, thickness 1846 may be in a range of about 50 microns to about 500 microns, about 75 microns to about 400 microns, about 100 microns to about 300 microns, about 125 microns to about 275 microns, about 150 microns to about 250 microns, about 175 microns to about 225 microns, or about 175 microns to about 200 microns. In some embodiments, thickness 1846 may be greater than thickness 1826. In some embodiments, thickness 1846 may be less than thickness 1826. In some embodiments, thickness 1846 may be greater or less than thickness 1826 by 5 microns or more. In some embodiments, thickness 1846 may be the same as thickness 1836. In some embodiments, thickness 1846 may be greater or less than thickness 1836. In some embodiments, thickness 1846 may be greater or less than thickness 1836 by 5 microns or more.
[0239] The third protein polyurethane alloy layer 1840 may have a g / m2 (g / m 2 ) is measured in units of about 30g / m 2 About 600g / m 2 For example, the dry weight of the third protein polyurethane alloy layer 1840 may be about 30 g / m 2 , about 40g / m 2 , about 60g / m 2 , about 80g / m 2 , about 100g / m 2 , about 120g / m 2, about 140g / m 2 , about 150g / m 2 , about 200g / m 2 , about 300g / m 2 , about 400g / m 2 , about 500g / m 2 or about 600g / m 2 , or within a range having any two of these values as endpoints, including the endpoints. In some embodiments, the dry weight of the third protein polyurethane alloy layer 1840 may be about 40 g / m 2 About 500g / m 2 , about 60g / m 2 About 400g / m 2 , about 80g / m 2 About 300g / m 2 , about 100g / m 2 About 200g / m 2 , about 120g / m 2 About 150g / m 2 or about 120g / m 2 About 140g / m 2 In some embodiments, the protein polyurethane alloy layer 1820 may have a first weight, and the third protein polyurethane alloy layer 1840 may have a third weight, and the first weight may be less than the third weight. In some embodiments, the protein polyurethane alloy layer 1820 may have a first weight, the second protein polyurethane alloy layer 1830 may have a second weight, and the third protein polyurethane alloy layer 1840 may have a third weight, and the first weight may be less than the second weight and the third weight. In some embodiments, the first weight may be 5 g / m less than the second weight and / or the third weight. 2 or more.
[0240] In some embodiments, the third protein polyurethane alloy layer 1840 may include a foaming agent. In some embodiments, the third protein polyurethane alloy layer 1840 may include a foam stabilizer. The foaming agent and / or the foam stabilizer may facilitate the formation of voids in the third protein polyurethane alloy layer 1840 during blending of the third protein polyurethane alloy layer 1840. Suitable foaming agents include, but are not limited to 0520 (a surfactant available from Unichem Specialty Chemicals, LLC) or HeiQ Chemtex 2216-T (a stable blend of nonionic and anionic surfactants), HeiQ Chemtex 2241-A (modified HEUR (hydrophobically modified ethylene oxide urethane) thickener), HeiQ Chemtex 2243 (a nonionic silicone dispersion) or HeiQ Chemtex 2317 (a stable blend of nonionic and anionic surfactants) foam stabilizers available from HeiQ Chemtex.
[0241] In some embodiments, the third protein polyurethane alloy layer 1840 may be referred to as a “foamed protein polyurethane alloy layer” because (i) layer 1840 includes one or more foaming agents or foam stabilizers and / or (ii) layer 1840 includes a density less than that of protein polyurethane alloy layer 1820 .
[0242] The density of the third protein polyurethane alloy layer 1840 can be in the range of about 5% void space to about 70% void space, including subranges, measured as a void space percentage of the layer 1840. For example, the third protein polyurethane alloy layer 1840 can have about 5% void space, about 10% void space, about 20% void space, about 30% void space, about 35% void space, about 40% void space, about 45% void space, about 50% void space, about 55% void space, about 60% void space, about 65% void space, or about 70% void space, or within a range having any two of these values as endpoints, inclusive. In some embodiments, the void space percentage of the third protein polyurethane alloy layer 1840 may be in the range of about 10% to about 65%, about 20% to about 60%, about 30% to about 55%, about 35% to about 50%, or about 40% to about 45%. In some embodiments, the protein polyurethane alloy layer 1820 may have a first density, and the third protein polyurethane alloy layer 1840 may have a third density, and the first density may be greater than the third density. In some embodiments, the protein polyurethane alloy layer 1820 may have a first density, the second protein polyurethane alloy layer 1830 may have a second density, and the third protein polyurethane alloy layer 1840 may have a third density, and the first density may be greater than the second density and the third density. In some embodiments, the first density may have a void space greater than the second density and / or the third density by 5% or more.
[0243] In some embodiments, the layered material 1800 can include multiple protein-polyurethane alloy layers having the same protein and polyurethane. In some embodiments, the layered material 1800 can include multiple protein-polyurethane alloy layers, and different layers can have different proteins and / or different polyurethanes.
[0244] In some embodiments, the third protein polyurethane alloy layer 1840 may also include, in addition to any other components that may be present, such as a foaming agent, a foam stabilizer, and one or more colorants. The type and amount of colorant used in the third protein polyurethane alloy layer 1840 can be any type and amount described herein for the protein polyurethane alloy layer 1820. In some embodiments, the third protein polyurethane alloy layer 1840 may be free of or substantially free of colorants.
[0245] In some embodiments, and as e.g. Fig.18B As shown, the layered material 1800 may include a primer layer 1860. The primer layer 1860 may be disposed on a top surface 1824 of the protein polyurethane alloy layer 1820. The primer layer 1860 may be directly or indirectly attached to the protein polyurethane alloy layer 1820. In some embodiments, the primer layer 1860 may be disposed on the top surface 1824 of the protein polyurethane alloy layer 1820. In some embodiments, the bottom surface 1862 of the primer layer 1860 may be in direct contact with the top surface 1824 of the protein polyurethane alloy layer 1820.
[0246] Primer 1860 includes a bottom surface 1862, a top surface 1864, and a thickness 1866 measured between bottom surface 1862 and top surface 1864. In some embodiments, thickness 1866 may be in the range of about 20 microns to about 200 microns, including sub-ranges. For example, thickness 1866 may be about 20 microns, about 30 microns, about 40 microns, about 50 microns, about 60 microns, about 70 microns, about 80 microns, about 90 microns, about 100 microns, about 150 microns, or about 200 microns, or in a range with any two of these values as endpoints, including endpoints. In some embodiments, thickness 1866 may be in the range of about 30 microns to about 150 microns, about 40 microns to about 100 microns, about 50 microns to about 90 microns, about 60 microns to about 80 microns, or about 60 microns to about 70 microns.
[0247] In the embodiment including the primer 1860, the primer 1860 can provide one or more of the following properties for the layered material 1800: (i) abrasion resistance, color fastness or hydrolysis resistance. In the embodiment including the top coat, the primer 1860 can also be used to adhere the top coat to the layered material 1800. In some embodiments, the primer 1860 can include one or more polymer materials. Suitable materials for the primer 1860 include, but are not limited to, polyether polyurethane, polycarbonate polyurethane, polyester polyurethane, acrylic polymers and crosslinking agents such as isocyanate or carbodiimide. In some embodiments, the layered material 1800 can include a plurality of primers 1860. In some embodiments, the primer 1860 may not be present in the layered material 1800.
[0248] The base coat 1860 may have a g / m2 2 ) is measured in units of about 20g / m 2 About 100g / m 2 For example, the dry weight of the base coating 1860 may be about 20 g / m 2 , about 30g / m 2 , about 40g / m 2 , about 50g / m 2 , about 60g / m 2 , about 70g / m 2 , about 80g / m 2 , about 90g / m 2 or about 100g / m 2 , or within a range having any two of these values as endpoints, including the endpoints. In some embodiments, the dry weight of the primer layer 1860 may be about 30 g / m 2 About 90g / m 2 , about 40g / m 2 About 80g / m 2 or about 50g / m 2 About 70g / m 2 within the range.
[0249] In some embodiments, such as for example Fig.18BAs shown, the layered material 1800 may include a top coating 1870. The top coating 1870 may be disposed on a top surface 1824 of the protein polyurethane alloy layer 1820. The top coating 1870 may be directly or indirectly attached to the protein polyurethane alloy layer 1820. In some embodiments, a bottom surface 1872 of the top coating 1870 may be in direct contact with the top surface 1824 of the protein polyurethane alloy layer 1820. In embodiments including a bottom coating 1860, the top coating 1870 may be disposed on a top surface 1864 of the bottom coating 1860. In some embodiments, the top coating 1870 may be disposed on a top surface 1864 of the bottom coating 1860. In some embodiments, a bottom surface 1872 of the top coating 1870 may be in direct contact with the top surface 1864 of the bottom coating 1860.
[0250] Top coating 1870 includes bottom surface 1872, top surface 1874, and thickness 1876 measured between bottom surface 1872 and top surface 1874. In some embodiments, thickness 1876 may be in the range of about 10 microns to about 80 microns, including sub-ranges. For example, thickness 1876 may be about 10 microns, about 20 microns, about 30 microns, about 40 microns, about 50 microns, about 60 microns, about 70 microns, or about 80 microns, or in a range having any two of these values as endpoints, including endpoints. In some embodiments, thickness 1776 may be in the range of about 20 microns to about 70 microns, about 30 microns to about 60 microns, or about 30 microns to about 50 microns.
[0251] In embodiments including a topcoat 1870, the topcoat 1870 may provide one or more of the following properties to the layered material 1800: surface feel, stain resistance, flame retardancy, gloss or color appearance. In some embodiments, the topcoat 1870 may include one or more polymeric materials. Suitable materials for the topcoat 1870 include, but are not limited to, polyurethane, acrylic resins, silicone-based feel agents, matte agents, and gloss agents. In some embodiments, the layered material 1800 may include a plurality of topcoats 1870. In some embodiments, the topcoat 1870 may not be present in the layered material 1800. In some embodiments, the topcoat 1870 may be transparent or translucent. In some embodiments, the topcoat 1870 may include one or more dyes, one or more pigments, and / or one or more reflective agents to affect the appearance.
[0252] The top coating 1870 may have a g / m2 2 ) is measured in units of about 10g / m 2 About 80g / m 2 For example, the dry weight of top coating 1870 may be about 10 g / m 2, about 20g / m 2 , about 30g / m 2 , about 40g / m 2 , about 50g / m 2 , about 60g / m 2 , about 70g / m 2 or about 80g / m 2 , or within a range having any two of these values as endpoints, including the endpoints. In some embodiments, the dry weight of the top coating 1870 can be about 20 g / m 2 About 70g / m 2 , about 30g / m 2 About 60g / m 2 or about 30g / m 2 About 50g / m 2 within the range.
[0253] The protein polyurethane alloy layers 1820, 1830, 1840, the bottom coating 1860 and / or the top coating 1870 together can define a layered assembly 1880 of the layered material 1800. The layered assembly 1880 can include any number of protein polyurethane alloy layers as described herein. For example, the layered assembly 1880 can include 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20 protein polyurethane alloy layers. In some embodiments, the layered material 1800 can include a layered assembly 1880 attached to the bottom surface 1712 of the substrate layer 1710. The layered assembly 1880 attached to the bottom surface 1712 of the substrate layer 1710 can include any layer and material of the layered assembly 1880 for attaching to the top surface 1714 of the substrate layer 1710 as described herein. In some embodiments, the layered material 1700 can include a layered component 1880 attached to the top surface 1714 of the base layer 1710 and a layered component 1880 attached to the bottom surface 1712 of the base layer 1710. In such embodiments, the layered material 1800 includes a layered component 1880 disposed on opposing surfaces 1712 and 1714 of the base layer 1710.
[0254] In some embodiments, the protein polyurethane alloy layer of the layered material 1800 is attached to the surface of the substrate 1710 by an adhesive layer 1850. In such embodiments, the adhesive layer 1850 includes a bottom surface 1952, a top surface 1854, and a thickness 1856 measured between the bottom surface 1852 and the top surface 1854. In some embodiments, the thickness 1856 can be in the range of about 10 microns to about 50 microns, including sub-ranges. For example, the thickness 1856 can be about 10 microns, about 20 microns, about 30 microns, about 40 microns, or about 50 microns, or in the range of having any two of these values as endpoints, including endpoints. In some embodiments, the thickness 1856 can be in the range of about 20 microns to about 40 microns. Suitable adhesives for the adhesive layer 1850 include, but are not limited to, polyurethane adhesives, hot melt adhesives, emulsion polymer adhesives, dry web adhesives, dry laminating adhesives, or wet laminating adhesives. Hauthane HD-2001 available from CL Hauthaway & Sons Corporation is an exemplary laminating adhesive suitable for adhesive layer 1850. Exemplary polyurethane adhesives include, but are not limited to, L-2183, L-2245, L-2255 available from Hauthaway and L-2265 available from Covestro. DAH, DAA. Exemplary dry web adhesives include, but are not limited to, 9D8D20 from Protechnic. In some embodiments, layered material 1800 does not include adhesive layer 1850 .
[0255] The adhesive layer 1850 may have a g / m2 (g / m 2 ) is measured in units of about 10g / m 2 About 50g / m 2 For example, the dry weight of adhesive layer 1850 may be about 10 g / m 2 , about 20g / m 2 , about 30g / m 2 , about 40g / m 2 or about 50g / m 2 , or within a range of any two of these values as endpoints, including the endpoints. In some embodiments, the dry weight of adhesive layer 1850 can be about 20 g / m 2 About 40g / m 2 within the range.
[0256] The layered material 1800 can be prepared by attaching one or more protein polyurethane alloy layers described herein and one or more primers and / or top coats to a substrate layer 1710. In some embodiments, the layer may be subsequently layered on the surface of the substrate layer. The layer may be attached to the top surface 1714 and / or the bottom surface 1712 of the substrate layer 1710. In some embodiments, the layer may be layered on a sacrificial layer that is removed after layering and before or after one or more layers are attached to the substrate layer 1710. Each protein polyurethane alloy layer of the layered material may be deposited using any suitable coating technique, including but not limited to knife roll coating, gravure coating, slot die coating, multilayer slot die coating, or curtain coating. Multilayer slot die coating may allow for simultaneous coating of multiple adjacent layers.
[0257] In some embodiments, the base layer 1710 may be coated with an adhesive layer 1850, and additional layers (e.g., layers 1820, 1830, 1840, 1860, and / or 1870) may be formed on the adhesive layer 1850 in any appropriate order. In such embodiments, the layers may be formed on the adhesive layer 1850 in the same manner as described below for method 1900, wherein the layers are formed on the adhesive layer 1850 instead of the sacrificial layer. In some embodiments, the blended mixture as described herein may be applied directly to the surface of the base layer 1710 using, for example, a coating or casting process. In such embodiments, the blended mixture may penetrate at least a portion of the base layer 1710. After application, the blended mixture may be dried to form a protein polyurethane alloy layer (e.g., layer 1820). In some embodiments, after drying, the protein polyurethane alloy layer and the base layer 1710 may be heated (e.g., hot pressed) to help attach the layers together. Other layers (e.g., layers 1830, 1840, 1860, and / or 1870) may be applied over the protein polyurethane alloy layer in any suitable order, either before or after drying and / or before or after attaching the protein polyurethane alloy layer and the base layer 1710. In such embodiments, the other layers may be formed over the protein polyurethane alloy layer in the same manner as described below for method 1900, where the layers are formed over the protein polyurethane alloy layer rather than a sacrificial layer.
[0258] In some embodiments, a decorative layer can be applied between layers of layered material during the manufacturing process. For example, a logo, artistic pattern, picture, or symbol can be applied to a first layer before another layer is disposed on the first layer. The decorative layer can be applied using, for example, screen printing, digital printing, or transfer printing.
[0259] The protein polyurethane alloys described herein can be prepared by blending one or more proteins and one or more polyurethanes in an aqueous protein polyurethane formulation and drying the formulation. In some embodiments, the protein can be dissolved in the polyurethane of the polyurethane dispersion. In some embodiments, the formulation can include water, one or more polyurethanes, one or more proteins, and one or more additives.
[0260] In order to prepare an aqueous protein polyurethane formulation, one or more polyurethanes dispersed or dissolved in an aqueous solution can be blended with one or more proteins to form a blended mixture in an aqueous solution. In some embodiments, the one or more polymers can be dispersed or dissolved in an aqueous solution before blending with the protein. In some embodiments, the one or more polyurethanes can be dispersed or dissolved in an aqueous solution during blending with the protein. In some embodiments, the one or more polyurethanes and the one or more proteins can be blended in a suitable container until a homogenized blend is formed. Suitable blending equipment includes, but is not limited to, a blender, a vertical mixer, an online mixer, or a high shear mixer.
[0261] In some embodiments, the protein may be dispersed or dissolved in an aqueous solution before mixing with one or more polyurethanes. Suitable aqueous solutions include, but are not limited to, water, aqueous alkali solutions, aqueous acid solutions, aqueous solutions including organic solvents, urea solutions, and mixtures thereof. In some embodiments, the aqueous alkali solution may be an alkaline solution, such as sodium hydroxide, ammonia, or ammonium hydroxide solution. In some embodiments, an example of an aqueous acid solution may be acetic acid or hydrochloric acid (HCl) solution. Suitable organic solvents include, but are not limited to, ethanol, isopropanol, acetone, ethyl acetate, isopropyl acetate, glycerol, and the like. In some embodiments, the protein concentration in the aqueous protein polyurethane formulation may be in the range of about 10 g / L to about 300 g / L, including sub-ranges. For example, the protein concentration can range from about 10 g / L to about 300 g / L, about 20 g / L to about 250 g / L, about 30 g / L to about 200 g / L, about 40 g / L to about 150 g / L, about 50 g / L to about 100 g / L, about 60 g / L to about 90 g / L, or about 70 g / L to about 80 g / L.
[0262] In some embodiments, the amount of protein in the aqueous protein polyurethane formulation can be in the range of about 5% to about 90% by weight, including subranges, based on the weight of the protein and the polyurethane. For example, in some embodiments, the amount of protein in the formulation can be in the range of about 5% to about 90% by weight, about 10% to about 90% by weight, about 15% to about 90% by weight, about 20% to about 90% by weight, about 30% to about 90% by weight, about 40% to about 90% by weight, about 50% to about 90% by weight, about 60% to about 90% by weight, about 70% to about 90% by weight, about 5% to about 85% by weight, about 5% to about 80% by weight, about 5% to about 70% by weight, about 5% to about 60% by weight, about 5% to about 50% by weight, about 5% to about 40% by weight, about 5% to about 30% by weight, or about 5% to about 20% by weight, or in the range having any two of these values as endpoints, including the endpoints. In some embodiments, the amount of protein in the formulation may range from about 20% to about 40% by weight.
[0263] Based on the weight of protein and polyurethane, the amount of polyurethane in the aqueous protein polyurethane formulation can be in the range of about 10 wt % to about 95 wt %, including sub-ranges. For example, in some embodiments, the amount of polyurethane in the formulation can be in the range of about 10 wt % to about 95 wt %, about 10 wt % to about 90 wt %, about 10 wt % to about 85 wt %, about 10 wt % to about 80 wt %, about 10 wt % to about 70 wt %, about 10 wt % to about 60 wt %, about 10 wt % to about 50 wt %, about 10 wt % to about 40 wt %, about 10 wt % to about 30 wt %, about 20 wt % to about 95 wt %, about 30 wt % to about 95 wt %, about 40 wt % to about 95 wt %, about 50 wt % to about 95 wt %, about 60 wt % to about 95 wt %, about 70 wt % to about 95 wt %, or about 80 wt % to about 95 wt %, or in the range with any two of these values as endpoints, including the endpoints.
[0264] In some embodiments, the blending temperature can be in the range of about room temperature (18° C.) to about 100° C., including subranges. For example, the blending temperature can be in the range of about 18° C. to about 90° C., about 18° C. to about 80° C., about 18° C. to about 70° C., about 18° C. to about 60° C., about 18° C. to about 50° C., about 18° C. to about 40° C., or about 18° C. to about 30° C.
[0265] In some embodiments, the protein polyurethane formulation may include one or more additives. The additives may affect the final properties of the protein polyurethane alloy and, therefore, the final properties of the material. For example, the added additives may affect one or more of the following material properties: stiffness, elasticity, cohesive strength, tear strength, flame retardancy, chemical stability, or wetting stability. Suitable additives include, but are not limited to, cross-linking agents, fillers, dyes, pigments, plasticizers, waxes, rheology modifiers, flame retardants, antimicrobial agents, antifungal agents, antioxidants, UV stabilizers, mechanical foaming agents, chemical foaming agents, foam stabilizers, and the like. Suitable dyes include, but are not limited to, fiber-reactive dyes or natural dyes. Suitable cross-linking agents include, but are not limited to, epoxy cross-linking agents (e.g., poly(ethylene glycol) diglycidyl ether (PEGDE) purchased from Sigma Aldrich), isocyanate cross-linking agents (e.g., ) and carbodiimide-based crosslinkers (e.g., XR-5577 (a carbodiimide-based crosslinker available from Stahl). Suitable blowing agents include 0520 (a surfactant available from Unichem Specialty Chemicals, LLC) or HeiQChemtex 2216-T (a stable blend of nonionic and anionic surfactants), HeiQ Chemtex 2241-A (modified HEUR (hydrophobically modified ethylene oxide urethane) thickener), HeiQ Chemtex 2243 (a nonionic silicone dispersion), or HeiQ Chemtex 2317 (a stable blend of nonionic and anionic surfactants) foam stabilizers available from HeiQ Chemtex. Suitable antimicrobial / antifungal agents include Ultra-Fresh DW-56, or other antimicrobial / antifungal agents used in the leather industry. Suitable flame retardants include DB9 (organic phosphorus compound with carbon chain polymer containing C-PO(OH)2 or C-PO(OR)2 group), PD3300 (organic phosphorus compound with carbon chain polymer containing C-PO(OH)2 or C-PO(OR)2 groups) or other flame retardants for coated textiles. Suitable fillers include but are not limited to thermoplastic microspheres, such as Suitable rheology modifiers include, but are not limited to, alkali-swellable rheology modifiers, hydrophobically modified ethylene oxide urethane (HEUR) rheology modifiers, and volume exclusion thickeners. Exemplary alkali-swellable rheology modifiers include, but are not limited to, ACRYSOL from Dow Chemicals. TM DR-106, ACRYSOL TMASE-60, available from Scott-Bader 13-3131 and 13-308. Exemplary HEUR modifiers include, but are not limited to, RM-4410 from Stahl and Chemtex 2241-A from HeiQ. Exemplary size exclusion thickeners include, but are not limited to, WALOCEL from Dow Chemicals. TM XM 20000PV and methyl hydroxyethyl cellulose were obtained from Sigma-Aldrich.
[0266] In some embodiments, the crosslinking agent may be a crosslinking agent selected from the group consisting of an epoxy-based crosslinking agent, an isocyanate-based crosslinking agent, and a carbodiimide-based crosslinking agent. In some embodiments, the crosslinking agent may be a carbodiimide-based crosslinking agent.
[0267] In some embodiments, the preparation may include one or more colorants. In some embodiments, the colorant may be a colored dye, such as a fiber reactive dye, a direct dye, an acid dye or a natural dye. Exemplary dyes include but are not limited to azo structure acid dyes, metal complex structure acid dyes, anthraquinone structure acid dyes, azo / diazo direct dyes, sulfur dyes and vat dyes. In some embodiments, the colorant may be a pigment, such as a lake pigment.
[0268] In some embodiments, preparation can comprise one or more colored dyes of about 4 % by weight to about 10 % by weight, including sub-range.For example, in some embodiments, the concentration of one or more colored dyes can be in the scope of about 4 % by weight to about 10 % by weight, about 5 % by weight to about 10 % by weight, about 6 % by weight to about 10 % by weight, about 7 % by weight to about 10 % by weight, about 4 % by weight to about 9 % by weight, about 4 % by weight to about 8 % by weight or about 4 % by weight to about 7 % by weight in preparation, or in the scope of any two as endpoints with these values, including endpoints.In some embodiments, preparation can comprise one or more colored dyes of about 0.5 % by weight to about 8 % by weight.
[0269] In some embodiments, preparation can comprise about 100 % by weight to about 250 % by weight of one or more colored dyes, and the % by weight of the one or more colored dyes is measured relative to the weight of the protein in the preparation. In some embodiments, the one or more colored dyes can include two kinds of colored dyes. In some embodiments, the one or more colored dyes can include three kinds of colored dyes. In some embodiments, the one or more colored dyes can include four kinds of colored dyes.
[0270] In some embodiments, the formulation may include from about 100% to about 250% by weight of one or more colored dyes, from about 100% to about 245% by weight of one or more colored dyes, from about 100% to about 240% by weight of one or more colored dyes, from about 100% to about 235% by weight of one or more colored dyes, from about 100% to about 230% by weight of one or more colored dyes, from about 100% to about 225% by weight of one or more colored dyes, from about 100% to about 220% by weight of one or more colored dyes, from about 100% to about 215% by weight of one or more colored dyes, and from about 100% to about 225% by weight of one or more colored dyes. % of one or more colored dyes, about 100 wt % to about 170 wt % of one or more colored dyes, about 100 wt % to about 165 wt % of one or more colored dyes, about 100 wt % to about 180 wt % of one or more colored dyes, about 100 wt % to about 190 wt % of one or more colored dyes, about 100 wt % to about 195 wt % of one or more colored dyes, about 100 wt % to about 190 wt % of one or more colored dyes, about 100 wt % to about 185 wt % of one or more colored dyes, about 100 wt % to about 180 wt % of one or more colored dyes, about 100 wt % to about 175 wt % of one or more colored dyes, about 100 wt % to about 170 wt % of one or more colored dyes, about 100 wt % to about 165 wt % of one or more colored dyes, dyes, from about 100 wt % to about 160 wt % of one or more colored dyes, from about 100 wt % to about 155 wt % of one or more colored dyes, from about 100 wt % to about 150 wt % of one or more colored dyes, from about 100 wt % to about 145 wt % of one or more colored dyes, from about 100 wt % to about 140 wt % of one or more colored dyes, from about 100 wt % to about 135 wt % of one or more colored dyes, from about 100 wt % to about 130 wt % of one or more colored dyes, from about 100 wt % to about 125 wt % of one or more colored dyes, from about 100 wt % to about 120 wt % of one or more colored dyes, from 100 wt % to about 115 wt % of one or more colored dyes, % by weight of one or more colored dyes, from about 100 wt % to about 110 wt % of one or more colored dyes, from about 100 wt % to about 105 wt % of one or more colored dyes, from about 105 wt % to about 250 wt % of one or more colored dyes, from about 110 wt % to about 250 wt % of one or more colored dyes, from about 115 wt % to about 250 wt % of one or more colored dyes, from about 120 wt % to about 250 wt % of one or more colored dyes, from about 125 wt % to about 250 wt % of one or more colored dyes, from about 130 wt % to about 250 wt % of one or more colored dyes, from about 135 wt % to about 250 wt % of one or more colored dyes,from about 140 wt % to about 250 wt % of one or more colored dyes, from about 145 wt % to about 250 wt % of one or more colored dyes, from about 150 wt % to about 250 wt % of one or more colored dyes, from about 155 wt % to about 250 wt % of one or more colored dyes, from about 160 wt % to about 250 wt % of one or more colored dyes, from about 165 wt % to about 250 wt % of one or more colored dyes, from about 170 wt % to about 250 wt % of one or more colored dyes, from about 175 wt % to about 250 wt % of one or more colored dyes, from about 180 wt % to about 250 wt % of one or more colored dyes, from about 185 wt % to about 250 wt % of one or more colored dyes, from about 190 wt % to about 250 wt % of one or more colored dyes, from about 195 wt % to about 250 wt % of one or more colored dyes, % of the one or more colored dyes, about 200 wt % to about 250 wt % of the one or more colored dyes, about 205 wt % to about 250 wt % of the one or more colored dyes, about 210 wt % to about 250 wt % of the one or more colored dyes, about 215 wt % to about 250 wt % of the one or more colored dyes, about 220 wt % to about 250 wt % of the one or more colored dyes, about 225 wt % to about 250 wt % of the one or more colored dyes, about 230 wt % to about 250 wt % of the one or more colored dyes, about 235 wt % to about 250 wt % of the one or more colored dyes, about 240 wt % to about 250 wt % of the one or more colored dyes, or about 245 wt % to about 250 wt % of the one or more colored dyes, or within a range having any two of these values as endpoints, inclusive.
[0271] In some embodiments, the protein polyurethane formulation may include a foam stabilizer content of about 0.1% to about 10% by weight. For example, the formulation may include about 0.1% to about 10% by weight, about 1% to about 7.5% by weight, about 2.5% to about 5% by weight, about 0.1% to about 5% by weight, or about 0.1% to about 2.5% by weight of foam stabilizer. Suitable foam stabilizers include, but are not limited to 0520 (a surfactant available from Unichem Specialty Chemicals, LLC) or HeiQ Chemtex 2216-T (a stable blend of nonionic and anionic surfactants), HeiQ Chemtex 2241-A (modified HEUR (hydrophobically modified ethylene oxide urethane) thickener), HeiQ Chemtex 2243 (a nonionic silicone dispersion) or HeiQ Chemtex 2317 (a stable blend of nonionic and anionic surfactants) foam stabilizers available from HeiQ Chemtex.
[0272] In some embodiments, the protein polyurethane formulation may include a crosslinking agent content of about 0.1 wt % to about 10 wt %. For example, the formulation may include a crosslinking agent of about 0.1 wt % to about 10 wt %, about 1 wt % to about 7.5 wt %, about 2.5 wt % to about 5 wt %, about 0.1 wt % to about 5 wt %, or about 0.1 wt % to about 2.5 wt %. In some embodiments, the protein polyurethane formulation may include a crosslinking agent content of about 0.5 wt % to about 10 wt %. In some embodiments, the crosslinking agent weight percentage may be based on the solid weight of the polyurethane in the protein polyurethane formulation.
[0273] In some embodiments, the protein polyurethane formulations may have a pH in the range of about 8 to about 9. In some embodiments, the protein polyurethane formulations may have a pH of about 8. In some embodiments, a base (e.g., sodium hydroxide) may be blended in the formulation to adjust the pH to a desired value.
[0274] In some embodiments, the formulation can be foamed to form a foamed protein polyurethane formulation. The formulation can be foamed using, for example, a mechanical foaming process or a chemical foaming process. Exemplary mechanical foaming equipment includes a Hansa mixer or Foaming machine. Blending and foaming of the preparation can be carried out separately or simultaneously.
[0275] In some embodiments, the liquid density of the foamed protein polyurethane alloy formulation can be in the range of about 300 g / L to about 900 g / L, including subranges, before removing the solvent. For example, in some embodiments, the liquid density of the foamed formulation can be in the range of about 300 g / L to about 1000 g / L, about 300 g / L to about 800 g / L, about 400 g / L to about 600 g / L, about 300 g / L to about 500 g / L, or about 300 g / L to about 600 g / L.
[0276] The protein polyurethane formulation may be applied to the base layer 1710 using any suitable application technique, including but not limited to spraying, dipping, or pouring. In some embodiments, the foamed protein polyurethane formulation may be applied to the base layer 1710 using any suitable application technique, including but not limited to spraying, dipping, or pouring.
[0277] In some embodiments, the temperature of the formulation during application may be about 40°C or higher. For example, the temperature of the formulation may be in the range of about 40°C to about 100°C, including subranges. For example, in some embodiments, the temperature of the formulation during coating may be in the range of about 40°C to about 90°C, about 40°C to about 80°C, about 40°C to about 70°C, about 40°C to about 60°C, or about 40°C to about 50°C.
[0278] After the formulation is applied to the base layer 1710, the solvent (e.g., water) can be removed from the formulation to form the protein polyurethane alloy 1720. Suitable solvent removal methods include, but are not limited to, tunnel drying, vacuum drying, oven drying with hot air, humidity chamber drying, flotation drying with hot air, and ovens with a combination of mid-range IR (infrared) for preheating and hot air for subsequent drying. Suitable solvent removal temperatures may be in the range of about room temperature (18°C) to about 210°C, including sub-ranges. For example, in some embodiments, the solvent may be removed at a temperature in the range of about 18°C to about 35°C, about 18°C to about 50°C, about 18°C to about 75°C, about 18°C to about 100°C, about 18°C to about 150°C, about 18°C to about 200°C, or about 18°C to about 210°C.
[0279] In some embodiments, the layer of laminar material can be formed over the sacrificial layer and attached to the base layer after formation. Fig.19 A method 1900 for preparing a layered material 1800 is shown according to some embodiments. FIG. 20A to FIG. 20F The steps of method 1900 are shown. Unless otherwise specified, the steps of method 1900 need not be performed in the order described herein. In addition, unless otherwise specified, the steps of method 1900 need not be performed in order. The steps can be performed simultaneously. As an example, method 1900 does not need to include a solvent removal step after each individual protein polyurethane alloy layer is deposited; instead, the solvent (e.g., water) from multiple protein polyurethane alloy layers can be removed in a single step. Method 1900 can be used to attach a layer to one or both sides of substrate layer 1710.
[0280] In step 1902, a top coating 1870 may be disposed over a top surface 2002 of a sacrificial layer 2000, such as, for example Fig. 20AAs shown. Any suitable coating technique can be used to arrange the top coating 1870 on the sacrificial layer 2000, for example, by scraping, spraying or roller coating with reverse transfer paper. Sacrificial layer 2000 is a material layer that does not limit the layered material layer 1800. On the contrary, sacrificial layer 2000 is removed during the manufacture of layered material 1800. Sacrificial layer 2000 can be removed mechanically (such as by peeling) or chemically (for example, by dissolving sacrificial layer 2000). In some embodiments, sacrificial layer 2000 can be a release liner. Suitable materials for sacrificial layer 2000 include, but are not limited to, texture release paper. Exemplary texture release paper includes release paper purchased from Sappi paper, such as Matte Freeport 189, Freeport123 or Expresso 904. In some embodiments, method 1900 does not include step 1902. That is, step 1902 is optional. In some embodiments, top coating 1870 can be applied to layered material 1800 after sacrificial layer 2000 is removed in step 1918. In some embodiments, top coating 1870 can be applied to layered material 1800 after the protein polyurethane alloy layer is attached to base layer 1710 in step 1920.
[0281] In step 1904, a primer layer 1860 may be disposed over the sacrificial layer 2000, such as, for example Fig. 20B As shown. In an embodiment including a top coating 1870, a primer 1860 may be disposed on the top coating 1870. The primer 1860 may be disposed on the sacrificial layer 2000 using any suitable coating technique, for example, by scraping, spraying, or rolling with reverse transfer paper. In some embodiments, the method 1900 does not include step 1904. Step 1904 is optional. In some embodiments, the primer 1860 may be applied to the layered material 1800 after the sacrificial layer 2000 is removed in step 1918. In some embodiments, the primer 1860 may be applied to the layered material 1800 after the protein polyurethane alloy layer is attached to the base layer 1710 in step 1920.
[0282] In step 1906, one or more polyurethanes dispersed or dissolved in an aqueous solution may be blended with one or more proteins to form a blended mixture in an aqueous solution. In some embodiments, the one or more polymers may be dispersed or dissolved in an aqueous solution before blending with the protein. In some embodiments, the one or more polyurethanes may be dispersed or dissolved in an aqueous solution during blending with the protein. In some embodiments, the one or more polyurethanes and the one or more proteins may be blended in a suitable container until a homogenized blend is formed. Suitable blending equipment includes, but is not limited to, a blender, a vertical mixer, an in-line mixer, or a high shear mixer.
[0283] In some embodiments, the protein may be dispersed or dissolved in an aqueous solution prior to blending with the polyurethane in step 1906. Suitable aqueous solutions include, but are not limited to, water, aqueous alkali solutions, aqueous acid solutions, aqueous solutions including organic solvents, urea solutions, and mixtures thereof. In some embodiments, the aqueous alkali solution may be an alkaline solution, such as sodium hydroxide, ammonia, or ammonium hydroxide solution. In some embodiments, an example of an aqueous acid solution may be an acetic acid or hydrochloric acid (HCl) solution. Suitable organic solvents include, but are not limited to, ethanol, isopropanol, acetone, ethyl acetate, isopropyl acetate, glycerol, and the like. In some embodiments, the protein concentration in the aqueous protein mixture may be in the range of about 10 g / L to about 300 g / L, including sub-ranges. For example, the protein concentration in the aqueous protein mixture can be about 10 g / L, about 20 g / L, about 30 g / L, about 40 g / L, about 50 g / L, about 60 g / L, about 70 g / L, about 80 g / L, about 90 g / L, about 100 g / L, about 150 g / L, about 200 g / L, about 250 g / L, or about 300 g / L, or in a range having any two of these values as endpoints, including the endpoints. In some embodiments, the protein concentration in the aqueous protein mixture can be in the range of about 10 g / L to about 300 g / L, about 20 g / L to about 250 g / L, about 30 g / L to about 200 g / L, about 40 g / L to about 150 g / L, about 50 g / L to about 100 g / L, about 60 g / L to about 90 g / L, or about 70 g / L to about 80 g / L.
[0284] Based on the weight of protein and polyurethane, the amount of protein in the protein / polyurethane blend can be in the range of about 5 wt % to about 60%, including sub-ranges. For example, the amount of protein in the blend can be about 5 wt %, about 10 wt %, about 15 wt %, about 20 wt %, about 25 wt %, about 30 wt %, about 35 wt %, about 40 wt %, about 45 wt %, about 50 wt %, about 55 wt % or about 60 wt %, or in the range of any two as endpoints with these values. In some embodiments, the amount of protein in the blend can be about 10 wt % to about 55 wt %, about 15 wt % to about 50 wt %, about 20 wt % to about 45 wt %, about 25 wt % to about 40 wt % or about 30 wt % to about 35 wt %. In some embodiments, the amount of protein in the protein / polyurethane blend can be in the range of about 20 wt % to about 40 wt %.
[0285] Based on the weight of protein and polyurethane, the amount of polyurethane in the protein / polyurethane blend can be in the range of about 10 wt % to about 85%, including sub-ranges. For example, the amount of polyurethane in the blend can be about 10 wt %, about 15 wt %, about 20 wt %, about 25 wt %, about 30 wt %, about 35 wt %, about 40 wt %, about 45 wt %, about 50 wt %, about 55 wt %, about 60 wt %, about 65 wt %, about 70 wt %, about 75 wt %, about 80 wt % or about 85 wt %, or in the range of any two as endpoints with these values, including endpoints. In some embodiments, the amount of polyurethane in the blend can be in the range of about 20 wt % to about 75 wt %, about 30 wt % to about 65 wt % or about 40 wt % to about 55 wt %.
[0286] In some embodiments, the blending temperature may be in the range of about room temperature (18°C) to about 100°C, including sub-ranges. For example, the blending temperature may be about 18°C, about 30°C, about 40°C, about 50°C, about 60°C, about 70°C, about 80°C, about 90°C, or about 100°C, or in a range having any two of these values as endpoints, including endpoints. In some embodiments, the blending temperature may be in the range of about 18°C to about 90°C, about 18°C to about 80°C, about 18°C to about 70°C, about 18°C to about 60°C, about 18°C to about 50°C, about 18°C to about 40°C, or about 18°C to about 30°C.
[0287] In some embodiments, the blending time of step 1906 may be in the range of about 15 minutes to about 3 hours, including sub-ranges. For example, the blending time may be about 30 minutes, about 1 hour, about 90 minutes, about 2 hours, about 150 minutes, or about 3 hours, or in the range of any two of these values as endpoints, including endpoints. In some embodiments, the blending time may be in the range of about 15 minutes to about 150 minutes, about 15 minutes to about 2 hours, about 15 minutes to about 90 minutes, or about 15 minutes to about 1 hour. In some embodiments, the blending speed of step 1906 may be in the range of about 150rpm to about 250rpm, including sub-ranges. For example, the blending speed may be about 150rpm, about 175rpm, about 200rpm, about 225rpm, or about 250rpm. In some embodiments, the blending speed may be in the range of about 150rpm to about 225rpm, about 150rpm to about 200rpm, or about 150rpm to about 225rpm. The blending speed may depend on the size of the blending apparatus (eg, the size of the impeller) and / or the size of the container in which the components are blended.
[0288] In some embodiments, one or more additives may be added to the blend in step 1906. The additives may affect the final properties of the protein polyurethane alloy layer, and therefore the final properties of the layered material 1800. For example, the added additives may affect one or more of the following material properties: stiffness, elasticity, cohesive strength, tear strength, flame retardancy, chemical stability, or wetting stability. Suitable additives include, but are not limited to, cross-linking agents, fillers, dyes, pigments, plasticizers, waxes, rheology modifiers, flame retardants, antimicrobial agents, antifungal agents, antioxidants, UV stabilizers, mechanical foaming agents, chemical foaming agents, foam stabilizers, and the like. Suitable dyes include, but are not limited to, fiber-reactive dyes or natural dyes. Suitable cross-linking agents include, but are not limited to, epoxy cross-linking agents (e.g., poly(ethylene glycol) diglycidyl ether (PEGDE) purchased from Sigma Aldrich), isocyanate cross-linking agents (e.g., ) and carbodiimide-based crosslinkers (e.g., XR-5577 (a carbodiimide based crosslinker available from Stahl). Suitable foaming agents include HeiQ Chemtex 2216-T (a stable blend of nonionic and anionic surfactants), HeiQ Chemtex 2241-A (modified HEUR (hydrophobically modified ethylene oxide urethane) thickener), HeiQ Chemtex 2243 (a nonionic silicone dispersion), or HeiQ Chemtex 2317 (a stable blend of nonionic and anionic surfactants) foam stabilizers available from HeiQ Chemtex. Suitable antimicrobial / antifungal agents include Ultra-Fresh DW-56, or other antimicrobial / antifungal agents used in the leather industry. Suitable flame retardants include DB9 (organic phosphorus compound with carbon chain polymer containing C-PO(OH)2 or C-PO(OR)2 group), PD3300 (organic phosphorus compound with carbon chain polymer containing C-PO(OH)2 or C-PO(OR)2 groups) or other flame retardants for coated textiles. Suitable fillers include but are not limited to thermoplastic microspheres, such as Suitable rheology modifiers include, but are not limited to, alkali-swellable rheology modifiers, hydrophobically modified ethylene oxide urethane (HEUR) rheology modifiers, and volume exclusion thickeners. Exemplary alkali-swellable rheology modifiers include, but are not limited to, ACRYSOL from Dow Chemicals. TM DR-106, ACRYSOL TM ASE-60, available from Scott-Bader 13-3131 and 13-308. Exemplary HEUR modifiers include, but are not limited to, RM-4410 from Stahl and Chemtex 2241-A from HeiQ. Exemplary size exclusion thickeners include, but are not limited to, WALOCEL from Dow Chemicals. TM XM 20000PV and methyl hydroxyethyl cellulose were obtained from Sigma-Aldrich.
[0289] In some embodiments, the material 1800 may include from about 0.5 wt % to about 5 wt % of one or more rheology modifiers, the weight percentage being based on the total weight of the material 1800 .
[0290] In some embodiments, the blend may include one or more colorants. In some embodiments, the colorant may be a dye, such as a fiber-reactive dye, a direct dye, an acid dye, or a natural dye. Exemplary dyes include, but are not limited to, azo acid dyes, metal complex structure acid dyes, anthraquinone structure acid dyes, azo / diazo direct dyes, sulfur dyes, and vat dyes. In some embodiments, the colorant may be a pigment, such as a lake pigment. In some embodiments, the blend may include a colorant content of about 2 wt % or less. For example, the blend may include a colorant of about 0.1 wt %, about 0.5 wt %, about 1 wt %, about 1.5 wt %, or about 2 wt %. In some embodiments, the blend may include a colorant of about 0.1 wt % to about 2 wt %, about 0.5 wt % to about 1.5 wt %, or about 0.1 wt % to about 1 wt %. In some embodiments, the blend may be free of or substantially free of a colorant. In such embodiments, the protein polyurethane alloy layer produced by the blend may be free of or substantially free of a colorant.
[0291] In step 1908, a layer of the blended mixture is disposed on the top surface 2002 of the sacrificial layer 2000. The blended mixture may be coated on the top surface 2002 of the sacrificial layer 2000. In embodiments that do not include steps 1902 and 1904, the blended mixture may be directly coated on the top surface 2002 of the sacrificial layer 2000. In embodiments that include step 1904, the blended mixture may be directly coated on the surface of the base coating 1860. In embodiments that include step 1902 but do not include step 1904, the blended mixture may be directly coated on the surface of the top coating 1870. In some embodiments, the blended mixture may be formed into a sheet by coating it on a surface to a desired thickness. Coating may include pouring, extrusion, casting, etc. In some embodiments, the sheet may be spread to a desired thickness using, for example, a paddle, a blade, a roller, a doctor blade roll coating, a curtain coating, and a slot die coating.
[0292] In some embodiments, the temperature of the blended mixture during coating may be about 40°C or higher. For example, the temperature of the blended mixture may be in the range of about 40°C to about 100°C, including sub-ranges. For example, the temperature may be about 40°C, about 50°C, about 60°C, about 70°C, about 80°C, about 90°C, or about 100°C, or in a range with any two of these values as endpoints, including endpoints. In some embodiments, the temperature of the blended mixture during coating may be in the range of about 40°C to about 90°C, about 40°C to about 80°C, about 40°C to about 70°C, about 40°C to about 60°C, or about 40°C to about 50°C. Coating at a temperature below about 40°C may cause the blended mixture to be too viscous and may make it difficult to form a layer of uniform thickness.
[0293] In step 1910, the solvent (e.g., water) may be removed from the coated blended mixture to form a protein polyurethane alloy layer 1820, such as Fig. 20C Suitable solvent removal methods include, but are not limited to, tunnel drying, vacuum drying, oven drying with hot air, humidity chamber drying, flotation drying with hot air, and ovens with a combination of mid-range IR (infrared) for preheating and hot air for subsequent drying.
[0294] Suitable solvent removal temperatures for step 1910 may be in the range of about room temperature (18°C) to about 100°C, including sub-ranges. For example, the solvent may be removed at a temperature of about 18°C, about 35°C, about 50°C, about 60°C, about 70°C, about 80°C, about 90°C, or about 100°C, or in a range (including the endpoints) having any two of these values as endpoints. In some embodiments, the solvent may be removed at a temperature in the range of about 18°C to about 35°C, about 18°C to about 50°C, about 18°C to about 60°C, about 18°C to about 70°C, about 18°C to about 80°C, about 18°C to about 90°C, or about 18°C to about 100°C. Suitable humidity values for solvent removal in step 1910 include humidity in the range of 0% RH (relative humidity) to about 65% RH (including sub-ranges). For example, the humidity may be about 10% RH, about 20% RH, about 40% RH, about 50% RH, or about 65% RH, or within a range having any two of these values as endpoints, including the endpoints. In some embodiments, the humidity may be 0% RH to about 50% RH, 0% RH to about 40% RH, 0% RH to about 20% RH, or 0% RH to about 10% RH. The solvent removal temperature and / or humidity may affect the final properties of the protein polyurethane alloy layer, thereby affecting the final properties of the layered material. The solvent removal temperature and / or humidity in step 1910 may affect one or more of the following material properties: stiffness, elasticity, cohesive strength, tear strength, flame retardancy, chemical stability, and wetting stability. For example, relatively high humidity and relatively low temperature may produce a softer and more elastic material. On the contrary, relatively low humidity and relatively high temperature may produce a harder and less elastic material.
[0295] In some embodiments, steps 1906 to 1910 may be repeated multiple times to form multiple protein polyurethane alloy layers 1820 on the sacrificial layer 2000. In some embodiments, steps 1906 to 1910 may be repeated in sequence to form multiple protein polyurethane alloy layers 1820 on the sacrificial layer 2000. In some embodiments, steps 1906 to 1910 may be repeated after steps 1912 to 1916 to form one or more protein polyurethane alloy layers 1820 on one or more foamed protein polyurethane alloy layers 1830 / 1840. In some embodiments, method 1900 may not include steps 1906 to 1910.
[0296] In step 1912, one or more polyurethanes dispersed or dissolved in an aqueous solution may be blended with a protein and foamed to form a foamed blended mixture in an aqueous solution. In some embodiments, the one or more polymers may be dispersed or dissolved in an aqueous solution before being blended and foamed with the protein. In some embodiments, the one or more polyurethanes may be dispersed or dissolved in an aqueous solution during blending and foaming with the protein. In some embodiments, the one or more polyurethanes and the one or more proteins may be blended in a suitable container until a homogenized blend is formed. Suitable blending equipment includes, but is not limited to, a blender, a stand mixer, an in-line mixer, or a high shear mixer. The blend may be foamed using, for example, a mechanical foaming process or a chemical foaming process. Exemplary mechanical foaming equipment includes a Hansa mixer or Foaming machine. Blending and foaming can be performed separately or simultaneously.
[0297] Suitable polyurethanes for blending and foaming in step 1912 are those discussed herein for protein polyurethane alloy layers. In some embodiments, one or more blowing agents and / or foam stabilizers may be added to the blend in step 1912. Suitable blowing agents and foam stabilizers include those discussed herein for protein polyurethane alloy layers 1830 / 1840.
[0298] In some embodiments, blend may include about 10 wt % or less blowing agent or foam stabilizer content.For example, blend may include about 0.1 wt %, about 1 wt %, about 2.5 wt %, about 5 wt %, about 7.5 wt % or about 10 wt % blowing agent or foam stabilizer.In some embodiments, blend may include about 0.1 wt % to about 10 wt %, about 1 wt % to about 7.5 wt %, about 2.5 wt % to about 5 wt %, about 0.1 wt % to about 5 wt % or about 0.1 wt % to about 2.5 wt % blowing agent or foam stabilizer.In some embodiments, blend may be substantially free of or free of blowing agent and / or foam stabilizer.In such embodiments, the protein polyurethane alloy layer produced by blend may be substantially free of or free of blowing agent and / or foam stabilizer.
[0299] The foaming in step 1912 can be used to give the required density of the foamed protein polyurethane alloy layer. In some embodiments, before removing the solvent in step 1916, the liquid density of the foamed blended mixture can be in the range of about 300g / L to about 900g / L, including sub-ranges. For example, the liquid density of the foamed blended mixture formed in step 1912 can be about 300g / L, about 400g / L, about 500g / L, about 600g / L, about 700g / L, about 800g / L or about 900g / L, or in the range of any two as endpoints with these values. In some embodiments, the liquid density of the foamed blended mixture can be in the range of about 300g / L to about 800g / L, about 300g / L to about 700g / L, about 400g / L to about 600g / L, about 300g / L to about 500g / L or about 300g / L to about 600g / L. In some embodiments, the liquid density of the blended mixture formed in step 1906 before the solvent is removed from the blended mixture in step 1910 may be greater than the liquid density of the foamed blended mixture formed in step 1912 before the solvent is removed in step 1916 .
[0300] In some embodiments, the protein may be dispersed or dissolved in an aqueous solution before being blended and foamed with the polyurethane in step 1912. Suitable aqueous solutions include those discussed above for step 1906. The protein concentration in the aqueous solution may be any value or range discussed above for step 1906. The amount of protein in the protein / polyurethane blend of step 1912 may be any value or range discussed above for step 1906. The blending temperature of step 1912 may be any temperature or temperature range discussed above for step 1906. The blending time of step 1912 may be any time or time range discussed above for step 1906. The blending speed of step 1912 may be any speed or speed range discussed above for step 1906. In some embodiments, one or more additives may be added to the blend in step 1912. The additive added in step 1912 may be any of the additives discussed above for step 1906.
[0301] In step 1914, a layer of the foamed blended mixture is disposed on the sacrificial layer 2000. In some embodiments, a layer of the foamed blended mixture is disposed on the surface of the protein polyurethane alloy layer 1820. In some embodiments, the blended and foamed mixture can be directly coated on the surface of the protein polyurethane alloy layer 1820. In some embodiments, the foamed blended mixture can be formed into a sheet by coating it on the surface to a desired thickness. Coating can include pouring, extrusion, casting, etc. In some embodiments, the sheet can be spread to a desired thickness using, for example, a paddle, a blade, a roller, a doctor blade roll coating, a curtain coating, and a slot die coating.
[0302] In step 1916, the solvent (e.g., water) may be removed from the applied foamed blend mixture to form a foamed protein polyurethane alloy layer 1830, such as Fig.20D Suitable solvent removal methods include, but are not limited to, tunnel drying, vacuum drying, oven drying with hot air, humidity chamber drying, flotation drying with hot air, and ovens with a combination of mid-range IR for preheating and hot air for subsequent drying. Suitable solvent removal temperatures for step 1916 can be any of the temperatures or temperature ranges discussed above for step 1910. The humidity value for step 1916 can be any of the humidity values or humidity ranges discussed above for step 1910.
[0303] In some embodiments, steps 1912 to 1916 may be repeated multiple times to form multiple foamed protein polyurethane alloy layers, such as foamed protein polyurethane alloy layers 1830 and 1840, on sacrificial layer 2000. In such embodiments, the foamed blended mixtures formed in separate steps 1912 may have different liquid densities. For example, the liquid density of one foamed blended mixture may be 10 g / L to 300 g / L greater or less than the liquid density of another foamed blended mixture. For example, in some embodiments, the liquid density of the first blended mixture may be in the range of about 300 g / L to about 500 g / L, and the liquid density of the second blended mixture may be in the range of about 600 g / L to about 700 g / L. For another example, the liquid density of the first blended mixture may be in the range of about 300 g / L to about 400 g / L, and the liquid density of the second blended mixture may be in the range of about 500 g / L to about 700 g / L.
[0304] In some embodiments, steps 1912 to 1916 may be repeated in sequence to form a plurality of foamed protein polyurethane alloy layers on the sacrificial layer 2000. In some embodiments, the foamed and blended mixture formed in step 1912 may be used to form a plurality of foamed protein polyurethane alloy layers in steps 1914 to 1916. In some embodiments, steps 1912 to 1916 may be performed before performing a set of steps 1906 to 1910 to form one or more foamed protein polyurethane alloy layers between the protein polyurethane alloy layer 1820 and the sacrificial layer 2000. In some embodiments, method 1900 may not include steps 1912 to 1916.
[0305] In step 1918, sacrificial layer 2000 is removed from the layers formed in steps 1902-1916, such as Fig.20E As shown. Sacrificial layer 2000 can be removed by a mechanical process or a chemical process. For example, sacrificial layer 2000 can be removed by peeling sacrificial layer 2000 from other layers. As another example, sacrificial layer 2000 can be removed by dissolving sacrificial layer 2000. In some embodiments, sacrificial layer 2000 can be removed in step 1918, and then the layers formed in steps 1902 to 1916 are attached to base layer 1710 in step 1920. In some embodiments, sacrificial layer 2000 can be removed after step 1920.
[0306] In step 1920, the layers formed in steps 1902-1916 are attached to the base layer 1710, such as Fig.20F As shown. In step 1920, the protein polyurethane alloy layer 1820 and any other protein polyurethane alloy layer formed in steps 1906 to 1916 are attached to the base layer 1710. In some embodiments, attaching one or more protein polyurethane alloy layers (e.g., protein polyurethane alloy layer 1820) to the base layer 1710 in step 1920 includes a hot pressing process. In such embodiments, the protein polyurethane alloy layer (e.g., protein polyurethane alloy layer 1820) may be in direct contact with the base layer 1710. In addition, in such embodiments, the protein polyurethane alloy layer may be partially melted into the base layer 1710, and when cooled, the two layers are firmly attached. In some embodiments, attaching one or more protein polyurethane alloy layers (e.g., protein polyurethane alloy layer 1820) to the base layer 1710 in step 1920 includes a lamination process. In such embodiments, lamination can be achieved with an adhesive layer 1850. In such embodiments, the base layer 1710 and / or the protein polyurethane alloy layer can be coated with an adhesive by known techniques such as slot die casting, conformal coating, pull-down techniques, or reverse transfer coating. In some embodiments, the lamination process can include passing the base layer 1710 and other layers through rollers under heating.
[0307] In some embodiments, step 1920 may be omitted from method 1900. In such embodiments, the layers formed in steps 1902 to 1916 define the protein polyurethane alloy layer or layered material of base layer 1710.
[0308] In some embodiments, the tear strength of the protein polyurethane alloy layer described herein may be in the range of about 2N to about 30N, including subranges. For example, the tear strength of the protein polyurethane alloy layer may be 2N, about 4N, about 5N, about 10N, about 15N, about 20N, about 25N, or about 30N, or in a range having any two of these values as endpoints, including endpoints. In some embodiments, the tear strength may be in the range of about 4N to about 25N, about 5N to about 20N, or about 10N to about 15N.
[0309] Tear strength (or tear resistance) is a measure of the degree to which a material can withstand the effects of tearing. Tear resistance can be measured by a variety of methods, such as the method provided by ASTM D 412 or the method provided by ISO 3377 (also known as "Baman tearing"). The method provided by ASTM D 624 can also be used to measure the ability to resist tear formation and the ability to resist tear expansion. Regardless of the method used, first, a cut is made in the material sample tested to cause tearing. Then, the sample is held between two clamps and a uniform pulling force is applied until the sample is torn in half. Tear resistance is then calculated by dividing the applied force by the thickness of the material. Unless otherwise specified, the tear strength values reported herein are measured by ISO 3377.
[0310] In some embodiments, the tensile strength of the layered materials described herein can be in the range of about 1 kPa (kilopascals) to about 100 MPa (megapascals), including subranges. For example, the tensile strength of the material can be about 1 kPa, about 50 kPa, about 100 kPa, about 200 kPa, about 300 kPa, about 400 kPa, about 500 kPa, about 600 kPa, about 700 kPa, about 800 kPa, about 900 kPa, about 1 MPa, about 5 MPa, about 10 MPa, about 20 MPa, about 30 MPa, about 40 MPa, about 50 MPa, about 60 MPa, about 70 MPa, about 80 MPa, about 90 MPa, or about 100 MPa, or in a range having any two of these values as endpoints, including the endpoints. In some embodiments, the tensile strength may be in the range of about 50 kPa to about 90 MPa, about 100 kPa to about 80 MPa, about 200 kPa to about 70 MPa, about 300 kPa to about 60 MPa, about 400 kPa to about 50 MPa, about 500 kPa to about 40 MPa, about 600 kPa to about 30 MPa, about 700 kPa to about 20 MPa, about 800 kPa to about 10 MPa, or about 1 MPa to about 5 MPa.
[0311] The softness of a material (also referred to as "hand") can be determined by ISO 17235. In some embodiments, the softness of the outer surface of the material described herein can be in the range of about 2 mm to about 12 mm, including sub-ranges. For example, the softness of the outer surface of the material can be about 2 mm, about 3 mm, about 4 mm, about 5 mm, about 6 mm, about 7 mm, about 8 mm, about 9 mm, about 10 mm, about 11 mm, or about 12 mm, or in a range having any two of these values as endpoints, including the endpoints. In some embodiments, the softness can be about 3 mm to about 11 mm, about 4 mm to about 10 mm, about 5 mm to about 9 mm, about 6 mm to about 8 mm, or about 6 mm to about 7 mm. Unless otherwise indicated, the softness values disclosed herein are determined by ISO 17235.
[0312] The flexibility or strain of a material can be determined by measuring its elongation at break when a tensile force is applied, for example using the formula: ΔL / L, where ΔL is the change in length of the material after the tensile force is applied, and L is the initial length of the material. Flexibility can also be measured according to the method provided by ASTM D 412. In some embodiments, the flexibility of the material described herein may be in the range of about 100% to about 400%, including sub-ranges. For example, the flexibility of the material may be about 100%, about 200%, about 300%, or about 400%, or in a range with any two of these values as endpoints, including endpoints. In some embodiments, the flexibility may be about 100% to about 200%, about 100% to about 300%, about 200% to about 300%, or about 200% to about 400%. Unless otherwise specified, the flexibility values disclosed herein are measured by ASTM D 412. In some embodiments, the protein polyurethane alloy layer described herein may have a flexibility value or range as described above for the layered material.
[0313] In some embodiments, the permanent deformation of the material as described herein in the hysteresis experiment may be about 8% or less. In some embodiments, the permanent deformation of the material may be about 1%, about 2%, about 3%, about 4%, about 5%, about 6%, about 7%, or about 8%, or in a range with any two of these values as endpoints. In some embodiments, the permanent deformation of the material may be about 1% to about 8%, about 2% to about 7%, about 3% to about 6%, or about 4% to about 5%.
[0314] Unless otherwise specified, permanent deformation values are measured by the following method. Cut a dog-bone shaped material tensile specimen and measure the initial length of the specimen. The specimen is cut into a dog-bone shape of approximately 110 mm long and 10 mm wide (75 mm-100 mm gauge length). Then, use The machine stretches the sample along its length to 15% strain and back to 0% strain, both at a constant rate of three millimeters per second. This operation is repeated five times. Then, the distance between the initial sample length and the length of the sample at the last return cycle when the load becomes zero is measured. The percentage difference between the length measured after repeatedly straining the material and the initial length is the permanent set %. To calculate the permanent set value, three separate samples of the material are evaluated, and the average permanent set value is reported as the permanent set value of the material.
[0315] In some embodiments, the materials described herein may have a moisture vapor transmission rate (MVTR) of about 75 g / m 2 / hour or more. In some embodiments, the MVTR of the materials described herein may be about 75 g / m 2 / hour to about 200g / m 2 / hour, including sub-ranges. For example, the MVTR of the material may be about 80 g / m 2 / hour to about 190g / m 2 / hour, about 90g / m 2 / hour to about 180g / m 2 / hour, about 100g / m 2 / hour to about 170g / m 2 / hour, about 110g / m 2 / hour to about 160g / m 2 / hour, about 120g / m 2 / hour to about 150g / m 2 / hour or about 130g / m 2 / hour to about 140g / m 2 Unless otherwise indicated, the MVTR values disclosed herein are measured using ASTM E96 ("Standard Test Method for Water Vapor Transmission of Materials") - Procedure B, Water Method, at about 74.3°F at about 50% relative humidity, and with a 3 / 4 inch air gap.
[0316] Materials having moisture vapor transmission rates as reported herein may be useful in a variety of applications where breathability of the material is a desired property. Exemplary applications where breathability may be desired include, but are not limited to, footwear, apparel, and interior decoration. The layered materials as described herein may have significantly higher water vapor transmission rates than layered polymer materials having the same number of layers and the same thickness and made of the same polymer material but without the protein blended in the polymer material.
[0317] In some embodiments, the materials described herein may have a color fastness of 4 or higher when measured according to the ISO 11640 ("Leather - Tests for color fastness - Fastness to back and forth rubbing cycles") wet rubbing test. In some embodiments, the layered materials described herein may have a color fastness of 4, 4.5, or 5 when measured according to the ISO 11640 wet rubbing test. Color fastness of 4 or higher can provide the materials described herein with the abrasion resistance required for a variety of applications.
[0318] Material as herein described can realize 4 grades or higher color fastness or any other color characteristic as herein described when pigment is not included in the material.Compared with the polyurethane material made of the same polyurethane of the protein not blended in the polyurethane, this is a unique characteristic.The protein in material as herein described can be well attached to the dye for coloring the material.In order to realize high color fastness, pigment is usually used to color the polyurethane material, because dye can not be well attached to polyurethane usually.The poor adhesion between dye and polyurethane causes relatively low color fastness.Dyeing material as herein described can have the color depth and other aesthetic features of improvement that can not be realized with the polyurethane colored with pigment.
[0319] In some embodiments, the dyeing materials according to the embodiments described herein may have a wet friction value of 3 or more. In some embodiments, the dyeing materials according to the embodiments described herein may have a wet friction value of 4 or more. In some embodiments, the dyeing materials according to the embodiments described herein may have a dry friction value of 3 or more. In some embodiments, the dyeing materials according to the embodiments described herein may have a dry friction value of 4 or more. Unless otherwise stated, wet and dry friction are measured according to ISO 105-X12 (2016): Textiles-Tests for color fastness-Part X12: Color fastness to rubbing.
[0320] In some embodiments, the dyeing material according to the embodiments described herein may have a water fastness value of 3 or higher. In some embodiments, the dyeing material according to the embodiments described herein may have a water fastness value of 4 or higher. In some embodiments, the dyeing material according to the embodiments described herein may have a perspiration fastness of 3 or higher. In some embodiments, the dyeing material according to the embodiments described herein may have a perspiration fastness of 4 or higher. Unless otherwise stated, water fastness is measured according to ISO 11642IULTCS / IUF 421 (2012): Leather-Color Fastness Test-Water Fastness. Unless otherwise stated, perspiration fastness is measured according to ISO 105-E04 (2013): Textiles-Color Fastness Test-Part E04: Perspiration Fastness.
[0321] In some embodiments, the dyeing materials according to the embodiments described herein may have a color migration value of 2 or more. In some embodiments, the dyeing materials according to the embodiments described herein may have a color migration value of 4 or more. In some embodiments, the dyeing materials according to the embodiments described herein may have a color migration value of 5 or more. Unless otherwise stated, color migration is measured according to ISO 15701IULTCS / IUF 442 (2015): Leather-Color Fastness Test-Color Fastness to Migration to Polymeric Materials.
[0322] In some embodiments, the dyed materials according to the embodiments described herein may have a dry Martindale value of 2 or more. In some embodiments, the dyed materials according to the embodiments described herein may have a dry Martindale value of 3 or more. Unless otherwise stated, the dry Martindale is measured according to ISO 12947-4:1998: Textiles - Determination of abrasion resistance of fabrics by the Martindale method - Part 4: Evaluation of changes in appearance.
[0323] In some embodiments, the dyed materials according to the embodiments described herein may have a light fastness value of 3 or higher. In some embodiments, the dyed materials according to the embodiments described herein may have a light fastness value of 4 or higher. Unless otherwise stated, light fastness is measured according to ISO 105-B02 (2014): Textiles - Tests for color fastness - Part B02: Color fastness to artificial light: Xenon arc lamp test.
[0324] In some embodiments, the dyed materials according to the embodiments described herein may have a K / S color intensity value of 6 or higher. In some embodiments, the dyed materials according to the embodiments described herein may have a K / S color intensity value of 7 or higher. Unless otherwise stated, K / S color intensity values are measured using a spectrophotometer at the wavelength of the lowest R / T (reflectance to transmittance) value.
[0325] In some embodiments, the material described herein (e.g., material 1700 or 1800) or a single layer of the material described herein may be subjected to finishing treatments identical or similar to those used to process natural leather. In some embodiments, the material described herein may be rolled or softened to customize the properties of the material, such as the feel of the material. In such embodiments, traditional textile polishing and softening methods may be used. In some embodiments, the material described herein may be tanned. In some embodiments, the material described herein may be fatliquored. In some embodiments, the material described herein may be retanned.
[0326] In some embodiments, the materials described herein (e.g., material 1700 or 1800) or a single layer of a material described herein may have an elastic modulus of 9*10^7 Pa or less. In some embodiments, the materials described herein (e.g., material 1700 or 1800) or a single layer of a material described herein may have an elastic modulus of 8*10^7 Pa or less, 7*10^7 Pa or less, 6*10^7 Pa or less, 5*10^7 Pa or less, 4*10^7 Pa or less, 3*10^7 Pa or less, 2*10^7 Pa or less, or 1*10^7 Pa or less. In some embodiments, a material described herein (e.g., material 1700 or 1800) or a single layer of a material described herein may have an elastic modulus ranging from 1*10^5 Pa to 9*10^7 Pa, 5*10^5 Pa to 9*10^7 Pa, 1*10^6 Pa to 9*10^7 Pa, 5*10^6 Pa to 9*10^7 Pa, or 1*10^7 Pa to 9*10^7 Pa. Unless otherwise stated, the elastic modulus values disclosed herein are measured according to ASTM D5934-02 (Determination of the elastic modulus of rigid and semi-rigid plastic specimens by controlling the loading rate using the three-point bending method) with the following modifications to the test specification. Different from collecting single modulus data points on five different samples using a dual cantilever fixture as recommended by ASTM D5934-02 and averaging the results, 37 data points were applied to a single sample using an oscillating 3-point bending fixture with a DMA 850 dynamic mechanical analyzer at a predetermined strain percentage and 1 Hz frequency over 2 minutes of oscillation. The average modulus value of the 37 data points was obtained and reported. In order to determine the strain percentage of the 37 data points, an amplitude sweep was performed on the sample with the same material to identify the stress and strain region where the elastic modulus is linear. All 37 data points were taken within this linear region.
[0327] Tanning can be carried out in any number of well-understood modes, including by contacting the material with vegetable tanning agents, blocked isocyanate compounds, chromium compounds, aldehydes, synthetic tanning agents, natural resins, tanning natural oils or modified oils. The blocked isocyanate compounds may include X-tan. Vegetable tannins may include tannins based on pyrogallol or catechol, such as oak bowl, mimosa, ten, tara, oak, pine, sumac, broken axe tree and chestnut tannins. Chrome tanning agents may include chromium salts, such as chromium sulfate. Aldehyde tanning agents may include glutaraldehyde and oxazolidine compounds. Synthetic tanning agents may include copolymers of aromatic polymers, polyacrylates, polymethacrylates, maleic anhydride and styrene, condensation products of formaldehyde and melamine or dicyandiamide, lignin and natural grain flour.
[0328] In order to tan the material, the pH of the material can be adjusted in the presence of 10% salt (e.g., sodium chloride, sodium sulfate or sodium salt), for example, reduced to a pH in the range of about 2.5 to about 3.0, to allow the tanning agent to penetrate. After penetration, the pH of the material can be adjusted again, for example, raised to a pH in the range of about 3.5 to about 4.0, to fix the tanning agent. In some embodiments, the material can be immersed in a bath of chromium sulfate (III) comprising 2 wt % (based on the weight of the protein polyurethane alloy in the material), and the pH can be adjusted according to the needs of penetration and fixation. The material can then be added to a container, and the container can be stirred, for example, on an orbital oscillator, at 50 rpm. Stirring can be carried out at a pH of about 2.8 to about 3.2, and can be carried out for a time sufficient to allow chromium sulfate (III) to penetrate into the material. After penetration, the pH of the bath can be increased, and the fixation of chromium sulfate (III) can be carried out at a pH between about 3.8 and about 4.2. The duration of the fixing step can be selected to achieve the desired color of the material.
[0329] In some embodiments, the material can be tanned by cross-linking protein polyurethane alloy. The cross-linking reaction can stabilize the alloy structure. Any suitable cross-linking agent known in the art can be used to cross-link the alloy, such as mineral salts (such as those based on chromium), formaldehyde, hexamethylene diisocyanate, glutaraldehyde, polyepoxides, gamma radiation, and ultraviolet radiation when using riboflavin. Any suitable cross-linking agent may include isocyanates, carbodiimides, poly (aldehydes), poly (aziridines), mineral salts, poly (epoxy resins), enzymes, ethylene sulfide, phenolic resins, novolacs, resols, and other compounds with chemical properties that react with amino acid side chains (such as lysine, arginine, aspartic acid, glutamic acid, hydroxyproline or hydroxylysine). In some embodiments, the cross-linking agent may be a cross-linking agent selected from the group consisting of epoxy cross-linking agents, isocyanate cross-linking agents, and carbodiimide cross-linking agents. In some embodiments, the cross-linking agent may be a carbodiimide cross-linking agent.
[0330] In some embodiments, after tanning, the material can be retanned. Retanning refers to post-tanning treatment. Such treatments may include secondary tanning, wetting (rehydrating semi-processed materials), squeezing (squeezing 45%-55% water from the material), dehydration, neutralization (the pH of the material is adjusted to, for example, between about 4.5 and about 6.5), adding colorants (such as dyes), fattening, fixing unbound chemicals, shaping (giving particle flatness and removing excess water), conditioning (adding moisture to the material to, for example, about 18%-28% level), softening (physical softening of the material by separating fibers), polishing (grinding the material surface to reduce fluff and particle defects), scraping (thinning the material), filling (dense / heavy chemicals to make the material harder and heavier) and / or stuffing (adding fats, oils, waxes).
[0331] In some embodiments, the material may be subjected to a surface coating process. Surface coating may include any one or combination of the following steps: oiling (coating the material with crude oil or oil), sanding, spraying, roller coating, curtain coating, polishing, electroplating, embossing, ironing or polishing.
[0332] In some embodiments, the fatting agent used during fatting may include functionalized oil. Suitable fatting agents include anionic fatting agents, cationic fatting agents, nonionic fatting agents, emulsion-based fatting agents or non-emulsion fatting agents. In some embodiments, the fatting agent may include sulfited fatting agents, sulfated fatting agents or combinations thereof.
[0333] In some embodiments, additional lubricants can be incorporated into the material according to the embodiments described herein. Additional lubricants include, but are not limited to, fats, bio-oils, mineral oils or synthetic oils, cod oils, polymers, organofunctional siloxanes or other hydrophobic compounds or agents or mixtures thereof for lubricating conventional leather. Other lubricants include surfactants, anionic surfactants, cationic surfactants, cationic polymer surfactants, anionic polymer surfactants, amphiphilic polymers, fatty acids, modified fatty acids, nonionic hydrophilic polymers, nonionic hydrophobic polymers, polyacrylic acid, polymethacrylic acid, acrylic resins, natural rubber, synthetic rubber, resins, amphiphilic anionic polymers and copolymers, amphiphilic cationic polymers and copolymers and mixtures thereof, and emulsions or suspensions of these materials in water, alcohol, ketones and other solvents.
[0334] In some embodiments, after fatliquoring, the material may comprise from about 1 wt % to about 16 wt %, including subranges. For example, in some embodiments, the material may comprise from about 1 wt % to about 16 wt %, from about 2 wt % to about 16 wt %, from about 3 wt % to about 16 wt %, from about 4 wt % to about 16 wt %, from about 5 wt % to about 16 wt %, from about 6 wt % to about 16 wt %, from about 7 wt % to about 16 wt %, from about 8 wt % to about 16 wt %, from about 9 wt % to about 16 wt %, or from about 10 wt % to about 16 wt % of one or more fatliquoring agents.
[0335] Surprisingly, materials comprising a protein polyurethane alloy applied to a textile as described herein are able to accept a fatliquor in a weight percentage range of about 1 wt % to about 16 wt % to achieve desired mechanical properties, such as softness and flexibility. This is surprising, especially at high protein concentrations, because adding protein to a material typically results in a material with high hardness and rigidity.
[0336] In some embodiments, after fatliquoring, the protein polyurethane alloy may include from about 1 wt % to about 16 wt %, including subranges. For example, in some embodiments, the protein polyurethane alloy may include from about 1 wt % to about 16 wt %, from about 2 wt % to about 16 wt %, from about 3 wt % to about 16 wt %, from about 4 wt % to about 16 wt %, from about 5 wt % to about 16 wt %, from about 6 wt % to about 16 wt %, from about 7 wt % to about 16 wt %, from about 8 wt % to about 16 wt %, from about 9 wt % to about 16 wt %, or from about 10 wt % to about 16 wt % of one or more fatliquoring agents.
[0337] Surprisingly, the protein polyurethane alloys applied to textiles as described herein are able to accept a fatliquor in a weight percentage range of about 1 wt % to about 16 wt % to achieve desired mechanical properties, such as softness and flexibility. This is surprising, especially at high protein concentrations, because adding protein to a material typically results in a material with high hardness and rigidity.
[0338] In some embodiments, water can be removed by filtering, evaporating, freeze drying, solvent exchange, vacuum drying, convection drying, heating, radiation or microwave treatment, or by other known methods for water removal. In some embodiments, the water content of the material after dehydration is no more than about 60 weight % of the material, for example, no more than about 5 weight %, about 10 weight %, about 15 weight %, about 20 weight %, about 30 weight %, about 35 weight %, about 40 weight %, about 50 weight % or about 60 weight %. Unless otherwise specified, water content is measured by balancing at 25 ℃ and 1atm, 65% relative humidity.
[0339] In some embodiments, the tanned material may be mechanically or chemically finished. For example, mechanical finishing may include buffing the material to produce a shiny surface; ironing and electroplating the material to achieve a flat, smooth surface; embossing the material to form a three-dimensional print or pattern on the surface of the material; or tumbling the material to provide a more pronounced grain and smooth surface. Chemical finishing may involve applying a film, natural or synthetic coating, or other treatment. The chemical treatment may be applied, for example, by spraying, curtain coating, or roller coating.
[0340] In some embodiments, the materials described herein can be used as a substitute for natural leather in a variety of applications. For example, the materials can be used in footwear, clothing, gloves, furniture, vehicle decoration, and other goods and products, such as coats, coats, jackets, shirts, trousers, pants, shorts, swimwear, underwear, uniforms, badges or letters, performance costumes, ties, skirts, dresses, blouses, leggings, gloves, mittens, shoes, shoe parts (such as soles, waists, tongues, shoe collars, welts and shoe counters), dress shoes, athletic shoes, running shoes, casual shoes, sneakers, or casual shoes. parts thereof (such as toes, pull-ons, outsoles, insoles, uppers, laces, eyelets, collars, pads, Achilles grooves, heels and counters), fashion shoes or women's shoes and shoe parts thereof (such as uppers, outsoles, toe tips, pull-ons, decorations, vamps, pads, insoles, midsoles, platforms, counters, and heels or high heels), boots, sandals, buttons, sandals, hats, masks, head covers, headbands, headscarves and belts; jewelry such as bracelets, watch straps and necklaces; gloves, umbrellas , walking sticks, wallets, mobile phone or wearable computer covers, purses, backpacks, suitcases, handbags, folios, folders, boxes and other personal effects; sports, athletic, hunting or recreational equipment such as harnesses, bridles, reins, bits, leads, mittens, tennis rackets, golf clubs, polo, hockey or lacrosse equipment, chess and game boards, medicine balls, children's soccer, baseball and other kinds of balls, and toys; book bindings, book covers, photo frames or works of art; furniture and residential, office or other interior or exterior furnishings, including chairs, chairs, doors, seats, ottomans, room dividers, coasters, mouse pads, desk blotters, or other mats, tables, beds, floors, wall or ceiling coverings, floor coverings, automobile, boat, aircraft and other vehicle products, including seats, headrests, upholstery, paneling, steering wheels, joystick or control covers and other wrappings or coverings.
[0341] In some embodiments, a material, a layered material, or a single layer of a layered material may have a rough outer surface. For example, the top surface 1824 of the protein polyurethane alloy layer 1820 may have a rough surface, the top surface 1874 of the top coating 1870 may have a rough surface, the top surface 1864 of the bottom coating 1860 may have a rough surface, the top surface 1834 of the protein polyurethane alloy layer 1830 may have a rough surface, or the top surface 1844 of the protein polyurethane alloy layer 1840 may have a rough surface. The rough outer surface may produce a surface texture that is similar to natural leather (e.g., the texture of pebbled natural leather) in appearance and feel. In some embodiments, the top surface 2002 of the sacrificial layer 2000 may have a rough surface that is transferred to the surface of a layer directly disposed on the top surface 2002 during method 1900.
[0342] The surface area per square inch of a rough surface is at least about 1% greater than 1 square inch. In other words, in some embodiments, a one square inch sample of a material (e.g., material 1700 or layered material 1800) (including a layer having a rough outer surface) may have a surface area at least about 1% greater than a one square inch sample of a material having a completely smooth surface. In some embodiments, the surface area per square inch of the rough outer surface may be at least about 1% greater than 1 square inch, about 10% greater than 1 square inch, about 20% greater than 1 square inch, about 30% greater than 1 square inch, about 40% greater than 1 square inch, about 50% greater than 1 square inch, about 60% greater than 1 square inch, about 70% greater than 1 square inch, about 80% greater than 1 square inch, about 90% greater than 1 square inch, about 100% greater than 1 square inch, about 150% greater than 1 square inch, about 200% greater than 1 square inch, about 250% greater than 1 square inch, about 300% greater than 1 square inch, about 350% greater than 1 square inch, about 400% greater than 1 square inch, about 450% greater than 1 square inch, or about 500% greater than 1 square inch, or within a range having any two of these values as endpoints, inclusive. In some embodiments, the surface area per square inch of the rough surface may be about 1% to about 500% greater than 1 square inch, about 10% to about 450% greater than 1 square inch, about 20% to about 400% greater than 1 square inch, about 30% to about 350% greater than 1 square inch, about 40% to about 300% greater than 1 square inch, about 50% to about 250% greater than 1 square inch, about 60% to about 200% greater than 1 square inch, about 70% to about 150% greater than 1 square inch, or about 80% to about 100% greater than 1 square inch. Unless otherwise specified, the surface area of the materials disclosed herein is measured using profilometry. For opaque materials, optical profilometry is used. In some embodiments, the layered material or a single layer of a layered material may have a smooth outer surface. The surface area per square inch of the smooth surface is less than 1% greater than 1 square inch. For example, the surface area per square inch of the smooth surface may be 1 square inch to less than 1.01 square inches. In some embodiments, the top surface 2002 of the sacrificial layer 2000 can have a smooth surface that is transferred to the surface of a layer disposed directly on the top surface 2002 during the method 1900 .
[0343] In some embodiments, the layered material or a single layer of the layered material can have a textured outer surface. In some embodiments, the top surface 2002 of the sacrificial layer 2000 can have a textured surface that is transferred to the surface of the layer disposed directly on the top surface 2002 during the method 1900. In some embodiments, the textured outer surface can have a surface area per square inch or a range of surface area per square inch, as discussed above for the rough surface.
[0344] In some embodiments, the texture may be a macroscale texture, for example, a The macroscale texture of the present invention can be any one of the many textures used on the Sappi / Warren release paper manufactured by Sappi North America, which is operated by SDWarren Company, under the trade name Classic. An example of macroscale texture is a replica of the natural leather texture of about 50 microns to about 300 microns with a characteristic depth. Any other required macroscale texture can also be used. In some embodiments, the macroscale texture can be "leather texture". As used herein, the term "leather texture" is the texture of simulating the appearance and feel of natural leather. Exemplary "leather texture" includes but is not limited to Sappi Matte Freeport 189, Sappi Freeport 123 or Sappi Expresso 904.
[0345] In some embodiments, the texture may be a micron-scale texture. In some embodiments, the texture may be a micron-scale texture with surface features having a characteristic size less than 50 microns (e.g., 1000 nanometers to less than 50 microns). An example of a micron-scale texture is referred to as "Sharklet" in the art. Sharklet textures may be applied to provide a structured surface to a product to prevent bacterial growth. The micron-scale texture on the surface replicates shark skin denticles, which are arranged in a diamond pattern with millions of tiny ribs. Sharklet materials are discussed, for example, in U.S. Patent Nos. 7,650,848 and 8,997,672, the disclosures of which are incorporated herein by reference.
[0346] In some embodiments, the texture can be a micron-scale texture having surface features with a characteristic size less than 1000 nanometers, such as 10 nanometers to less than 1000 nanometers. An example of a nanoscale texture is a diffraction grating having a series of ridges about 400 nanometers wide, spaced about 800 nanometers apart, and about 100 nanometers deep.
[0347] The embodiments discussed herein will be further illustrated in the following examples.It should be understood that these examples are not limited to the embodiments described above.
[0348] Example 1
[0349] The sample was prepared by mixing 5.5 g of aqueous polyurethane dispersion L3360 from Hauthaway with 10 mL of deionized water and stirring at 1000 rpm (rotations per minute) for 30 minutes at 50°C. The solution was then pipetted into a Teflon evaporating dish with a diameter of 10 cm. The dish was dried in an oven at 45°C overnight. After drying, the dried sample was conditioned in a standard reference atmosphere (23°C, 50% humidity) for 24 hours to obtain a polyurethane film.
[0350] The film was tested using DMA-850 from TA Instruments. A 1 cm × 2.5 cm strip was cut from each film using a metal die. The cut film samples were loaded into a film and fiber tension fixture for testing. During the test, a preload of 0.01 N was applied to the cut film samples. The instrument was cooled to -80 ° C, held for 1 minute, and then the temperature was raised to 200 ° C at 4 ° C / min, or until the sample was too weak to maintain tension. During the temperature ramp, the sample oscillated 0.1% strain at a frequency of 1 Hz. For both films, storage modulus, loss modulus and tan (δ) were plotted against temperature. The resulting second storage modulus transition (the starting point of the last drop in the measured storage modulus, i.e., the second DMA modulus transition starting temperature) of the control sample was 114.9 ° C.
[0351] In addition, five tensile specimens (according to ASTM D638) were cut from each of the dried and conditioned sample films using a metal mold. The cut film samples were loaded onto 5960 series machine, and stretched at a tension of 100 mm / min until it broke. The average Young's modulus, average tensile strength (maximum tensile stress), and average elongation at break were recorded. The Young's modulus was 59 MPa, the maximum tensile stress was 12.9 MPa, and the elongation at break was 402%.
[0352] Examples 2 to 8
[0353] Examples 2 to 8 were carried out using the same method as Example 1 to illustrate a series of polyurethane dispersions. The polyurethanes used and the resulting properties are listed in Tables 3 to 6.
[0354] Example 9
[0355] The sample was prepared by dissolving 0.825 g (gram) of gelatin from pig skin into 10 mL (milliliter) of deionized water and stirring with a magnetic stirring bar at 1000 rpm (rotations per minute) for 1 hour at 50 ° C. After the gelatin was completely dissolved, the pH of the solution was adjusted to 7.0 with 0.1 N sodium hydroxide. Then 5.5 g of L3360 was added to the solution and stirred at 1000 rpm for 30 minutes. The polyurethane and gelatin solution was then pipetted into a Teflon evaporating dish with a diameter of 10 cm. The culture dish was dried overnight in an oven at 45 ° C. After drying, the dried sample was conditioned for 24 hours in a standard reference atmosphere (23 ° C, 50% humidity) to produce a gelatin polyurethane alloy film.
[0356] During pipetting, the gelatin polyurethane solution had a milky white appearance with no visible particles. After drying, the gelatin polyurethane solution produced a transparent film with a uniform appearance without optically visible particles. This result combined with Examples 33 and 34 shows that when the protein is miscible with the hard phase, the protein polyurethane alloy can be transparent and have enhanced properties.
[0357] DMA testing was performed as outlined in Example 1. The resulting second storage modulus transition (as the starting point of the last drop in the measured storage modulus, ie, the second DMA modulus transition onset temperature) of the gelatin polyurethane alloy was 180.6°C, 65.7°C higher than that of the control sample described in Example 1.
[0358] Tensile testing was performed as outlined in Example 1. The gelatin polyurethane alloy had an average Young's modulus of 344 MPa, measured an average tensile stress of 19.8 MPa, and an average elongation at break of 197%.
[0359] The increase in the second DMA modulus transition onset temperature and the increase in modulus and strength and decrease in elongation of this example compared to the polyurethane alone in Example 1 indicate that the dissolved gelatin in the gelatin polyurethane alloy is miscible with the hard phase of the polyurethane.
[0360] Examples 10 to 19
[0361] Examples 10 to 19 were carried out using the same method used for Example 9 to show a range of polyurethane dispersions from different manufacturers and different proteins. The resulting properties of these alloys are listed in Tables 3 to 6.
[0362] Embodiment 20
[0363] The sample was prepared by dissolving 0.825 g (gram) of bovine serum albumin (BSA) from Sigma into 10 mL (milliliter) of deionized water and stirring at 1000 rpm (rotations per minute) for 1 hour with a magnetic stirring bar at 20°C. Then 5.5 g of L3360 was added to the solution and stirred at 1000 rpm for 30 minutes. The polyurethane and BSA solution was then pipetted into a Teflon evaporating dish with a diameter of 10 cm. The culture dish was dried overnight at 25°C on a bench. After drying, the dried sample was conditioned for 24 hours in a standard reference atmosphere (23°C, 50% humidity) to produce a BSA polyurethane alloy film.
[0364] DMA testing was performed as outlined in Example 1. The resulting second storage modulus transition (as the starting point of the last drop in the measured storage modulus, ie, the second DMA modulus transition onset temperature) of the BSA polyurethane alloy was 184.9°C, 70°C higher than the control sample described in Example 1.
[0365] Tensile testing was performed as outlined in Example 1. The BSA polyurethane alloy had an average Young's modulus of 174 MPa, an average tensile stress of 11.7 MPa was measured, and an average elongation at break of 123%.
[0366] Embodiment 21
[0367] SPI was dispersed by adding 0.75 g of soy protein isolate (SPI) to 15 mL of sodium hydroxide solution at a concentration of 0.05 mol / L. The dispersion was stirred at 600 rpm for 3 hours at 80 ° C with a magnetic stirring bar. Then 5 g of L3360 was added to the solution and stirred at 600 rpm for 30 minutes. The SPI polyurethane solution was then pipetted into a Teflon evaporating dish with a diameter of 10 cm. The dish was dried overnight in an oven at 45 ° C. After drying, the dried sample was conditioned for 24 hours in a standard reference atmosphere (23 ° C, 50% humidity) to produce a SPI polyurethane alloy film.
[0368] DMA testing was performed as outlined in Example 1. The resulting second storage modulus transition (as the starting point of the last drop in the measured storage modulus, ie, the second DMA modulus transition onset temperature) of the SPI polyurethane alloy was 186.6°C, 72°C higher than the control in Example 1.
[0369] Tensile testing was performed as outlined in Example 1. The SPI polyurethane alloy had an average Young's modulus of 396 MPa, measured an average tensile stress of 18 MPa, and an average elongation at break of 151%.
[0370] The increase in the second DMA modulus transition onset temperature and the increase in modulus and strength and the decrease in elongation indicate that the dissolved SPI in the SPI polyurethane alloy is miscible with the hard phase of the polyurethane.
[0371] Examples 22 to 23
[0372] Examples 22 to 23 were carried out using the same method as Example 21. The proteins used and the resulting properties of these protein polymer alloys are listed in Tables 3 to 6.
[0373] Examples 24 to 29
[0374] The samples were prepared by the same method as in Example 9. The amounts of gelatin and L3360 were varied to achieve various mass ratios of the two components in the alloy samples. The masses of gelatin and PU dispersion and the resulting mass fractions are summarized in Table 2 below.
[0375] Table 2
[0376]
[0377]
[0378] Tensile and DMA testing were performed as outlined in Example 1. The resulting properties of the alloys are listed in Tables 3-6.
[0379] Embodiment 30
[0380] SPI was dispersed by adding 0.25g of soy protein isolate (SPI) to 15mL DI water. The dispersion was stirred at 600rpm for 3 hours at 80°C with a magnetic stirring bar. Then 6.42g of L3360 was added to the solution and stirred at 600rpm for 30 minutes. The SPI polyurethane solution was then pipetted into a Teflon evaporating dish with a diameter of 10cm. The dish was dried overnight in an oven at 45°C. After drying, the dried sample was conditioned for 24 hours in a standard reference atmosphere (23°C, 50% humidity) to produce a SPI polyurethane alloy film.
[0381] Tensile and DMA testing were performed as outlined in Example 1. The resulting properties of the alloys are listed in Tables 3-6.
[0382] Embodiment 31
[0383] SPI was dispersed by adding 0.5 g of soy protein isolate (SPI) to 15 mL of a sodium hydroxide solution having a concentration of 0.05 mol / L. The dispersion was stirred at 600 rpm for 3 hours at 80°C with a magnetic stirring bar. 6.42 g of L3360 was then added to the solution and stirred at 600 rpm for 30 minutes. The SPI polyurethane solution was then pipetted into a Teflon evaporating dish having a diameter of 10 cm. The dish was dried overnight in an oven at 45°C. After drying, the dried sample was conditioned for 24 hours in a standard reference atmosphere (23°C, 50% humidity) to produce a SPI polyurethane alloy film.
[0384] Tensile and DMA testing were performed as outlined in Example 1. The resulting properties of the alloys are listed in Tables 3-6.
[0385] Embodiment 32
[0386] Whey protein (from Sigma's milk whey W1500) is dispersed by adding 0.75g whey to 15mL sodium hydroxide solution with a concentration of 0.05mol / L. At 80 ℃, the dispersion is stirred at 600rpm for 3 hours with a magnetic stirring bar. Then 5g L3360 is added to the solution and stirred at 600rpm for 30 minutes. The whey polyurethane solution is then pipetted into a Teflon evaporating dish with a diameter of 10cm. The culture dish is dried overnight in an oven at 45 ℃. After drying, the dried sample is conditioned for 24 hours to produce a whey polyurethane alloy film under a standard reference atmosphere (23 ℃, 50% humidity).
[0387] DMA testing was performed as outlined in Example 1. The resulting second storage modulus transition (as the starting point of the last drop in the measured storage modulus, ie, the second DMA modulus transition onset temperature) of the whey polyurethane alloy was 100.9°C, an increase of 14°C compared to the control in Example 1.
[0388] Tensile testing was performed as outlined in Example 1. The whey polyurethane alloy had an average Young's modulus of 105 MPa, an average tensile stress of 7.6 MPa was measured, and an average elongation at break of 224%.
[0389] Although whey appears to be miscible with the hard phase of the polyurethane, it is believed that the second DMA modulus transition temperature does not increase due to the poor thermal stability of the protein itself. As discussed above, whey has a denaturation temperature at 158°C and is therefore considered to be non-thermally stable.
[0390] Embodiment 33
[0391] 0.75 g of casein (from milk, Sigma, C7078) was added to 15 mL of DI water (pH=7) without any other additives in a 20 mL glass vial, stirred at 600 rpm, heated to 90° C., and maintained for 3 hours.
[0392] Then add 5g L3360 to a 20mL glass vial. Cap the glass vial and vortex at maximum speed for 1 minute. Then transfer the mixed casein polyurethane liquid to a 10cm Teflon Petri dish. Dry the Petri dish in an oven at 45°C overnight (16 to 24 hours).
[0393] After drying, the casein polyurethane alloy film had an opaque appearance with many optically visible particles in the film. The 5960 series machine measures five tensile samples to measure the tensile properties of the film. The sample is stretched at a tension of 100 mm / min until it breaks. The average tensile strength of the film is 4.96 MPa. The average elongation at break of the film is 12.03%. The average Young's modulus of the film is 158 MPa. These results and the results of Example 34 indicate that casein is insoluble and non-dispersible in water at pH 7, and therefore does not dissolve in L3360 when mixed.
[0394] Embodiment 34
[0395] 0.75 g of casein (from milk, Sigma, C7078) was dispersed into 15 mL of 0.05 mol / L NaOH DI aqueous solution in a 20 mL glass vial, stirred at 600 rpm, heated to 90°C, and maintained for 3 hours. A uniform dispersion was obtained.
[0396] Then 5g of L3360 was added to a 20mL glass vial. The glass vial was then capped and vortexed at maximum speed for 1 minute. The mixed casein polyurethane liquid was then transferred to a 10cm Teflon Petri dish. The Petri dish was dried overnight (16 to 24 hours) in an oven at 45°C.
[0397] After drying, the casein polyurethane alloy film has a transparent and uniform appearance with no optically visible particles in the film. The tensile properties of the film were measured using a 5960 series machine measuring five tensile specimens. The samples were stretched at a tension of 100 mm / min until they broke. The average tensile strength of the film was 15.5 MPa. The average elongation at break of the film was 160%. The average Young's modulus of the film was 160 MPa. The increased modulus, strength, and elongation compared to Example 33 indicate that the modified casein is soluble in the polyurethane and is miscible with the hard phase of the polyurethane.
[0398] Embodiment 35
[0399] 0.375 g of soy protein isolate (SPI) and 0.375 g of r-collagen were added to 15 mL of 0.05 mol / L sodium hydroxide solution in a 20 mL glass vial. The soy protein isolate was purchased from MP Medicals (IC90545625). The r-collagen was recombinant collagen from Modern Meadow. The solution in the vial was mixed at 80°C with a magnetic stirring bar at 600 rpm for 2 hours.
[0400] Then 5g L3360 was added to a 20mL glass vial. The glass vial was capped and vortexed at maximum speed for 1 minute. The mixed SPI / r-col polyurethane liquid was then transferred to a 10cm Teflon Petri dish. The Petri dish was dried overnight in an oven at 45°C. After drying, the dried sample was conditioned for 24 hours in a standard reference atmosphere (23°C, 50% humidity) to produce a SPI / r-col polyurethane alloy film.
[0401] By using The tensile properties of the film were measured by measuring five tensile specimens using a 5960 series machine. The sample was stretched at a tension of 100 mm / min until it broke. The average tensile strength of the film was 15.71 MPa. The average elongation at break of the film was 175.9%. The average Young's modulus of the film was 247.1 MPa. The film was also tested using a DMA-850 from TA Instruments according to the method described in Example 1. The resulting second storage modulus transition (starting point of the last drop in the measured storage modulus, i.e., the second DMA modulus transition starting temperature) of the SPI / r-col polyurethane alloy was 184.9°C.
[0402] These results show an increase in the second DMA modulus transition onset temperature, as well as an increase in modulus and strength and a decrease in elongation compared to Example No. 1 and Example No. 9, indicating that the blend of SPI and r-col in the polyurethane alloy is miscible with the hard phase of the polyurethane and shows a corresponding enhancement in properties.
[0403] Embodiment 36
[0404] Films were prepared using the same method as Example 35 using 0.375 g pea protein MTX5232 from Bobs Red Mills, 0.375 g r-collagen (recombinant collagen from Modern Meadow) and 5 g L3360 polyurethane dispersion.
[0405] The resulting protein polyurethane alloy film was tested using the same tensile and DMA test methods as described for Example 35. The average tensile strength of the film was 15.36 MPa. The average elongation at break of the film was 183.17%. The average Young's modulus of the film was 231.13 MPa. The second DMA modulus transition onset temperature of the pea protein / r-col polyurethane alloy was 189.65°C.
[0406] These results show an increase in the second DMA modulus transition onset temperature, as well as an increase in modulus and strength compared to Example No. 1 and Example No. 9, indicating that the blend of pea protein and r-col in the protein polyurethane alloy is miscible with the hard phase of the polyurethane and shows a corresponding enhancement in properties.
[0407] Embodiment 37
[0408] The gelatin solution was prepared by dissolving 0.825 g (gram) of gelatin (Sigma Aldrich G2500) from porcine skin into 10 mL (milliliter) of deionized water and stirring at 1000 rpm (rotations per minute) for 1 hour at 50°C with a magnetic stirring bar. After the gelatin was completely dissolved, the pH of the solution was adjusted to 7.0 with 0.1 N sodium hydroxide. Navy Black #1684 fiber reactive dye was added to the gelatin solution at 4.05 parts per hundred parts of gelatin and mixed at 45°C for 15 minutes. Then 5.5 g of L3360 was added to the solution and stirred at 1000 rpm for 30 minutes. The polyurethane and gelatin solutions were then pipetted into a Teflon evaporating dish having a diameter of 10 cm. The dish was dried overnight in an oven at 45°C. The resulting film was uniformly dyed with no phase separation or color differences across the sample. Comparable films of the same polyurethane dispersion without protein could not be uniformly dyed.
[0409] Embodiment 38
[0410] Chemically modified soybean protein solutions (chemically modified soybean protein) were prepared by preparing two 5 mL 0.1 mol / L sodium hydroxide solutions. XT 55 Soy Protein Isolate and Chemically Modified XT 221D soy protein isolate). Once prepared, 40 milligrams (mg) of DABCO (1,4-diazabicyclo[2.2.2]octane) was added to each solution and allowed to dissolve. While DABCO was dissolved, 300 mg of poly(ethylene glycol) monoglycidyl ether-550Mn was added to each solution, followed by 0.75 g XT 55 soy protein isolate was added to one solution and 0.75 g XT221D soy protein isolate is added to other solutions. The solution is stirred at 600 rpm for 45 minutes at 65 ° C to produce chemically modified soy protein, which has a much higher solubility in aqueous solution than individual unmodified soy protein in 0.1 mol / L sodium hydroxide alone. Compared with the same protein solution without poly (ethylene glycol) monoglycidyl ether, the protein solution modified by poly (ethylene glycol) monoglycidyl ether is significantly more transparent, thereby indicating an increase in solubility. In addition, size exclusion chromatography (SEC) data indicate that the protein solution of soluble modification shows minimal hydrolysis, which indicates that the protein solubility is due to protein modification rather than hydrolysis due to the alkaline conditions used.
[0411] Embodiment 39
[0412] Chemically modified soybean protein solutions (chemically modified soybean protein) were prepared by preparing two 5 mL 0.1 mol / L sodium hydroxide solutions. XT 55 Soy Protein Isolate and Chemically Modified XT 221D soy protein isolate). Once prepared, 40 mg of DABCO (1,4-diazabicyclo[2.2.2]octane) was added to each solution and allowed to dissolve. While DABCO was dissolving, 300 mg of poly(ethylene glycol) diglycidyl ether-550Mn was added to the solution, followed by 0.75 g XT 55 soy protein isolate was added to one solution and 0.75 g XT 221D soy protein isolate is added to other solutions. The solution is stirred at 65°C with 600 rpm for 45 minutes to produce soy protein, which has a much higher solubility in aqueous solution than the individual unmodified soy protein in 0.1 mol / L sodium hydroxide alone. Compared with the same protein solution without poly(ethylene glycol) diglycidyl ether, the protein solution modified by poly(ethylene glycol) diglycidyl ether is significantly more transparent, thereby indicating an increase in solubility. In addition, SEC data indicate that the soy protein solution of soluble modification shows minimal hydrolysis, which indicates that the protein solubility is due to the hydrolysis of the protein modification rather than the alkaline conditions used.
[0413] Embodiment 40
[0414] The SPI was dispersed by adding 0.75 g of soy protein isolate (SPI) to 5 mL of 0.1 mol / L sodium hydroxide solution. XT55 SPI. The dispersion was stirred at 600 rpm with a magnetic stirring bar at 65°C for 2 hours. HeiQ Chemtex 2317 (anionic surfactant) was added in an amount of 5 parts per 100 parts of protein by mass. 5g of L3360 was then added to the solution and stirred at 600 rpm for 30 minutes. The SPI polyurethane solution was then pipetted into a Teflon evaporating dish with a diameter of 10 cm. The dish was dried in an oven at 45°C overnight. After drying, the dried sample was conditioned in a standard reference atmosphere (23°C, 50% humidity) for 24 hours to produce a SPI polyurethane alloy film.
[0415] Embodiment 41
[0416] The gelatin solution was prepared by dissolving 3.885g gelatin (Sigma Aldrich G2500) from porcine skin in 22mL deionized water and stirring at 450rpm for 1 hour at 50°C using an overhead impeller mixer. After the gelatin was completely dissolved, the pH of the solution was adjusted to 7.0 with 1N sodium hydroxide. After adjusting the pH, antimicrobial Ultra-Fresh DW-56 was added at 1.2 parts by weight per hundred parts of gelatin solution. The solution was then mixed at 50°C for 10 minutes to ensure that all components were well dispersed. After 10 minutes, 15mL of the solution was divided into equal parts and Antifoam 204 (a mixture of organic polyether dispersions derived from Sigma Aldrich) was added at 0.5 parts per hundred parts of the estimated final solution weight. The aliquoted solution was mixed at 50°C for 10 minutes to ensure that all components were well dispersed. Then, 25.885g L3360 was added to the solution. After adding L3360, the solution was mixed until a temperature of 43-45°C was reached.
[0417] To other aliquots of the solution, 5.5 parts of HeiQ Chemtex 2216-T (a stable blend of nonionic and anionic surfactants) and 2.2 parts of HeiQ Chemtex 2317 per hundred parts of solution weight, and 0.1 parts of HeiQ Chemtex 2243 (a nonionic silicone dispersion) per hundred parts of solution weight were added. The solution was then cooled and mechanically foamed until a wet density between 650 g / L and 850 g / L was reached at a temperature of 43° C. to 45° C., thereby forming a foam blend mixture.
[0418] A surface finish comprising a topcoat and a basecoat was prepared to create a front skin of a protein polyurethane alloy. The topcoat blend was formed by blending 9.74 parts of Stahl Melio WF-5227.A LIQ, 100 parts of Stahl WT-42-511, 30 parts of Stahl DI-17-701, 30 parts of Stahl XR-13-820, and 25 parts of water. The basecoat blend was formed by blending 450 parts of Stahl RC-43-023, 50 parts of Stahl RU-3901, 150 parts of Stahl RA-30, 50 parts of Stahl FI-1208, 30 parts of Stahl XR-13-820, and 100 parts of Stahl RA-22-063.
[0419] The blended non-foamed solution was deposited on the dried front surface layer at a target wet thickness of 200 gsm using a knife coating device and dried in a Mathis LTE-S Labcoater for 15 minutes at 75°C, an air speed of 2000 rpm, and 70% of the air was blown out from the sample below to form a protein polyurethane alloy layer. After the first layer was dried, a second layer of the blended foamed solution was deposited on top of the first layer at a target wet thickness of 350 gsm and dried in a Mathis LTE-S Labcoater for 15 minutes at a ramp drying program starting from 75°C for 5 minutes, then at 100°C for 5 minutes, and finally at 120°C for 5 minutes, an air speed of 700 rpm, and 70% of the air was blown out from below to form a first foamed protein polyurethane alloy layer. After the foamed layer was dried, a third layer of the blended foaming solution was deposited on top of the first foamed layer with a target wet thickness of 350 gsm and dried in a Mathis LTE-S Labcoater for 15 minutes starting from 75°C for 5 minutes in a ramp drying method, then at 100°C for 5 minutes, and finally at 120°C, an air speed of 700 rpm, and 70% air blown from below to form a second foamed protein polyurethane alloy layer.
[0420] After the sample was completely dried and conditioned in a conditioning room at 23°C and 50% humidity for 24 hours, the sample was cut and tested according to the DMA and tensile mechanical properties test described herein. The resulting second storage modulus transition (as the starting point of the last drop in the measured storage modulus, i.e., the second DMA modulus transition starting temperature) was 190°C, the Young's modulus was 88.9 MPa, the tensile stress was 5.4 MPa, and the elongation at break was 110%.
[0421] Embodiment 42
[0422] Samples were prepared by dissolving 1g of 50KDa rCol in 5mL deionized water and stirring with a magnetic stirring bar at 1000rpm for 1 hour at 20°C. 50KDa rCol protein is a collagen segment with an amino acid sequence listed as SEQ IDNO:2 prepared by Modern Meadow. After stirring for 1 hour, 6.7g of L3360 was added to the solution and stirred at 1000rpm for 30 minutes. Then polyurethane and 50KDa rCol solution were transferred to a Teflon evaporating dish with a diameter of 10cm. The dish was dried overnight in an oven at 45°C. After drying, the dried sample was conditioned for 24 hours to produce a 50KDa rCol polyurethane alloy film under a standard reference atmosphere (23°C, 50% humidity).
[0423] DMA testing was performed as outlined in Example 1. The resulting second storage modulus transition (as the starting point of the last drop in the measured storage modulus, ie, the second DMA modulus transition onset temperature) of the 50 KDa rCol polyurethane alloy was 177.8°C, 62.9°C higher than that of the control sample described in Example 1.
[0424] Tensile testing was performed as outlined in Example 1. The 50 KDa rCol polyurethane alloy had an average Young's modulus of 161 MPa, measured an average tensile stress of 17 MPa, and an average elongation at break of 173%.
[0425] Embodiment 43
[0426] By purchasing from CREATIVE 1g of natural Trichoderma cellulase (cellulase-RG) was dissolved in 5mL of deionized water and stirred at 1000rpm for 1 hour at 20°C with a magnetic stirring bar to prepare the sample. After stirring for 1 hour, 11.4g of L3360 was added to the solution and stirred at 1000rpm for 30 minutes. The polyurethane and cellulase solution was then pipetted into a Teflon evaporating dish with a diameter of 10cm. The culture dish was dried overnight in an oven at 45°C. After drying, the dried sample was conditioned for 24 hours in a standard reference atmosphere (23°C, 50% humidity) to produce a cellulase polyurethane alloy film.
[0427] DMA testing was performed as outlined in Example 1. The resulting second storage modulus transition (as the starting point of the last drop in the measured storage modulus, i.e., the second DMA modulus transition onset temperature) of the cellulase-RG polyurethane alloy was 153.1°C, 38.2°C higher than that of the control sample described in Example 1.
[0428] Tensile testing was performed as outlined in Example 1. The cellulase polyurethane alloy had an average Young's modulus of 184 MPa, measured an average tensile stress of 14.7 MPa, and an average elongation at break of 252%.
[0429] Embodiment 44
[0430] The sample was prepared by dissolving 1g of laboratory-grade cellulase (cellulase-IG) purchased from Carolina Biological Supply Company in 5mL of deionized water and stirring at 1000rpm for 1 hour with a magnetic stirring bar at 20°C. After stirring for 1 hour, 11.4g of L3360 was added to the solution and stirred at 1000rpm for 30 minutes. The polyurethane and cellulase solution was then pipetted into a Teflon evaporating dish with a diameter of 10cm. The dish was dried overnight in an oven at 45°C. After drying, the dried sample was conditioned for 24 hours in a standard reference atmosphere (23°C, 50% humidity) to produce a cellulase polyurethane alloy film.
[0431] DMA testing was performed as outlined in Example 1. The resulting second storage modulus transition (as the starting point of the last drop in the measured storage modulus, i.e., the second DMA modulus transition onset temperature) of the cellulase-IG polyurethane alloy was 122.1°C, 7.2°C higher than the control sample described in Example 1.
[0432] Tensile testing was performed as outlined in Example 1. The cellulase polyurethane alloy had an average Young's modulus of 84 MPa, measured an average tensile stress of 15.1 MPa, and an average elongation at break of 286%.
[0433] Embodiment 45
[0434] Two control samples (Example No. 45a and Example No. 45b) were each prepared according to the following method. 0.4 g of AF-715 (defoamer available from Quaker Color) was mixed into 38 grams of Hauthane HD-2001, an aqueous polyurethane dispersion from CL Hauthaway & Sons Corporation. The mixture was mixed using an impeller at a rate of 500 rpm and stirred at room temperature for 5 minutes. After the mixture was properly mixed, 0.6 g of Gel L 75N was added to increase the viscosity of the mixture and the mixture was mixed for 5 minutes. The mixture was then coated onto a release paper using a Mathis LTE-S Labcoater and dried at 75°C for 10 minutes and at 100°C for 10 minutes. The coating was then removed from the release paper to produce a protein-free polyurethane film.
[0435] After drying, the thickness of the sample of Example 45a was 0.4 mm, and the thickness of the sample of Example 45b was 0.4 mm. As reported in Table 7, the moisture vapor transmission rate of the polyurethane film of Example 45a was 30 g / m 2 / 24 hours, and the moisture vapor transmission rate of the polyurethane film of Example 45b was 38 g / m 2 / 24 hours.
[0436] Embodiment 46
[0437] Two samples (Example No. 46a and Example No. 46b) were prepared according to the following method. At 50°C, 13.25g of gelatin from pig skin was dissolved in a solution of 2g of antimicrobial Ultra-Fresh DW-56, 0.8g of AF-715 (a defoamer purchased from Quaker Color), and 75mL of water. The solution was stirred at 500rpm using an impeller until the gelatin was completely dissolved. The pH of the solution was then increased using 1M NaOH until a pH of 8 to 9 was reached. After the pH was adjusted, 77g of Hauthane HD-2001, an aqueous polyurethane dispersion from CL Hauthaway & Sons Corporation, was added to the gelatin solution and stirred for 15 minutes. After the gelatin and polyurethane solutions were properly mixed, 1g of RM-4410 from Stahl was added to increase the viscosity of the solution, and the solution was mixed for 5 minutes. The solution was then coated on a 0.35mm thick suede-like textile, the surface of which was coated with a thin film of DLS coating (thickness 0.03 mm). Use a handheld knife coating device to apply the gelatin polyurethane solution on a thin The DLS coating was placed on top of the film and allowed to dry in a standard reference atmosphere (23°C and 50% humidity) to produce a gelatin-polyurethane film with a textile backing. The DLS coating is used to prevent the gelatin polyurethane coating from penetrating deeply into the suede textile.
[0438] After drying, the thickness of the sample of Example No. 46a was 0.77 mm (gelatin-polyurethane film, thin film The total thickness of the DLS coating and the suede-like textile) and the thickness of the sample of Example 46b was 0.82 mm (gelatin-polyurethane film, thin film Total thickness of DLS coating and suede textile).
[0439] As reported in Table 7, the moisture vapor transmission rate of the sample of Example No. 46a was 180 g / m 2 / 24 hours, which is 150g / m2 more than the sample of Example No. 45a.2 / 24 hours, and increased by 142 g / m compared to the sample of Example No. 45b 2 / 24 hours. As also reported in Table 7, the moisture vapor transmission rate of the sample of Example No. 46b was 138 g / m 2 / 24 hours, which increased by 108g / m compared with the sample of Example No. 45a. 2 / 24 hours, and increased by 100 g / m compared to the sample of Example No. 45b 2 / 24 hours.
[0440] For the sample of Example No. 46a or 46b, the thin Neither the DLS coating nor the suede textile had a significant effect on the MVTR. In other words, the MVTR reported in Table 7 reflects the MVTR for the gelatin-polyurethane film only.
[0441] Embodiment 47
[0442] Two control samples (Example No. 47a and Example No. 47b) were each prepared according to the following method. 0.4 g of AF-715 (defoamer available from Quaker Color) was mixed into 38 g of aqueous polyurethane dispersion L3360 from Hauthaway. The mixture was mixed using an impeller at a rate of 500 rpm and stirred at room temperature for 5 minutes. After the mixture was properly mixed, 0.6 g of Gel L 75N was added to increase the viscosity of the mixture and the mixture was mixed for 5 minutes. The mixture was then coated onto a release paper using a Mathis LTE-S Labcoater and dried at 75°C for 10 minutes and at 100°C for 10 minutes. The coating was then removed from the release paper to produce a protein-free polyurethane film.
[0443] After drying, the thickness of the sample of Example No. 47a was 0.32 mm, and the thickness of the sample of Example No. 47b was 0.36 mm. As reported in Table 7, the moisture vapor transmission rate of the polyurethane film of Example No. 47a was 23 g / m 2 / 24 hours, and the moisture vapor transmission rate of the polyurethane film of Example No. 47b was 27 g / m 2 / 24 hours.
[0444] Embodiment 48
[0445] Two samples (Example No. 48a and Example No. 48b) were each prepared according to the following method. At 50°C, 13.25g of gelatin from pig skin was dissolved in a solution of 2g of antimicrobial Ultra-Fresh DW-56, 0.8g of AF-715 (a defoamer purchased from Quaker Color), and 75mL of water. The solution was stirred at 500rpm using an impeller until the gelatin was completely dissolved. The pH of the solution was then increased using 1M NaOH until a pH of 8 to 9 was reached. After the pH was adjusted, 77g of aqueous polyurethane dispersion L3360 from Hauthaway was added to the gelatin solution and stirred for 15 minutes. After the gelatin and polyurethane solutions were properly mixed, 1g of RM-4410 from Stahl was added to increase the viscosity of the solution, and the solution was mixed for 5 minutes. The solution was then coated on a 0.35mm thick suede-like textile, the surface of which was coated with a thin film of DLS coating (thickness 0.03 mm). Use a handheld knife coating device to apply gelatin and polyurethane solution on a thin The DLS coating was placed on top of the film and allowed to dry in a standard reference atmosphere (23°C and 50% humidity) to produce a gelatin-polyurethane film with a textile backing. The DLS coating is used to prevent the gelatin polyurethane coating from penetrating deeply into the suede textile.
[0446] After drying, the thickness of the sample of Example No. 48a was 0.77 mm (gelatin-polyurethane film, thin film The total thickness of the DLS coating and the suede-like textile fabric), and the thickness of the sample of Example No. 48b was 0.84 mm (gelatin-polyurethane film, thin film Total thickness of DLS coating and suede textile).
[0447] As reported in Table 7, the moisture vapor transmission rate of the sample of Example No. 48a was 117 g / m 2 / 24 hours, which increased by 94g / m compared with the sample of Example No. 47a. 2 / 24 hours, and increased by 90g / m compared with the sample of Example No. 47b 2 / 24 hours. As also reported in Table 7, the moisture vapor transmission rate of the sample of Example 48b was 74 g / m 2 / 24 hours, which increased by 51g / m compared with the sample of Example No. 47a. 2 / 24 hours, and increased by 47 g / m compared to the sample of Example No. 47b 2 / 24 hours.
[0448] For the sample of Example No. 46a or 46b, the thin Neither the DLS coating nor the suede textile had a significant effect on the MVTR. In other words, the MVTR reported in Table 7 reflects the MVTR for the gelatin-polyurethane film only.
[0449] Embodiment 49
[0450] Two control samples (Example No. 49a and Example No. 49b) were each prepared according to the following method. 0.2 g of AF-715 (defoamer available from Quaker Color) was mixed into 38 grams of aqueous polyurethane dispersion L3360 from Hauthaway. The mixture was mixed for 5 minutes at a rate of 500 rpm using an impeller. After the mixture was properly mixed, 0.6 g of Gel L 75N was added to increase the viscosity of the mixture and the mixture was mixed for another 5 minutes. This polyurethane mixture was then coated onto release paper using a Mathis LTE-S Labcoater and dried at 75°C for 10 minutes and at 100°C for 10 minutes.
[0451] Then, by mixing the aqueous polyurethane dispersion L3360 from Hauthaway with HeiQ Chemtex 2216-T (based on 3% of solution weight), HeiQ Chemtex 2317 (based on 3% of solution weight), HeiQ Chemtex 2241-A (based on 1% of solution weight) and HeiQ Chemtex2243 (based on 0.1% of solution weight) to prepare foam solution. Use impeller to stir the mixture at room temperature for 5 minutes with 500rpm. Then make the mixture foam to produce the foaming mixture between 700g / L and 900g / L of wet density. Use Mathis LTE-S Labcoater that the foaming mixture is coated on the polyurethane layer previously applied, and dry 10 minutes at 75 ℃, and dry 10 minutes at 100 ℃. After drying this first foaming coating, the second foaming coating made of identical foaming mixture is coated on the first foaming coating using the same conditions. After drying the second foaming layer, remove the three-layer sample from release paper.
[0452] The thickness of the three-layer sample of Example No. 49a was 0.23 mm, and the thickness of the three-layer sample of Example No. 49b was 0.24 mm. As reported in Tab...
Claims
1. A material comprising: Textiles; a protein polyurethane alloy disposed on the textile, the protein polyurethane alloy comprising protein dissolved in polyurethane; and From about 1 wt. % to about 16 wt. % of one or more fatliquors.
2. The material of claim 1, wherein the protein polyurethane alloy comprises greater than 50% by weight of the protein.
3. The material of claim 1, wherein the protein polyurethane alloy comprises from about 60% to about 90% by weight of the protein.
4. The material of any one of claims 1 to 3, wherein the one or more fatliquors comprise a functionalized oil.
5. The material according to any one of claims 1 to 3, wherein the one or more fatliquors are selected from the group consisting of sulfited fatliquors, sulfated fatliquors or combinations thereof.
6. The material according to any one of claims 1 to 5, wherein the material has an elastic modulus of 9*10^7 Pa or less.
7. The material according to any one of claims 1 to 5, wherein the material has an elastic modulus of 6*10^7 Pa or less.
8. A material comprising: Textiles; A protein polyurethane alloy comprising a protein dissolved in a polyurethane; a first portion having a first protein polyurethane alloy density; and A second portion having a second protein polyurethane alloy density different than the first protein polyurethane alloy density.
9. The material of claim 8, wherein the first protein polyurethane alloy has a density that is 5% or more less or greater than the second protein polyurethane alloy.
10. A material according to claim 8 or claim 9, wherein the first portion comprises a first protein polyurethane alloy layer, and wherein the second portion comprises a second protein polyurethane alloy layer.
11. The material according to claim 10, wherein: The textile comprises a top surface and a bottom surface, The first protein polyurethane alloy layer is disposed on the top surface of the textile, and The second protein polyurethane alloy layer is disposed over the bottom surface of the textile.
12. A material according to claim 8 or claim 9, wherein: The first portion comprises the protein polyurethane alloy integrated into the textile at the first protein polyurethane alloy density, and The second portion includes the protein polyurethane alloy integrated into the textile at the second protein polyurethane alloy density.
13. The material according to claim 8 or claim 9, wherein The textile comprises a first textile layer coupled to a second textile layer, The first portion comprises the protein polyurethane alloy integrated into the first textile layer at the first protein polyurethane alloy density, and The second portion includes the protein polyurethane alloy integrated into the second textile layer at the second protein polyurethane alloy density.
14. The material according to any one of claims 8 to 13, further comprising a cross-linking agent selected from the group consisting of an epoxy-based cross-linking agent, an isocyanate-based cross-linking agent, and a carbodiimide-based cross-linking agent.
15. The material of claim 14, wherein the crosslinking agent is a carbodiimide-based crosslinking agent.
16. An aqueous preparation, comprising: water; Waterborne polyurethane dispersion; protein; from about 4% to about 10% by weight of one or more colored dyes; and Foam stabilizer.
17. The formulation of claim 16, wherein the protein is dissolved within the polyurethane of the polyurethane dispersion.
18. A material comprising: Textiles; a protein polyurethane alloy integrated into the textile, the protein polyurethane alloy comprising a protein dissolved in a polyurethane; and About 100 wt % to about 250 wt % of one or more colored dyes, the wt % of the one or more colored dyes being measured relative to the weight of the protein in the protein polyurethane alloy.
Citation Information
Patent Citations
Yeast strains and methods for producing collagen
US20190002893A1
Yeast strains and methods for controlling hydroxylation of recombinant collagen
US20190040400A1
Recombinant yeast strains
US20190092838A1
Recombinant yeast strains
US20190093116A1
Methods for the production of gelatin and full-length triple helical collagen in recombinant cells
US6428978B1